Synaptic summation shapes information transfer in GABA-glutamate co-transmission - Belle Krubitski; Cesar Ceballos; Ty Roachford; Rodrigo F. O. Pena (Cognitive Neurodynamics, 2026)

Molecular characterization of extended-spectrum β-lactamases-producing Escherichia coli isolated from patients with bacteremia - Beatrice D. V. L. Souza; Guilherme Solveira; Guilherme F. R. de Souza; Henrique Orsi; Daiany R. P. De Lira; Iranildo do A. Fernandes; Adriano M. Ferreira; Alessandro L. Mondelli; Claudio T. Sacchi; Karoline R. Campos; Marlon B. N. Santos; Carlos H. Camargo; et al. (Brazilian Journal of Microbiology, 2026)
Bacteremia is a major health problem that affects millions of people worldwide. E. coli is one of the main pathogens associated with bacteremia and its resistance to the antimicrobial drugs, including β-lactams, has significantly increased in recent years. In view of the above, our objective was to determine the antimicrobial resistance profile of 60 E. coli isolates obtained from patients with bacteremia, as well as to characterize extended-spectrum β-lactamases (ESBL) -producing isolates. The highest resistance rates were observed for ciprofloxacin (33.3%), levofloxacin (31.7%), cefuroxime (20%) and cefotaxime (20%). Furthermore, 12 isolates (20%) were ESBL producers. Genomic analysis showed that 58.3% of these ESBL-producing isolates belonged to the phylogroup B2, ST131, serotype O25:H4 and carried the following ESBL-encoding genes: bla CTX−M−15 (66.7%), bla CTX−M−8 (16.7%), bla CTX−M−2 (8.7%) or bla CTX−M−27 (8.7%). Our data highlight the high frequency of E. coli ST131 among the ESBL-producing isolates obtained from patients with bacteremia in Botucatu, Brazil.

Forest conversion is more strongly associated with soil microbial functioning than chronic trace element exposure in an industrialized coastal mediterranean ecosystem - S. Fabian Plaza; F. Gonzalo Tortella; Giovanni Larama; Rodrigo Rodriguez; Thierry Lebeau; Clémentine Lapie; Walter Valdivia; Eros Fajardo; M. Fernández-Baldo; Juan Hirzel; Gustavo Santoyo; Mauricio Schoebitz (Environmental Pollution, 2026)

Organic acid-mediated solubilization of sedimentary and igneous phosphate rocks: Mineralogical controls on phosphorus release for sustainable agriculture - Sendy M. Soares; Vinícius F. Majaron; Rodrigo Klaic; Caue Ribeiro; Cristiane S. Farinas; Ricardo Bortoletto-Santos (Journal of Environmental Chemical Engineering, 2026)

Far from the coast: organohalogen bioaccumulation in spinner dolphins from the Southwestern Atlantic - Caroline A.C. Corrêa; Bárbara M.R. Manhães; Nara Oliveira-Ferreira; Elitieri B. Santos-Neto; Eduardo R. Secchi; Juliana C. Di Tullio; Rodrigo C. Genoves; Haydée A. Cunha; Tatiana L. Bisi; Alexandre F. Azevedo; José Lailson-Brito (Marine Pollution Bulletin, 2026)

Oat vs. corn grain for finishing Merino Dohne lambs: Intake stability, growth performance, and meat quality during wet-aging - María Sol Villaverde; Ethel E. Pérez; Hugo M. Arelovich; Mariano Menghini; Rodrigo D. Bravo; Marcela F. Martínez (Small Ruminant Research, 2026)

Large-scale toxic bloom of Dinophysis acuminata complex following a major flood disaster in southern Brazil - Luiz L. Mafra; Bruna Fernanda Sobrinho; Ana Martínez; Karoline Magalhães F. Lubiana; Regiane Valejo Maciel; José Guilherme F. Bersano; Luciano F. Fernandes; Fabiola Kaviatkovski; Pedro Almeida Rodrigo; Rafaela Cristine Zem; Carlos E.J.de Azevedo Tibiriçá; Mathias Alberto Schramm; et al. (Harmful Algae, 2026)

Stepwise versus gradual deterioration: Consequences for evolutionary rescue - Rodrigo A.S. Ribeiro; Osmar Freitas; José Alexandre F. Diniz-Filho; Paulo R.A. Campos (Ecological Modelling, 2026)

Evaluation of deep learning-based pipelines for salmon segmentation and multi-object tracking in commercial aquaculture cages - Martin Campos; Juan C. Aguilera; Marcos D. Zuniga; Luis F. Leiva; Julio Lopez; Nicolas Jara; Mohamed A. Ahmed; Manuel Pedraza; Alexis Alva; Rodrigo Carvajal; Gonzalo Carvajal (Aquacultural Engineering, 2026)

The role of global warming trend and tropical interannual variability as drivers of South America’s 2022–2024 climate extremes - Leonardo Mamani; Wallace Cevalho; Renato Trevisan Signori; Itamara Parente de Souza; Mary Toshie Kayano; Jorge Molina-Carpio; Rodrigo Augusto F. de Souza; Jhan-Carlo Espinoza; Rita V. Andreoli (Climate Dynamics, 2026)
From 2022 to 2024, South America experienced unprecedented regional climate extremes with severe socioeconomic impacts. These included extreme anomalies in temperature and precipitation, causing extreme drought conditions in southeastern South America and the Altiplano during spring 2022; extreme fire weather in central Chile in summer 2023; flooding in Rio Grande do Sul during autumn 2024; and the multiyear Amazon drought persisting throughout the springs 2022–2024. While these events were linked to the Global warming trend (GWT), Tropical interannual variability (TIV), and synoptic-scale processes, their contributions need to be clarified. Using linear regression, we decomposed the observed climate anomalies during 1998–2024 into GWT and TIV components and derived a Residual component representing anomalies not explained by either. This approach clarifies, through seasonal spatial patterns and contributions from regional variance, the roles of GWT and TIV in observed climate extremes across South America. From spring 2022 to spring 2024, GWT exhibited a strong background warming anomaly, while TIV displayed unusually robust teleconnections, particularly during its positive phases. As a result, a significant part of precipitation variability associated with climate extremes across the continent was driven by TIV, whereas GWT dominated in central-southern Chile. Both TIV and GWT contributed substantially to widespread South American warming, with GWT becoming the dominant influence as TIV weakened, except in central-southern Chile, where other factors prevailed. The unprecedented concurrence of strong GWT and combined TIV forcing amplified and prolonged climate extremes across the continent. The framework presented here can support climate extremes attribution worldwide.

Optimization of the production of biolubricants from a residual oil by a hydroesterification strategy: Yield-dependent performance evaluation of home-made combi-biocatalyst systems - Rodolpho R.C. Monteiro; Maria M.F. de Melo Neta; Adriano A. Mendes; F. Murilo T. de Luna; Roberto Fernandez-Lafuente; Rodrigo S. Vieira (Sustainable Chemistry and Pharmacy, 2026)

Risk of failure of insecticides and Cry/Vip Bt maize hybrids to control field populations of fall armyworm in Brazil - Josélia C.O. França; Hugo M. Monteiro; Rafael M. Pitta; Simone M. Mendes; João G.T. Moraes; Arleide F. Neto; Royner J. Ortiz-Rojas; Rodrigo J.S. Satolo; Leidiana M. Ribeiro; Yann J.M. Campos; Thadeu C. Souza; Eliseu J.G. Pereira (Crop Protection, 2026)

Using La2O3/Printex carbon cathode for simultaneous H2O2 generation and synergistic amitriptyline degradation in aqueous matrices - F. Escalona-Durán; C.H.M. Fernandes; G.O.S. Santos; R.J.A. Felisardo; W.R.P. Barros; R. Colombo; M.A. R. Rodrigo; M.R.V. Lanza (Process Safety and Environmental Protection, 2026)

Late Quaternary change in sources and burial of organic carbon off Northeastern Brazil - Alice Maria da S. Rodrigues; Rodrigo de L. Sobrinho; Patrícia Piacsek; Ioanna Bouloubassi; Arnaud Huguet; Ana Luiza S. Albuquerque; Igor M. Venancio; Thiago P. Santos; Joana F. Cruz; Marcelo C. Bernardes (Quaternary Science Reviews, 2026)

Microparticulated whey proteins: a literature review - Igor L. de Paula; Paola F. Lazzarini; Alan F. Wolfschoon-Pombo; Thomas Spiegel; José Toro-Sierra; Rodrigo Stephani (International Dairy Journal, 2026)

Influence of carbohydrate on the microparticulation process of whey proteins: structural modifications and indicators of the Maillard Reaction - Igor L. de Paula; Natalia C. Mesa; Alan F. Wolfschoon-Pombo; Uwe Schwarzenbolz; Thomas Henle; Ítalo T. Perrone; Luiz Fernando C. de Oliveira; Rodrigo Stephani (International Dairy Journal, 2026)

Range-wide monitoring reveals demographic vulnerability in Lahille's bottlenose dolphins - Fábio G. Daura-Jorge; Paula Laporta; Ignacio B. Moreno; Paulo H. Ott; Paulo A.C. Flores; Pedro Volkmer de Castilho; André S. Barreto; Rodrigo Cezar Genoves; Carolina Bezamat; Alexandre M.S. Machado; Eduardo R. Secchi; Silvina Botta; et al. (Biological Conservation, 2026)

Effect of supplementation with different trace minerals sources and fibrolytic enzyme on the productive and reproductive performance of Nellore cows on pasture - Keuven S. Nascimento; Amanda C. M. Queiroz; Aline N. Rodrigues; Luiz F. Costa e Silva; Carlos R. Zilioti; James E. Pettigrew; Rodrigo S. Marques; Flávio D. Resende; Gustavo R. Siqueira (Tropical Animal Health and Production, 2026)

Patterns of resource use in loggerhead turtle (Caretta caretta) from the Southwestern Atlantic Ocean - Celina Carolina Almeida; Rodrigo F. Bastos; Sérgio C. Estima; Andrine Paiva da Silva; Gabriela M. Vélez-Rubio; Danielle S. Monteiro (Marine Biology, 2026)
The Southwestern Atlantic Ocean (SWAO) is an important feeding and developmental area for loggerhead turtle ( Caretta caretta ). However, long-term patterns of resource use across life stages and sexes remain poorly understood for the species in this region. Here, we used stable isotope analysis (SIA) of sequential layers of carapace scutes to investigate resource use of loggerhead turtles in the SWAO across life stages and sexes. Scute samples were collected from 42 individuals stranded or incidentally caught by pelagic longline and bottom pair trawl fishery in southern Brazil and Uruguay (from 31º21′S–51º05′W to 34º55′S–56º09′W), between 2013 and 2024. Cluster analysis based on δ¹⁵N values revealed two distinct groups, corresponding to oceanic and neritic foraging habitats, whereas linear mixed models indicated ontogenetic increases in δ¹³C and δ¹⁵N values consistent with habitat shifts. Significant differences between sexes were observed only for δ¹³C values. Bayesian mixing models (MixSIAR) were used to estimate prey contributions to the diet, based on isotopic values from the literature, revealing a dominance of pelagic prey in oceanic non-shifters and of benthic invertebrates in neritic non-shifters. Shifters showed a transition from oceanic to neritic habitats, with a dietary shift from pelagic to benthic prey, reflecting two main ontogenetic shift patterns: discrete and facultative. Our results enhance the understanding of life-history variation in loggerhead turtles and highlight that sequential analysis of carapace scutes is a valuable tool for reconstructing long-term resource use patterns, providing a broader view of the ecology of this long-lived and endangered species.

Influence of Joint Degradation on the Stand-up Time of Rock Structures Around Underground Openings - Karina F. F. Lima; Rodrigo P. de Figueiredo; Louis D. G. Tabosa (Geotechnical and Geological Engineering, 2026)
The progressive degradation of joints in rock masses may occur through time-dependent failure of intact rock bridges along discontinuity planes, leading to a reduction in joint cohesive strength and, ultimately, to the onset of instability in underground excavations. This paper investigates the role of rock bridges in controlling the stability of a symmetrical roof block in a circular opening, under the assumption of temporally evolving bridge failure and the associated reduction in joint cohesion, in order to estimate the stand-up time of the block. The analytical framework is developed under plane-strain conditions. Five parametric scenarios are defined based on distinct fracture toughness values, which are interpreted as representative of different rock-quality classes. The results indicate that cohesion decays over time to a critical threshold at which the block attains limit equilibrium, thereby defining the stand-up time for each scenario. A global sensitivity analysis, combining the Morris elementary-effects method with Monte Carlo–based uncertainty propagation, demonstrates that the in situ stress ratio, the bridge-to-joint length ratio, and the joint friction angle are the primary controlling parameters. These factors exhibit comparable influence and are markedly more important than the parameters governing subcritical crack-growth kinetics. Complementary finite-element simulations conducted with RS2 illustrate the stress distribution mechanism that drives bridge-localized failure. Incorporating both time-dependent degradation mechanisms and reliability-based uncertainty propagation facilitates a probabilistic estimation of stand-up time, thereby providing a more robust basis for the design and safety assessment of underground excavations.

Strategies and successes of smoking cessation methods in head and neck cancer patients: a systematic review - Vincent Vander Poorten; Justine Van Rossum; Malene Roosens; Sandra Nuyts; Carol. R. Bradford; Juan Pablo Rodrigo; Remco De Bree; Karthik N. Rao; Orlando Guntinas-Lichius; Nabil F. Saba; Alfio Ferlito (Cancer and Metastasis Reviews, 2026)

Rearing substrate modulates mealworm (Tenebrio molitor) bioactivity: Implications for rainbow trout (Oncorhynchus mykiss) innate immune and oxidative status - Diogo Amaral; Mariana Girão; Thaís Cavalheri; Gabriel Campos; Ralph Urbatzka; Maria F. Carvalho; Alex H.L. Wan; Helena Peres; Rodrigo O.A. Ozório (Fish & Shellfish Immunology, 2026)

The Level and Nature of Impairment on the Iowa Gambling Task Following Acquired Brain Injury: A Meta-analysis - Sammy Moore; Kristin Naragon-Gainey; Carmela F. Pestell; Rodrigo Becerra; Melissa T. Buelow; Danielle M. Fynn; Michael Weinborn (Neuropsychology Review, 2026)
The Iowa Gambling Task (IGT) is a popular measure of risky decision-making, but to date, no formal quantitative reviews have been conducted, focused exclusively on IGT performance amongst individuals with acquired brain injury (ABI). Therefore, this meta-analytic study firstly explored performance differences between individuals with ABI vs controls. Second, we extended this comparison by investigating differences in IGT scoring and interpretive approaches (e.g., total score vs later block analysis). Finally, we explored potential IGT performance moderators (e.g., average age). A total of 25 studies, containing 39 samples (total n = 2188), were included. Overall findings suggested that the IGT is sensitive to the presence of ABI, particularly non-TBI and medically confirmed TBI, which becomes evident by block 2 of 5. Medium effect sizes were obtained for IGT total score, as well as indicators using later blocks only. Performance moderators such as population type and region influenced IGT performance, whilst average age, average education, and proportion of males did not. These results indicate that the IGT is sensitive to decision-making impairment following ABI, although we conclude that further research is needed to confirm the IGT’s ability to detect impairment relative to specific brain regions.

Effects of two advanced footwear technology shoes on durability in trained male runners - A. Alda-Blanco; S. Rodríguez-Barbero; F. Valero; J. J. Salinero; V. Rodrigo-Carranza; J. M. González-Ravé; F. González-Mohíno (German Journal of Exercise and Sport Research, 2026)

How climate variability modes influenced the fires in South America during the extreme droughts of 2023–2024 - Renato Trevisan Signori; Leonardo Mamani; Wallace Cevalho; Itamara Parente de Souza; Mary Toshie Kayano; Maria Betânia Leal de Oliveira; Wilmar L. Céron; Rita Valéria Andreoli; Rodrigo Augusto F. de Souza (Science of The Total Environment, 2026)

Modeling Future Climate Impacts on Brazil’s Operational Wind and Solar Energy Capacity - Felipe Husadel Poyer; Francisco Lopes Lima; Rodrigo Santos Costa; André Rodrigues Gonçalves; Fernando R. Martins; André F. P. Lucena; Enio Bueno Pereira (Environmental Modeling & Assessment, 2026)
Over the past decade, the Brazilian electricity sector has undergone a profound transformation, driven by the large-scale deployment of wind and solar photovoltaic power plants, a trend that is expected to continue in the years ahead. Although the transition to these variable renewable energy resources helps to reduce greenhouse gas emissions and mitigate the climate crisis, they are vulnerable to the very climate changes they help to avert. This study uses projections from CMIP6 global climate models under two future scenarios (SSP2-4.5 and SSP5-8.5) to assess potential impacts on power generation in the existing centralized wind and solar power facilities in Brazil. The study innovates by assessing the effects of climate change on the future performance of the power plants using measured historical capacity factors as a proxy, thereby eliminating the need for climate bias correction and standardized manufacturer power curves. Projections indicate a nationwide increase in wind potential between 6% and 15% by the end of the century, contributing to an extended wind season in the northeastern region and a stronger seasonality in the southern region. In contrast, the photovoltaic potential reveals modest change; the positive effects of increasing surface radiation are counterbalanced by the negative effects of warmer air temperatures across the assessed scenarios. These findings offer valuable insights for strengthening Brazil’s energy security under future climate conditions.

Serum Neurofilament Light Levels in Patients with Cerebrotendinous Xanthomatosis: a Pilot Study - Antonio Edvan Camelo-Filho; Pedro Lucas Grangeiro Sá Barreto Lima; Rodrigo Fagundes da Rosa; Oliver R Miyajima; Matheus Henrique Brustolim Marcucci; Stephanie Suzanne de Oliveira Scott; Luis Edmundo Teixeira de Arruda Furtado; Annyta F Frota; Michelle V R Soares; Danielle S Macedo; André Pessoa; Paulo R Nóbrega; et al. (The Cerebellum, 2026)
Introduction: Cerebrotendinous xanthomatosis (CTX) is a rare autosomal recessive disorder caused by pathogenic variants in CYP27A1 , leading to cholestanol accumulation and progressive neurological dysfunction. Neurofilament light chain (NfL) is a biomarker of neuroaxonal injury in several hereditary ataxias, but its role in CTX has not been investigated. We aimed to determine whether serum NfL is elevated in CTX and whether it correlates with clinical severity. Methods: Five genetically confirmed CTX patients and five age-, sex-, and body mass index–matched healthy controls were evaluated. Clinical severity was assessed using the Scale for the Assessment and Rating of Ataxia (SARA). Serum NfL concentrations were measured using single-molecule array technology. Group comparisons were performed using the Mann–Whitney U test, and associations were assessed using Spearman’s correlation coefficient. Results: Serum NfL levels were significantly higher in CTX patients than in controls (median 14.63 pg/mL [interquartile range 5.10–18.17] vs. 2.90 pg/mL [2.52–3.56]; p = 0.008). Within the CTX group, NfL levels showed a strong positive correlation with SARA scores (Spearman's ρ = 0.90, p = 0.037), indicating higher NfL levels in patients with greater neurological impairment. Conclusion: Serum NfL is elevated in CTX and correlates with ataxia severity, supporting its potential relevance as a marker of neuroaxonal injury in this disorder. Larger longitudinal studies are needed to confirm these preliminary findings and clarify the role of NfL in disease monitoring.

Taxonomic uncertainty: causes, consequences, and metrics - Leila Meyer; Richard J. Ladle; Rafaela J. Trad; Annelise Frazão; Lívia Frateles; Thainá Lessa; Rafael B. Pinto; Tiago M.S. Freitas; Geiziane Tessarolo; Jhonny J.M. Guedes; Rodrigo A. Castro-Souza; Herison Medeiros; et al. (Trends in Ecology & Evolution, 2026)

On the importance of soil texture for predicting future global soil respiration - Lucas Carvalho Gomes; Cássio Marques Moquedace; Ivan F. Souza; Ben Bond-Lamberty; Rodrigo Vargas; Lars Vesterdal; Gustavo V. Veloso; Marcio Rocha Francelino; Carlos E.G.R. Schaefer; Kendalynn A. Morris; Elpídio I. Fernandes-Filho (Science of The Total Environment, 2026)

Bisphenols removal from wastewater in a MBBR-photocatalysis system: Performance and biofilm community dynamics - Amanda F. do Amaral; Marina M.G. Pastre; Rodrigo Coutinho; Lia Teixeira; Marcia Marques (Journal of Water Process Engineering, 2026)

A new approach for HEMS to optimize cost, emissions and comfort through a smart integration of V2G, load scheduling, and PVT generation - Rodrigo Fiorotti; Jussara F. Fardin; Helder R.O. Rocha; Augusto C. Rueda-Medina; Antonio M. Pantaleo; Mohammad R. Nasab; Sergio Bruno (Energy and Buildings, 2026)

Non-native mollusc species in Brazil: a first national inventory and distributional overview - Fabrizio Marcondes Machado; Rodrigo B. Salvador; Igor C. Miyahira; Luiz Ricardo Lopes de Simone; Tarcilla C. de Lima; Mariana Osório Côrtes; Julia D. Sigwart; Angie Patiño Montoya; Vanessa S. Amaral; Paula Spotorno; Marcel Sabino Miranda; Augusto L. Ferreira Júnior; et al. (Biological Invasions, 2026)

Post-fire short-term treatments on a hillslope burnt soil: a case in the NW Iberian Atlantic transition region - M. Fernández-Raga; S. Alcalde-Aparicio; F. Serrano-Bernardo; A. Kavian; A. Cerda; J. Rodrigo-Comino (Small-scale Forestry, 2026)
Forest fires pose a significant threat to rural areas, affecting ecosystems, property, infrastructure, and human lives. Effective post-fire management strategies are crucial for short-term ecosystem and community recovery. This study evaluated the effectiveness of three post-fire interventions in reducing soil erosion and runoff within a temperate Atlantic–transition climate, focusing on a shrubland hillslope near organic vineyards in Corullón, NW Spain, after a moderate-severity fire. The research aimed to (i) compare the effects of plowing, straw mulching, and no intervention (control) on post-fire soil recovery, and (ii) assess the cost-effectiveness and environmental impacts of these treatments. Ten experimental plots were randomly assigned to plowing (n = 4), straw mulching (n = 4), or control (n = 2). Seventeen rainfall events were monitored between 15 days and six months post-fire. Results showed no significant differences in erosion or runoff reduction among treatments. Natural vegetation recovery, assessed visually, was rapid across all plots, with erosion and runoff stabilizing within two months. These findings suggest that, under the specific conditions of this temperate climate and moderate fire severity, early intervention techniques may not be necessary. The study concludes that natural regeneration can be a viable and cost-effective post-fire management strategy in regions with favorable environmental conditions for soil recovery, potentially reducing the need for intensive interventions.

Removal of Bisphenol A, Bisphenol S, and Estrogenic Activity from Real Wastewater Using a Multi-stage IFAS System - Amanda F. do Amaral; Alexandre S. A. da Silva; Deivisson L. Cunha; Priscila M. de O. M. Cunha; Rodrigo Coutinho; Marcia Marques (Bulletin of Environmental Contamination and Toxicology, 2026)
This study evaluated the removal of bisphenol A (BPA), bisphenol S (BPS), and estrogenic activity from real municipal wastewater using a pilot-scale multi-stage integrated fixed-film activated sludge (MS-IFAS) system. The configuration comprised five sequential reactors (Anaerobic, Anoxic-1, Aerobic under IFAS, Anoxic-2, and Re-aeration) providing distinct redox conditions. Influent concentrations averaged 112.6 ± 49.5 µg L −1 for BPA and 6.6 ± 3.0 µg L −1 for BPS. Overall removal efficiencies reached 99.8 ± 0.1% and 97.7 ± 1.0%, respectively, despite influent variability. The aerobic IFAS reactor was the main contributor to contaminant degradation, maintaining performance even after a > 90% biomass loss. Estrogenicity, assessed by the Yeast Estrogen Screen assay and expressed as 17β-estradiol equivalents (E2-EQ) decreased by 83.2% (0.031–0.005 ng L −1 ). Effluent E2-EQ values were below ecotoxicological thresholds, indicating negligible estrogenic risk to aquatic organisms. These highlight the strong potential of MS-IFAS for removal of xenoestrogenic contaminants in real wastewater.

Life cycle assessment and costing of indoor VOC removal via electro-absorption and in situ electrochemical regeneration of activated carbon - Rafael Granados-Fernández; Javiera F. Gutiérrez-Espinoza; Alberto Rodríguez-Gómez; Manuel A. Rodrigo; Justo Lobato; Carmen M. Fernández-Marchante (Science of The Total Environment, 2026)

Replacing Conventional Fertilization with Organomineral Fertilizer in ‘Hass’ Avocado Trees Improves Chlorophyll Indices and Fruit Size: A Bootstrap Simulation Approach - Marllon F. S. dos Santos; Rodrigo J. Milan; Bruna M. Costa; Tatiana E. Cantuarias-Avilés; Idemauro A. R. de Lara; Simone R. da Silva (Applied Fruit Science, 2026)
Modern agriculture faces significant challenges related to the depletion of finite resources used in fertilizer production. In response to this situation, the market has been adapting by developing biofertilizers or organomineral fertilizers, which incorporate an organic fraction into their composition. These fertilizers provide nutrients more gradually, reducing leaching. Studies on this topic are scarce for avocado trees, whose global production has been increasing. For this reason, the present research aimed to compare conventional fertilization with organomineral fertilization in ‘Hass’ avocado trees. A total of 20 plants per treatment were used in a commercial orchard, with treatments providing the same amount of nutrients. Variables related to vegetative growth, gas exchange, and productive data were evaluated. Data analysis was performed using bootstrap simulations, a resampling technique with 10,000 simulations, which enabled the construction of confidence intervals for the variables being assessed, resulting in an experimental optimization. Although no significant differences were detected in overall yield, the organomineral treatment showed increases of up to 10% in chlorophyll levels, 17.69% in fruit weight, and 8.35% and 9.18% in fruit length and diameter, respectively, compared to the conventional treatment. The bootstrap technique proved effective for analyzing this type of experiment, confirming the benefits of replacing conventional fertilization with organomineral fertilization, which provides nutrients more efficiently and sustainably.

PAH pollution in water and blue mussels (Mytilus edulis) along the northern Portuguese Atlantic Coast: Evaluation of ecological and human cancer risks - Ana Margarida Esteves; Rodrigo F. Alves; Eduardo Rocha; Maria João Rocha (Marine Pollution Bulletin, 2026)

Sequential extraction of heavy metals from sediments of the Maipo River basin, Chile - Sylvia V. Copaja; Sebastián Ortiz; F. Nacaratte; Valeria Hermosilla; Rodrigo Pardo (CATENA, 2026)

Analysis of the energy and nature of bandgap in layered double hydroxides Mg-Al-X and Zn-Al-X (X= Cl − , OH − , CO 3 2 − , or NO 3 − ) - Márcio F. Santos; Pedro Ivo R. Moraes; Sérgio R. Tavares; A.S. Martins; Rodrigo B. Capaz; Fernando Wypych; Alexandre A. Leitão (Applied Clay Science, 2026)

Historical Temperature Stability and Environmental Drivers Shape Patterns of Phylogenetic Diversity in Cactaceae - Afonso Kempner; Rodrigo Castro‐Souza; Dieison André Moi; Danilo Trabuco do Amaral; Rosane Garcia Collevatti; Sidney F. Gouveia; Isabel A. S. Bonatelli; Thadeu Sobral‐Souza (Journal of Biogeography, 2026)
Aim We aim to investigate the environmental drivers shaping macroecological patterns of phylogenetic structure in plants, using the cactus family (Cactaceae) as a model group. Major Taxa and Location Cactus family (Cactaceae), comprising 1892 species, distributed across the American continent (approximately 42 million km 2 ). Methods We compiled a robust dataset of 435,694 occurrence records and estimated two complementary metrics of phylogenetic structure: the standardised effect size of mean phylogenetic distance (ses.MPD, reflecting deep/basal lineages) and mean nearest taxon distance (ses.MNTD, reflecting recent/tip lineages). We also assessed the effects of climatic, topographic, and soil‐related variables on phylogenetic structure metrics at regional and continental scale. Results Phylogenetic structure in cacti is shaped by complex spatial interactions among environmental drivers varying across scales. Northern Mesoamerica—including central and northern Mexico and the southwestern United States—showed the highest ses.MPD but some of the lowest ses.MNTD values. This indicates that these regions harbour deeply divergent lineages while local communities remain composed of closely related species. Other regions, such as high‐elevation areas in South America, also showed high ses.MPD and ses.MNTD, indicating both deep and recent phylogenetic divergence. ses.MPD and ses.MNTD responded differently to environmental gradients, indicating that basal and tip lineages are influenced by different factors. Historical temperature stability (calculated as the temperature delta between the last glacial maximum and the present) was the strongest predictor of phylogenetic structure, mainly on a regional scale. Solar radiation and elevation, at the continental scale, also contributed to these patterns, indicating that topographic complexity and climatic drives recent phylogenetic divergence. Main Conclusions Cactus phylogenetic diversity is primarily driven by historical temperature stability but results from the combined influence of multiple environmental drivers acting across scales. These scale‐dependent effects reveal that cactus communities reflect both contemporary conditions and long‐term evolutionary constraints. Given the link between PD, ecosystem functioning, and conservation value, high‐PD regions, especially those with stable climates and heterogeneous topography, should be prioritized for conservation.

Behavior of anthropogenic particles on coastal seawater and intertidal sediment of a gulf in Patagonia Argentina - Ayelén Costa; Juan P. Pisoni; Juan P. Tomba; E. Camila F. Tavano-Formigo; Rodrigo D. Hernández-Moresino (Environmental Monitoring and Assessment, 2025)

In vitro and in silico schistosomicidal activity of hexane fraction from Copaifera oblongifolia leaves - Rafael Corrêa Ramos; Lizandra G. Magalhães; Rodrigo C. S. Veneziani; Sérgio R. Ambrósio; Híllary Ozorio Gobeti Caprini; Cibelle Ramos Da Silva; Jairo K. Bastos; Márcio L. Andrade e Silva; Erdi Can Aytar; Mario F. C. Santos; Wilson R. Cunha (In Silico Pharmacology, 2025)

Vegetation type and climate determine temperature thresholds of soil respiration across drylands - María Almagro; Ana Rey; Rosa M. Inclán; Josep Barba; Rodrigo Vargas; Arnaud Carrara; José M. Grünzweig; Marcelo Sternberg; Yiftach Talmon; Rebecca L. McCulley; Sara Marañón-Jiménez; Penélope Serrano-Ortiz; et al. (Soil Biology and Biochemistry, 2025)

Plastic waste leakage in the oceans: Socioeconomic influences, predictive modeling with artificial intelligence and wavelet analysis - Iwldson G.S. Santos; Adalgiza Fornaro; Daniel C. Zacharias; Ana L.F. Nascimento; Inaura P.S. Santos; Isnaldo I. Barbosa; José F. Oliveira-Júnior; Micejane S. Costa; Marcos F.M. Ferreira; Rodrigo M.S. Brito (Regional Studies in Marine Science, 2025)

Growth rate and finishing system alter beef color and early postmortem metabolism in Bos indicus crossbred cattle - Juan F. Morales Gómez; Patricia M. Ramos; Mariane Beline; Daniel S. Antonelo; Bruna Pavan; Rodrigo S. Goulart; Laila T. Kirkpatrick; David E. Gerrard; Saulo L. Silva (Meat Science, 2025)

Multi-trait GWAS for growth under contrasting thermal rearing conditions in rainbow trout (Oncorhynchus mykiss) - Jousepth Gallardo-Hidalgo; David A. Tapia; Baltasar F. Garcia; Rodrigo Marin-Nahuelpi; Pablo Cáceres; Liane N. Bassini; Vito A. Mastrochirico-Filho; Carolina Araya; José M. Yáñez (Molecular Genetics and Genomics, 2025)

Postsynaptic frequency filters shaped by the interplay of synaptic short-term plasticity and cellular time scales - Yugarshi Mondal; Guillermo Villanueva Benito; Rodrigo F. O. Pena; Horacio G. Rotstein (Journal of Computational Neuroscience, 2025)
Neuronal frequency filters can be thought of as constituent building blocks underlying the ability of neuronal systems to process information, generate rhythms and perform computations. How neuronal filters are generated by the concerted activity of a multiplicity of processes (e.g., electric circuit, history-dependent) and interacting time scales within and across levels of neuronal network organization is poorly understood. In this paper, we use mathematical modeling, numerical simulations and analytical calculations of the postsynaptic response to presynaptic spike trains to address this issue in a basic feedforward network motif in the presence of synaptic short-term plasticity (STP, depression and facilitation). The network motif consists of a presynaptic spike-train, a postsynaptic passive cell, and an excitatory (AMPA) chemical synapse. The dynamics of each network component are controlled by one or more time scales. We explain the mechanisms by which the participating time scales shape the neuronal filters at the (i) synaptic update level (the target of the synaptic variable in response to presynaptic spikes), which is shaped by STP, (ii) the synaptic level, and (iii) the postsynaptic membrane potential (PSP) level. We focus on three metrics that gives rise to three types of profiles (curves of the corresponding metrics as a function of the spike-train input frequency or firing rate): (i) peak profiles, (ii) peak-to-trough amplitude profiles, and (iii) phase profiles. The effects of STP are present at the synaptic update level and are communicated to the synaptic level where they interact with the synaptic time scales. The PSP filters result from the interaction between these variables and time scales and the biophysical properties and time scales of the postsynaptic cell. Band-pass filters (BPFs) result from a combination of low-pass filters (LPFs) and high-pass filters (HPFs) operating at the same or different levels of organization. PSP BPFs can be inherited from the synaptic level (STP-mediated BPFs) or they can be generated across levels of organization due to the interaction between (i) a synaptic LPF and the PSP summation-mediated HPF (PSP peaks), and (ii) a synaptic HPF and the PSP summation-mediated LPF (PSP amplitude). These types of BPFs persist in response to more realistic presynaptic spike trains: jittered (randomly perturbed) periodic spike trains and Poisson-distributed spike trains. The response variability is frequency-dependent and is controlled by STP in a non-monotonic frequency manner. The results and lessons learned from the investigation of this basic network motif are a necessary step for the construction of a framework to analyze the mechanisms of generation of neuronal filters in networks with more complex architectures and a variety of interacting cellular, synaptic and plasticity time scales.

Astrocytic signatures in neuronal activity: a machine learning-based identification approach - João Pedro Pirola; Paige DeForest; Paulo R. Protachevicz; Laura Fontenas; Ricardo F. Ferreira; Rodrigo F. O. Pena (Cognitive Neurodynamics, 2025)

Quantitative summary of nine years of fungicide efficacy data for managing white spot and protecting yield in maize - MonalisaC. De Cól; Karla Braga; AdrianoA.P. Custódio; Marcelo G. Canteri; Lucas H. Fantin; Carlos M. Utiamada; Hércules D. Campos; Dagma D. Silva-Araújo; Rodrigo V. Costa; InêsF.U. Yada; Aildson P. Duarte; Alfredo R. Dias; et al. (Crop Protection, 2025)

Delayed embryonic attachment, circulating pregnancy-associated glycoproteins, and pregnancy loss in heifer embryo recipients - João Paulo N. Andrade; Rafael R. Domingues; Victor E. Gomez-León; Guilherme Madureira; Luma C. Sartori; Gustavo F. Grillo; Meliton Fosado; Rodrigo V. Sala; Milo C. Wiltbank (Theriogenology, 2025)

Regression model for predicting beef carcass cutability in crossbred beef cattle - Welder A. Baldassini; Victor G. L. da Fonseca; Marcelo A. S. Coutinho; Gregori Rovadoscki; Rick A. F. Mangueira; Rodrigo N. S. Torres; Otávio R. Machado Neto; Guilherme L. Pereira; Rogério A. Curi; Luis Artur L. Chardulo (Tropical Animal Health and Production, 2025)

Patterns of circulating cytokines after 2 types of exercise in active type-1 diabetic patients - María Herranz-López; Rodrigo Martín-San Agustín; Mariló Olivares-Vicente; Laura Pardines-Oltra; Alba Cuerda Del Pino; Jorge Bondia; Paolo Rossetti; F. Javier Ampudia-Blasco; Enrique Roche (Journal of Physiology and Biochemistry, 2025)
Aerobic training (beneficial for type 1 diabetes mellitus (T1DM) patients) could result boring, leading to inactivity or suboptimal performance. Therefore, High-Intensity Interval Training (HIIT) could be an appealing alternative. The present study aimed to compare modulation of certain inflammatory cytokines in T1DM participants performing aerobic vs. HIIT routines. We recruited 26 T1DM male subjects: ages 18–40, T1DM ≥ 2 years, glycated hemoglobin < 8.5%, stable insulin regimen for 6 months, minimum 90 min weekly physical activity and completion of International Physical Activity Questionnaire (IPAQ). IPAQ:2 corresponds to moderate activity and IPAQ:3 to intense physical activity. Participants performed a single aerobic or HIIT session separated by at least 72 h. Blood plasma samples were collected 20 min before and after each session. Cytokines were measured using LUMINEX technique. After aerobic exercise, pro-inflammatory cytokines interleukin (IL)-1β, IL-6, IL-7, IL-8, IL-17 A, tumor necrosis factor-α (TNF-α) and interferon-γ (IFN-γ) showed no significant differences in participants (IPAQ:2 and 3). Only anti-inflammatory cytokine IL-2 increased significantly in IPAQ:3 participants. Compared to pre-exercise, post-exercise HIIT situation presented a similar pattern. The 4 participants (IPAQ:3) that voluntarily followed a 12-week HIIT routine, showed significant increases in IL-7, IL-8, and TNF- α, and the detection of the anti-inflammatory cytokine IL-22. Altogether, these results suggest that HIIT favors the presence of some pro-inflammatory cytokines. The anti-inflammatory action of certain cytokines, such as IL-22, should be considered for a possible compensatory action. Nevertheless, programs of interval exercises at moderate intensity could be at the moment a safe option for T1DM patients.

Historical Fragmentation in Atlantic Forest Explains the Diversification of a Clade of Mountaintop Bromeligenous Frogs (Leptodactylidae: Crossodactylodes ) - Marcus Thadeu T. Santos; Marcelo Gehara; Caroline B. Oswald; Rodrigo B. Ferreira; Fabrício R. Santos; Paulo C. A. Garcia; Kelly R. Zamudio; Célio F. B. Haddad; Rafael F. Magalhães (Zoologica Scripta, 2025)
The Atlantic Forest domain is a biodiversity hotspot with remarkable amphibian diversity, including over 700 species, 70% of which are endemic. Most of these endemic species have restricted geographic ranges, often confined to mountainous areas, as exemplified by the leptodactylid genus Crossodactylodes . These frogs are characterised by small body sizes, a bromeligenous habit and limited dispersal abilities, with species often restricted to their type localities. Previous studies have revealed geographically structured lineages within the genus, even when separated by short distances. Here, we focused on a clade of Crossodactylodes comprising three lineages from southeastern Brazil, inhabiting montane forest ‘islands’ distinct from surrounding lowland areas regarding vegetation structure and microclimate. We integrated genetic, geographic, morphometric and qualitative morphological data to assess species boundaries through species delimitation analyses and validation procedures. This integrative approach provided evidence supporting the recognition of one lineage as a distinct taxonomic entity, which we formally describe herein as Crossodactylodes alairi sp. nov. Additionally, we applied coalescent simulations and supervised machine‐learning approaches to evaluate alternative diversification hypotheses. Our results provide strong support for fragmentation models, suggesting that divergences within the focal lineages were driven by climate‐related habitat fragmentation during the Plio‐Pleistocene. Given that these lineages inhabit a non‐macrorefugium region of the Atlantic Forest, their evolutionary trajectories were likely shaped by survival in isolated microrefugia that offered stable and suitable microclimatic conditions amidst broader environmental changes.

Myiasis-causing flies in anurans: new interactions, geographic distribution, and an updated list of records in the Neotropics - Franciele Cristina de Souza; Victor Morais Ghirotto; Alexandre Polletini Neto; Camila Saraiva dos Anjos; André Luís F. da Silva; Rodrigo Lingnau; Emeline da S. Ceccon; Cátia Antunes de Melo-Patiu †; Mirco Solé; Silionamã P. Dantas; Claudio Borteiro; Domingos de J. Rodrigues; et al. (Biologia, 2025)

Hormonal control of the asymmetric uterus of the bat Molossus molossus during pregnancy and lactation: Emphasis on progesterone and estradiol - Juliana F. Ferraz; Rodrigo S. de Oliveira; Cornélio S. Santiago; Emília M. Soares; Rejane M. Góes; Eliana Morielle-Versute; Sebastião R. Taboga; Mateus R. Beguelini (Tissue and Cell, 2025)

Ecotoxicological implications of microplastics transformed by advanced oxidation processes with low oxidant concentrations - Jacqueline Aparecida Malvestiti; Maina Ruth Conceição Silva; Rodrigo Pereira Cavalcante; Valdemar L. Tornisielo; Renato F. Dantas (Journal of Environmental Chemical Engineering, 2025)

Three-dimensional discrete magnetic inversion using graph theory to determine the framework of isolated sources - Rômulo Rodrigues de Oliveira; Rodrigo Bijani; Nelson Ribeiro-Filho; Edson Alonso Falla-Luza; Cosme F. Ponte-Neto (Journal of Applied Geophysics, 2025)

Group living influences larval melanism in gregarious caterpillars - Mónica F. Cisternas; Rodrigo S. Ríos; Ernesto Gianoli (The Science of Nature, 2025)

Age-related Changes in Dehydroepiandrosterone-sulfate in Black-and-gold Howler Monkeys (Alouatta caraya) - Josi T. Melo; Gessiane P. Silva; Ana K. F. Pereira; Aline A. Imbeloni; Emilee N. Hart; Abbigail Swiney; Rodrigo H. F. Teixeira; Frederico O. B. Monteiro; Rafaela S. C. Takeshita (International Journal of Primatology, 2025)
Dehydroepiandrosterone-sulfate (DHEAS) is the most abundant steroid in humans and some nonhuman primates. This adrenal androgen contributes to immune enhancement, neuroprotection, and reproduction. In humans and apes, DHEAS levels increase before puberty, a phenomenon called adrenarche. However, a postnatal increase in the levels of these hormones is not apparent in cercopithecoids. In marmosets, DHEAS is only synthesized from female adrenal glands, if their ovarian function is compromised. However, DHEAS is poorly investigated among other platyrrhines. Our main objective was to test the influence of sex and age on fecal and serum DHEAS levels in black-and-gold howler monkeys ( Alouatta caraya ) under human care. We measured DHEAS levels in feces from 16 females and 21 males aged between 6 months and 26 years old and in serum from 27 of those animals using a commercial enzyme immunoassay kit. We found high levels of serum DHEAS in adult females, and DHEAS levels in fecal and serum samples were strongly and positively correlated. Fecal DHEAS levels showed a quadratic relationship with age, increasing from infancy to adulthood, then declining in older adults. There was no significant effect of sex, although females had a greater range than males. The postnatal increase in DHEAS levels in howler monkeys is like that of apes and humans, while the large variation in DHEAS levels among adult females suggests that, as in marmosets, DHEAS may be important for female howler monkey reproduction. This pattern highlights the importance of comparative studies to investigate the biological function of DHEAS in evolution. Graphical Abstract

Rainfall Variability in South America Modulated by the Central and Eastern Atlantic Niña Modes - Mary T. Kayano; Rita V. Andreoli; Leonardo Mamani; Wilmar L. Cerón; Itamara Parente Souza; Wallace Cevalho; Rodrigo A. F. Souza; Djanir Sales Moraes (International Journal of Climatology, 2025)
The present analysis examines the effects of the central Atlantic Niña (NCAN) and eastern Atlantic Niña (NEAN) modes on seasonal precipitation in South America (SA) and related atmospheric circulation during the 1951–2020 period. NCAN is the negative pole of broader Atlantic sea surface temperature (SST) modes: negative South Atlantic dipole (SAD) in all seasons, positive interhemispheric SST gradient (GRAD) in austral summer and autumn, and a weaker positive GRAD in winter. These modes modify the regional Hadley, intensifying the South American low‐level jet in autumn, winter and spring. In all seasons, the NCAN mode modifies the regional Walker cell by positioning its descending branch in the central equatorial Atlantic. This branch may extend westward due to the coupling of the negative SST and positive pressure anomalies in the NCAN area (summer and spring) or the anomalous surface warming in the eastern tropical Pacific (winter). Precipitation anomalies feature a dipole between northern (positive values) and northeastern (negative values) SA in summer and autumn and in the other seasons, negative values in northern SA and localised positive values south of 20° S in winter and in the 10° S–25° S band in spring. The NEAN modes have limited influence on the regional atmospheric circulation during summer and spring. But during autumn (winter), the regional anomalous Walker and Hadley cells associated with a negative (positive) GRAD mode and a negative SAD mode modulate the precipitation variability through wind changes. The GRAD mode with reversed polarity from autumn to winter explains the near‐reversed dipole precipitation anomaly patterns in tropical SA. The smallest (largest) differences in the seasonal precipitation anomalies between the NCAN and NEAN occur in winter (autumn). Since previous works did not distinguish the longitudinal position of the maximum SST anomalies, the present findings could be relevant for climate monitoring and modelling efforts.

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

Reproductive outcomes of prepubertal Bos indicus beef heifers raised in a feedlot system submitted or not to ovulation induction strategies prior to a timed-artificial insemination treatment regimen - Rodrigo L.O.R. Alves; Lucas O. e Silva; Carlos E.C. Consentini; Oseias P. Santos; Andrés A.C. Narváez; Leandro D. da Cunha; Rafael A. Braz; Maria E.R. e Silva; Rodrigo Brüner; Leonardo F. Melo; Roberto Sartori (Theriogenology, 2025)

Assessing the environmental health of urbanized mangroves on the Brazilian equatorial margin using widely consumed bioindicators (Ceará coast, Brazil) - Camila F. Alencar; Antônia D.F. Lima; Alessandra S.B. Moraes; Ana B. Costa; Rafael P. dos Santos; Maria G.L. Coêlho; Rodrigo Maggioni; Rivelino M. Cavalcante (Marine Environmental Research, 2025)

Trends in the study and impacts of brine discharge on benthic communities - Juan F. Hernández-Bentancor; Rodrigo Riera (Marine Environmental Research, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Ecosystem type modulates the effects of litter quality and litter identity on decomposition in a tropical riparian environment - Anderson Rocha Gripp; Ana Clézia Simplicio Moraes; Mery Ingrid Guimarães Alencar; Jorge Gabriel F. Genovez; Rodrigo Lemes Martins; Rafael Dettogni Guariento; Luciana Silva Carneiro; Adriano Caliman (Aquatic Ecology, 2025)

Characterising Long-Term Depressive Symptoms Post-brain Injury: A Systematic Review of Symptom Trajectory Groups and Their Predictors - Priscilla Prince; Kristin Naragon-Gainey; Rodrigo Becerra; Michael Weinborn; Carmela F. Pestell (Neuropsychology Review, 2025)
This systematic review investigates the long-term trajectories of depressive symptoms in individuals with acquired brain injury (ABI) and identifies factors predicting group membership in these trajectories. The review follows the PRISMA guidelines and is registered on the International Platform of Registered Systematic Review and Meta-analysis Protocols (INPLASY-2023–11-0013). A comprehensive search of MEDLINE, PSYCINFO, EMBASE, CINHALPlus, ScienceDirect, Scopus, and Web of Science identified peer-reviewed studies published in English on adults aged 16 and above with an ABI diagnosis. Studies were included if they used a validated depression measure, had at least three assessment points, and applied group-based trajectory modelling. Exclusion criteria included studies focusing on neurodegenerative or neurodevelopmental disorders, or solely on treatments. The methodological quality was assessed using Joanna Briggs’ critical appraisal tool. The review synthesised data from ten studies involving 13,205 participants (average age 51.38 years, 55.86% male). Four depressive symptom trajectory groups were identified with varying prevalence: stable low (68%), persistent high (13%), increasing (20%), and decreasing (11%). Several key predictors including sex, age, injury severity, and education emerged as significant predictors of group membership in the persistent high , increasing , and decreasing depressive groups. However, variability in study methodologies and sample compositions posed challenges to direct comparison. Nonetheless, the review underscores the importance of long-term monitoring and the development of tailored interventions, as depression can manifest or intensify years post-injury. Understanding depressive symptom trajectories could help create personalised interventions, improving quality of life for those with depression after ABI.

Genomic-assisted selection to guide mate allocation and leverage hybrid vigor in Coffea canephora - Rodrigo Barros Rocha; Matheus Massariol Suela; Marcone Comério; Elaine M. Riva Souza; João Felipe Brites Senra; Maria Amélia G. Ferrão; Romário G. Ferrão; Aymbiré F. Almeida da Fonseca; Abraão Carlos Verdin Filho; Paulo Sérgio Volpi; Luis Felipe V. Ferrão (Tree Genetics & Genomes, 2025)

Soil carbon and nutrient stocks under intensified pasture and sugarcane expansion - Luiza Pecci Canisares; Eduardo Mariano; Adibe L. Abdalla-Filho; Lucas P. Canisares; Mauricio C. A. Leite; Maria G. S. Araújo; Rodrigo F. Almeida; Taciana F. Gomes; Érika S. P. B. Saldanha; Luiz A. Martinelli (Nutrient Cycling in Agroecosystems, 2025)

Late Quaternary population expansion in gray brocket deer [ Subulo gouazoubira (G. Fisher, 1814), Cervidae, Mammalia] in Brazil - Alex Hubbe; Mark Hubbe; Elver Luiz Mayer; Eliane Nunes Chim; Paulo Miguel Haddad‐Martim; Augusto S. Auler; Luís B. Piló; William J. Pestle; Alba Rey‐Iglesia; Isac dos Santos Antônio Machado; Paulo C. F. Giannini; Eluzai Dinai Pinto Sandoval; et al. (Journal of Quaternary Science, 2025)
There is little information about the changes in the abundance of mammalian species in South America during the late Quaternary, which is a key parameter to understanding past ecological and evolutionary dynamics. Here, we describe a conspicuous increase in the abundance of the gray brocket deer ( Subulo gouazoubira G. Fisher, 1814; Mammalia) during the late Quaternary in Brazil based on paleontological evidence. We studied the material retrieved from pitfall deposits in Cuvieri Cave (Brazil) representing three time intervals (Late Pleistocene, Pleistocene/Holocene transition, and Holocene). The deposits in this cave were previously characterized in terms of facies composition, chronology, and overall taxa and taphonomy. We combined previous data with taxonomic identification at the species level for deer (morphological and ancient DNA analyses), quantification of the number of individuals for large mammals (>10 kg), taphonomic analyses, and stratigraphic distribution of specimens. Our results show that while in the Late Pleistocene gray brocket deer corresponded to up to 18% of 38 individuals, in the Holocene they represented at least 82% of 78 individuals. We interpret this change in frequency as a considerable increase in abundance in the surroundings of the cave, after excluding major taphonomical biases. The causes for this phenomenon are uncertain but could have involved a surplus of food availability and predation release due to the late Quaternary extinction event.

Stable isotopic differences ( δ 13 C and δ 15 N ) between muscle and fin ray tissues from juvenile Atlantic goliath grouper Epinephelus itajara (Lichtenstein, 1822) using non‐lethal sampling - Ester F. Barbosa; Rodrigo F. Bastos; Lorena L. Almeida; Rafael L. Oliveira; Sabrina R. Vollrath; Alexandre M. Garcia; Mauricio Hostim‐Silva; Mario V. Condini (Journal of Fish Biology, 2025)
The Atlantic goliath grouper ( Epinephelus itajara ) is the largest species of grouper in the Atlantic Ocean and is classified as critically endangered in Brazil. This study compared the isotopic ratios of carbon (δ 13 C) and nitrogen (δ 15 N) between the muscle tissue and dorsal‐fin rays of 37 juveniles to assess fin rays as a non‐lethal alternative to muscle tissue sampling. The δ 13 C values in rays were significantly higher than those found in muscle, whereas the δ 15 N values did not differ significantly between tissues. Both stable isotopes showed high Spearman correlation coefficients (>0.80) between tissues. Thus, the study can enhance future research and broaden the application of stable isotope techniques in a non‐lethal manner.

Assessment of bacteriospermia using flow cytometry - Nicolas F. Koller; Carolina L.A. Da Silva; Raúl G. Urdiales; Rodrigo M. Godinho (Animal Reproduction Science, 2025)

Mitonuclear genetics reveals a novel perspective on the stock structure and fishery management of skipjack tuna (Katsuwonus pelamis) in the Atlantic Ocean - Maria Clara G. Queiroz-Brito; Fernando F. Mendonça; Joana I. Robalo; Freddy Arocha; N’Guessan Constance Diaha; Monin Justin Amandé; Fambaye Ngom Sow; Davy Angueko; Paulo Travassos; Rodrigo A. Torres (Reviews in Fish Biology and Fisheries, 2025)

Optimizing fecal output estimation in lactating cows: Effects of marker selection, diet, and methodological factors - Filipe Zanferari; Thiago Henrique A. Vendramini; Carlos E.C. Consentini; Mariana F. Rentas; Rodrigo Gardinal; Gustavo D. Calomeni; Luciana N. Rennó; Caio S. Takiya; Alanne T. Nunes; Francisco P. Rennó (Animal Feed Science and Technology, 2025)

Bird–window collisions: A comprehensive dataset for the Neotropical region - Augusto João Piratelli; Bianca Costa Ribeiro; Wesley Dáttilo; Luis‐Bernardo Vázquez; Anelisa Ferreira de Almeida Magalhães; Edna Maria Gomes Cavalcante; Eric Silva; Giovanna Viana Cruz; Gisele Regina Ruy; Juliana Laurito Summa; Júlia Milan; Leila Pedrosa; et al. (Ecology, 2025)
Our primary objective was to compile a comprehensive dataset on bird–window collisions throughout the Neotropical region, including both published and unpublished sources. On May 12, 2020, we extensively disseminated invitations to provide data via email and social media platforms. By providing a template worksheet, we required standardized information from collaborators to complete and register their data. To better understand how these data were acquired (e.g., incidental observations and systematic procedures), we sent out a survey to all collaborators. We established rigorous validation criteria for data inclusion and conducted thorough curation procedures to ensure accuracy. After the filtering process, we compiled a total of 4103 bird–window collision reports. These came from 11 Neotropical countries, dating from 1946 to 2020, and revealing distinct regional patterns and potential seasonal patterns. The five most frequent orders were Passeriformes (2451), Columbiformes (520), Apodiformes (377), Psittaciformes (202), and Piciformes (186). Data on bird–window collisions were collected through a local specific systematic protocol (1419), by chance (1252), by government agencies (742), and by other approaches (632), while a few reports were collected by unknown procedures (58). The volume of records across months in our dataset suggests that there may be temporal patterns, with peaks: the first one in March–April and the second one in October–November, which seem to align with the major migration and reproduction seasons. This dataset represents the first comprehensive effort in the Neotropical region focused on bird–window collision data, providing valuable insights for further scientific advancements and conservation policies. The data are free from copyright or proprietary restrictions. Please cite this data paper when using the data in publications or scientific presentations.

Forest citizens and people‐centered conservation in the Brazilian Amazon - Luke Parry; Thiago F. Morello; James A. Fraser; Natalia Guerrero; Gabriela S. Lotta; Rodrigo C. Martins; Peter Newton; Jessica C. Pires Cardoso; Andreza A. Souza Santos; Mauricio Torres (Conservation Biology, 2025)
Demands for territorial recognition are foundational to the claiming of rights by forest‐proximate people who attempt to conserve their forests. The rights of these often‐marginalized populations have been largely overlooked by conservationists, yet they are central to achieving people‐centered conservation. We further developed the concept of forest citizenship as a normative framework and analytical tool based on Brazilian social environmentalism ( socioambientalismo ), florestania (a former political project in Acre state), Latin American scholarship on ecological citizenship, and Eurocentric political philosophy. Decades of struggle for territorial recognition and social inclusion have solidified the right to have rights for Amazonia's forest citizens. Hence, forest citizens are people who have become so through the sociopolitical dynamics of their rights claims. Forest citizenship is built on community mobilization to create legally recognized territories with participatory governance but becomes tangible only if individuals and communities can successfully claim other rights from institutions through everyday practices of citizenship. We also assessed the current number and distribution of forest citizens across Brazilian Amazonia based on gridded population data and spatial analyses to calculate the resident population in four territorial categories that meet these democratic preconditions: Indigenous lands, extractive reserves, sustainable development reserves, ecological settlement projects, and Afro‐descendent Quilombola territories. The territories covered 31% of the Legal Amazon, were home to 1.05 million forest citizens, and had diverse primary policy objectives but shared goals of empowering communities and conserving forests. To be emancipatory, forest citizenship must be bottom‐up, socially inclusive, and improve people's lives. We suggest that conservationists pay greater attention to power relations and decision‐making structures related to forest territories. Territory‐based forest citizenship may be relevant for other countries where environmentalism has intersected with struggles for land rights and democracy.

Linking the grain weight damage by Fusarium graminearum and the gluten composition of bread wheat under different sulfur fertilization - Agustín F. Arata; Mauro Martínez; Deborah P. Rondanini; Laura Lázaro; Adriana C. Arrigoni; Rodrigo I. Galizio; Florencia Arroyo; María Inés Dinolfo (Journal of Cereal Science, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Forward energy grade line analysis for tsunami inundation mapping - María F. Estrada; Rodrigo Cienfuegos; Alejandro Urrutia; Patricio A. Catalán; Patricio Winckler (Coastal Engineering, 2025)

The Combined and Isolated Impacts of El Niño and Positive Indian Ocean Dipole Events on South American Precipitation During Austral Winter and Spring Depending on the Atlantic Multidecadal Oscillation Phases - Itamara P. Souza; Rita V. Andreoli; Mary T. Kayano; Jean A. C. Costa; Leonardo Mamani; Rodrigo A. F. Souza; Wilmar L. Cerón (International Journal of Climatology, 2025)
The isolated/combined impacts of the positive Indian Ocean Dipole (pIOD) and El Niño (EN) events on precipitation in South America (SA) were investigated during austral winter and spring for the 1901–2012 period, considering both Atlantic Multidecadal Oscillation (AMO) phases. Under the warm phase (WAMO), EN events are well characterised in winter and, in spring, are accompanied by anomalous warming of the Tropical North Atlantic (TNA); thus, variations in the Walker circulation and the northward shifted Intertropical Convergence Zone (ITCZ) reduce precipitation over northern SA. In the cold AMO phase (CAMO), EN events are weak in winter. At the same time, an intense cooling in the equatorial North Atlantic, favoured by the CAMO, enhances moisture transport from the Amazon to central and southeastern Brazil, increasing precipitation in the South Atlantic Convergence Zone region. As EN develops in spring, the anticyclone off the east coast of SA associated with the Pacific‐South American (PSA) pattern decreases (increases) precipitation in central (southeastern) SA. The pIOD events predominantly occur during WAMO phase, when warming in the TNA is favoured by AMO. In winter, the moisture transport to northern SA is weakened, and the ITCZ remains northward shifted, inhibiting the precipitation over northeastern Brazil and southeastern Amazon. In spring, pIOD intensified ascending motions in equatorial Atlantic, increasing precipitation over northeastern Brazil. A wave train from the Indian Ocean strengthens the South Atlantic subtropical high, suppressing precipitation in central and eastern SA. EN‐pIOD events are well established in both AMO phases, though the sea surface temperature anomalies in the TNA depend on the AMO. During WAMO, reduced precipitation in western Amazon and northeastern SA is influenced by the Walker circulation, while in CAMO, TNA cooling enhances moisture transport from the Amazon into southeastern SA, where the PSA pattern and wave train from the Indian Ocean increase precipitation.

Long‐haul flights and migratory routes of a nectar‐feeding bat - Theresa M. Laverty; Debbie C. Buecher; David C. Dalton; Mallory L. Davies; Fernando Gual‐Suárez; Paul A. Heady; Rodrigo A. Medellín; Mayra C. Ordóñez‐García; Samara Pérez‐Harp; A. Nayelli Rivera‐Villanueva; Brandi D. Stevenson; Kathryn E. Stoner; et al. (Ecology, 2025)

Feasibility of using silica (Na2SiO3 and SiO2NPs) to mitigate mercury in transgenic soybeans grown in contaminated soils and respective effects on nutrient homeostasis - Vinnícius H. C. da Silva; Rodrigo F. de Lima; Juliana L. S. Mayer; Marco Aurélio Zezzi Arruda (Environmental Science and Pollution Research, 2025)

ReBreed21-ET: Evaluation of a rapid resynchronization program that allows timed embryo transfer every 21 days - João Paulo N. Andrade; Victor E. Gomez-León; Guilherme Madureira; Luma C. Sartori; Gustavo F. Grillo; Rafael R. Domingues; Meliton Fosado; Rodrigo V. Sala; Milo C. Wiltbank (Theriogenology, 2025)

Extreme droughts in the Amazon Basin during cyclic ENSO events coupled with Indian Ocean Dipole modes and Tropical North Atlantic warming - Leonardo Mamani; Rita V. Andreoli; Itamara Parente de Souza; Wallace Cevalho; Djanir Sales; Mary Toshie Kayano; Rodrigo Augusto F. de Souza; Jorge Molina-Carpio; Wilmar L. Ceron; Tabata Macedo (Science of The Total Environment, 2025)

Development and validation of a rapid method for the determination of oil and oleic acid content in peanut (Arachis hypogaea L.) using time domain nuclear magnetic resonance - Lucas J. Carvalho; Jacqueline Elis de Souza; Evelyn de F. Guimarães; Luiz Alberto Colnago; Daniel Martelozo Consalter; Silvia Paulo de Azevedo; Cristina Torres Consalter; Karla Borba; Rodrigo Garcia; Davi dos Santos Miquelin; Bruno Felipe Caravieri; Jair Heuert; et al. (Food Research International, 2025)

Integration of spectroscopic techniques and machine learning for optimizing Phaeodactylum tricornutum cell and fucoxanthin productivity - Pedro Reynolds-Brandão; Francisco Quintas-Nunes; Constança D.F. Bertrand; Rodrigo M. Martins; Maria T.B. Crespo; Cláudia F. Galinha; Francisco X. Nascimento (Bioresource Technology, 2025)

Cannabidiol-Induced Autophagy Ameliorates Tau Protein Clearance - Talita A. M. Vrechi; Gabriel C. Guarache; Rafaela Brito Oliveira; Erika da Cruz Guedes; Adolfo G. Erustes; Anderson H. F. F. Leão; Vanessa C. Abílio; Antonio W. Zuardi; Jaime Eduardo C. Hallak; José Alexandre Crippa; Claudia Bincoletto; Rodrigo P. Ureshino; et al. (Neurotoxicity Research, 2025)
Tau is a neuronal protein that confers stability to microtubules; however, its hyperphosphorylation and accumulation can lead to an impairment of protein degradation pathways, such as autophagy. Autophagy is a lysosomal catabolic process responsible for degrading cytosolic components, being essential for cellular homeostasis and survival. In this context, autophagy modulation has been postulated as a possible therapeutic target for the treatment of neurodegenerative diseases. Studies point to the modulatory and neuroprotective role of the cannabinoid system in neurodegenerative models and here it was investigated the effects of cannabidiol (CBD) on autophagy in a human neuroblastoma strain (SH-SY5Y) that overexpresses the EGFP-Tau WT (Wild Type) protein in an inducible Tet-On system way. The results demonstrated that CBD (100 nM and 10 µM) decreased the expression of AT8 and total tau proteins, activating autophagy, evidenced by increased expression of light chain 3-II (LC3-II) protein and formation of autophagosomes. Furthermore, the cannabinoid compounds CBD, ACEA (CB1 agonist) and GW-405,833 (CB2 agonist) decreased the fluorescence intensity of EGFP-Tau WT; and when chloroquine, an autophagic blocker, was used, there was a reversal in the fluorescence intensity of EGFP-Tau WT with CBD (1 and 10 µM) and GW-405,833 (2 µM), demonstrating the possible participation of autophagy in these groups. Thus, it was possible to conclude that CBD induced autophagy in EGFP-Tau WT cells which increased tau degradation, showing its possible neuroprotective role. Hence, this study may contribute to a better understanding of how cannabinoids can modulate autophagy and present a potential therapeutic target in a neurodegeneration model. Graphical Abstract

Treatment of effluent from municipal wastewater treatment plants using electrochemically produced Caro's acid - M. Pilar Castro; Ismael F. Mena; Cristina Sáez; Manuel A. Rodrigo (Journal of Environmental Management, 2025)

Identifying changes in the drivers of ecosystem services: Socioeconomic changes underlie reduced provision of pollination service - Pedro Joaquim Bergamo; Kátia F. Rito; Kayna Agostini; Felipe Deodato da Silva e Silva; Márcia M. Maués; André R. Rech; Lucas A. Garibaldi; Eimear Nic Lughadha; Antonio M. Saraiva; Rodrigo Y. Tsukahara; Blandina F. Viana; Grasiela Casas; et al. (Journal of Environmental Management, 2025)

Connectivity at risk: a critical scenario for the endangered Baird’s tapir and the vulnerable white-lipped peccary in the Maya Forest - Fredy A. Falconi-Briones; René Bolom-Huet; Eduardo J. Naranjo; Rafael Reyna-Hurtado; Paula L. Enríquez-Rocha; José F. Moreira-Ramírez; Manolo J. García; Rodrigo A. Medellín (Biodiversity and Conservation, 2025)

Site‐Specific Nutrient Data Reveal the Importance of Soils in Driving the Mycorrhizal Make‐Up of Woody Vegetation Worldwide - Xiaobin Hua; Christopher H. Lusk; Ian A. Dickie; Stephen Adu‐Bredu; Kathryn J. Allen; Viviana Araus; Laurent Augusto; Pavel Barsukov; David Bauman; Félix Brédoire; David F. R. P. Burslem; James W. Dalling; et al. (Global Ecology and Biogeography, 2025)
Aim Arbuscular mycorrhizas (AM) and ectomycorrhizas (ECM) have different impacts on nutrient cycling, carbon storage, community dynamics and enhancement of photosynthesis by rising CO 2 . Recent global analyses have concluded that patterns of AM/ECM dominance in forests worldwide are shaped by climate, with soil nutrients contributing negligible additional explanatory power. However, their reliance on nutrient data from GIS surfaces masks important local influences of parent material, topography and soil age on soil nutrient status. We asked if use of site‐specific nutrient data reveals a more important role for nutrients. Time Period Present day. Location Global dataset comprising 703 sites, encompassing forests, savanna/woodlands, shrublands and deserts on all continents except Antarctica. Taxa Studied Arborescent plants, including angiosperms, gymnosperms and tree ferns. Methods Generalised Additive Models for Location, Scale and Shape (GAMLSS) to determine the effects of climate variables, soil nitrogen and soil phosphorus on the proportional representation of ECM and of non‐mycorrhizal species (NM) in woody vegetation. Results GAMLSS showed a strong negative relationship of ECM representation with mean annual temperature (MAT), and a strong negative relationship with soil total nitrogen. NM representation was highest on dry sites and phosphorus‐poor sites. Reanalysis showed that GIS‐derived soil nutrient data had less explanatory power than site‐specific nutrient data, and resulted in poorer model fits. Conclusions Our results support the long‐held belief that soil nutrients as well as climate influence the relative fitness of different mycorrhizal syndromes worldwide, and demonstrate the value of using site‐specific nutrient data. Soil nutrients should be considered when predicting the impact of climate change on the mycorrhizal composition of vegetation and resulting shifts in ecosystem processes.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

A Natural Disaster Exacerbates and Redistributes Disease Risk Among Free‐Ranging Macaques by Altering Social Structure - Alba Motes‐Rodrigo; Gregory F. Albery; Josue E. Negron‐Del Valle; Daniel Philips; Michael L. Platt; Lauren J. N. Brent; Camille Testard (Ecology Letters, 2025)
Climate change is intensifying extreme weather events, with severe implications for ecosystem dynamics. A key behavioural mechanism whereby animals may cope with such events is by altering their social structure, which in turn could influence epidemic risk. However, how and to what extent natural disasters affect disease risk via changes in sociality remains unexplored in animal populations. By simulating disease spread in free‐living rhesus macaques ( Macaca mulatta ) before and after a hurricane, we demonstrate doubled pathogen transmission rates up to 5 years following the disaster, equivalent to an increase in pathogen infectivity from 10% to 20%. Moreover, the hurricane redistributed the risk of infection across the population by exacerbating sex‐related differences. Overall, we demonstrate that natural disasters can amplify and redistribute epidemic risk in animals via changes in sociality. These observations provide unexpected further mechanisms by which extreme weather events can threaten wildlife health, population viability and spillover to humans.

Contrasting Rainfall Anomaly Patterns Over South America Related to Central and Eastern Atlantic Niño Modes - Mary T. Kayano; Rita V. Andreoli; Wilmar L. Cerón; Leonardo Mamani; Itamara Parente de Souza; Wallace Cevalho; Rodrigo A. F. Souza; Djanir Sales de Moraes (International Journal of Climatology, 2024)
The present study examines the effects of the central Atlantic Niño (CAN) and eastern Atlantic Niño (EAN) events on the seasonal precipitation in South America (SA) during the 1951–2020 period. For the CAN during the summer and autumn, an interhemispheric sea surface temperature (SST) dipole mode induces an anomalous thermally direct circulation in the 10° N–10° S band and is the main factor causing precipitation anomaly patterns with a dipole structure between northern (negative) and northeastern (positive) SA. For winter and spring, the SST pattern featuring a South Atlantic dipole induces meridional and zonal anomalous circulations, which are the mechanisms causing positive precipitation anomalies in tropical SA to the north of 20° S. In contrast, for the EAN, the precipitation anomaly patterns show large areas with anomalous dryness, particularly during summer, autumn, and spring. For summer and autumn, the east–west SST anomaly gradient in the equatorial Atlantic and the associated sea level pressure (SLP) anomalies induce equatorial westerlies and a regional Walker cell with descending motions in most tropical SA, where large areas with anomalous dryness are noted. During spring, a northward SST gradient in the tropical Atlantic induces a meridional cell with descending motions in the 0°–10° S band; meanwhile, the westward SST gradient in the equatorial Atlantic and tropical South Atlantic induces a zonal circulation with descending motions over northeastern and eastern Brazil. These descending motions extend the anomalous dryness over a large area. For the EAN events, the east–west SST gradient and the associated east–west circulation in the South American/Atlantic region are crucial elements to modulate precipitation variability in SA. Therefore, the CAN and EAN events induce distinct precipitation anomaly patterns in SA due to distinct associated regional circulation patterns. The results presented here have not been discussed before and might have relevant implications for climate monitoring and modelling studies.

Trophic ecology and habitat use of an overexploited commercial snapper (Lutjanus jocu) in a tropical nursery estuary elucidated by stable isotopes - Patrick Derviche; Rodrigo F. Bastos; Mario V. Condini; Ester F. Barbosa; Rafael L. Oliveira; Lorena L. Almeida; Sabrina R. Vollrath; Marcelo Soeth; Alexandre M. Garcia; Maurício Hostim–Silva (Regional Studies in Marine Science, 2024)

Influence of carbon type in microbial communities formation when setting up BAC for secondary effluents treatment - Luan A. Camara; Rodrigo P. Cavalcante; Jacqueline A. Malvestiti; Maria J. dos Santos; Karina D. Pereira; Augusto D. Luchessi; Valdemar L. Tornisielo; Renato F. Dantas (Journal of Water Process Engineering, 2024)

Realized genetic gain with reciprocal recurrent selection in a Eucalyptus breeding program - Saulo F. S. Chaves; Luiz A. S. Dias; Rodrigo S. Alves; Filipe M. Ferreira; Maurício S. Araújo; Marcos D. V. Resende; Elizabete K. Takahashi; João E. Souza; Fernando P. Leite; Samuel B. Fernandes; Kaio Olimpio G. Dias (Tree Genetics & Genomes, 2024)

RecQ helicase expression in patients with telomeropathies - João Paulo L. Silva; Flávia S. Donaires; Fernanda Gutierrez-Rodrigues; Davi J. Martins; Vinicius S. Carvalho; Barbara A. Santana; Renato L. G. Cunha; Sachiko Kajigaya; Carlos F. M. Menck; Neal S. Young; Eigil Kjeldsen; Rodrigo T. Calado (Molecular Biology Reports, 2024)

Enteroaggregative Escherichia coli (EAEC) isolates obtained from non-diarrheic children carry virulence factor-encoding genes from Extraintestinal Pathogenic E. Coli (ExPEC) - Bruna M. Luiz; Maria C. Cergole-Novella; Stéfani T. A. Dantas; Daiany R. P. de Lira; Guilherme F. R. de Souza; Iranildo do A. Fernandes; Henrique Orsi; Guilherme Solveira; Vera L. M. Rall; Luís F. dos Santos; Rodrigo T. Hernandes (Brazilian Journal of Microbiology, 2024)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Circular economy in Latin America and the Caribbean: Drivers, opportunities, barriers and strategies - Alejandro Gallego-Schmid; Camila López-Eccher; Edmundo Muñoz; Rodrigo Salvador; Natalia A. Cano-Londoño; Murillo Vetroni Barros; Daniel Choconta Bernal; Joan Manuel F. Mendoza; Ana Nadal; Ana Belén Guerrero (Sustainable Production and Consumption, 2024)

Integration of a 3D-printed electrochemical reactor with a tubular membrane photoreactor to promote sulfate-based advanced oxidation processes - Agustina R. de Olivera; Carla S. Santos; Ismael F. Mena; Miguel A. Montiel; Rosa Montes; José B. Quintana; Rosario Rodil; Ana I. Gomes; Francisca C. Moreira; Jan Gäbler; Lothar Schäfer; C. Sáez; et al. (Chemical Engineering Journal, 2024)

Editorial special issue: Celebrating 25 years of AmeriFlux - Trevor F. Keenan; Gil Bohrer; Russell L. Scott; Rodrigo Vargas (Agricultural and Forest Meteorology, 2024)

Tuff deposits as preservational context for a Miocene continental mammal assemblage from Patagonia, Argentina - Rodrigo L. Tomassini; Claudia I. Montalvo; José I. Cuitiño; María Susana Bargo; Sergio F. Vizcaíno (Geobios, 2024)

Remote sensing imagery to predict soybean yield: a case study of vegetation indices contribution - Lucas R. Amaral; Henrique Oldoni; Gustavo M. M. Baptista; Gustavo H. S. Ferreira; Rodrigo G. Freitas; Cenneya L. Martins; Isabella A. Cunha; Adão F. Santos (Precision Agriculture, 2024)

The effects of keystone resources and landscape of fear in modulating the spatiotemporal use of paca (Cuniculus paca) in Brazilian Atlantic Forest - Mateus Melo-Dias; Rayssa F. Pedroso; Clarissa Rosa; Rodrigo L. Massara; Letícia G. Ribeiro; Marcelo Passamani (Mammalian Biology, 2024)

Correction to: A taxonomic proposal for cedratviruses, orpheovirus, and pithoviruses - Victória F. Queiroz; Rodrigo A. L. Rodrigues; Jônatas Santos Abrahão (Archives of Virology, 2024)

Characterization of a novel acidic phospholipase A2 isolated from the venom of Bothrops mattogrossensis: from purification to structural modelling - Micaela De M.C. Eulalio; Anderson M. De Lima; Rodrigo S. Caldeira Brant; Aleff F. Francisco; Mauro V. Paloschi; Hallison M. Santana; Sulamita Da S. Setubal; Carolina P. Da Silva; Paula H. Santa Rita; Anderson M. Kayano; Andreimar M. Soares; Daniela P. Marchi Salvador; et al. (Toxicon, 2024)

Subacute tributyltin exposure alters the development and morphology of mammary glands in association with CYP19A1 expression in female rats - Natalia P. Silva; Charles S. da Costa; Kayke L. Barbosa; Cidália de F. Januario; Leticia N. Gama-de-Souza; Cinthia Breves; Rodrigo S. Fortunato; Leandro Miranda-Alves; Miriane de Oliveira; Celia R. Nogueira; Jones B. Graceli (Reproductive Toxicology, 2024)

Towards scaling up of the electrochemical production of Caro’s acid: Electrode size and/or stacking? - M. Pilar Castro; Miguel A. Montiel; Ismael F. Mena; J. Gäbler; D. Barton; Cristina Sáez; Manuel A. Rodrigo (Chemical Engineering Journal, 2024)

Large Scale Voxel-Based FEM Formulation for NMR Relaxation in Porous Media - Luiz F. Bez; Ricardo Leiderman; André Souza; Rodrigo B. de V. Azeredo; André M. B. Pereira (Transport in Porous Media, 2024)

Cattleya attenboroughiana (Orchidaceae: Laeliinae): a new species from the Diamantina Plateau, Minas Gerais, Brazil - Euler L. F. Menezes; Samuel C. O. Giordani; Rodrigo A. Pinheiro; Paulo M. Gonella (Kew Bulletin, 2024)

Preliminary profile of the gut microbiota from amerindians in the Brazilian amazon experiencing a process of transition to urbanization - Rodrigo M. Alencar; José G. Martínez; Valéria N. Machado; Juan F. Alzate; Cinthya P. Ortiz-Ojeda; Rosiane R. Matias; Denise C. Benzaquem; Maria C.F. Santos; Enedina N. Assunção; Evelyn C. Lira; Spartaco Astolfi-Filho; Tomas Hrbek; et al. (Brazilian Journal of Microbiology, 2024)
The Yanomami are one of the oldest indigenous tribes in the Amazon and are direct descendants of the first people to colonize South America 12,000 years ago. They are located on the border between Venezuela and Brazil, with the Venezuelan side remaining uncontacted. While they maintain a hunter-gatherer society, they are currently experiencing contact with urbanized populations in Brazil. The human gut microbiota of traditional communities has become the subject of recent studies due to the Westernization of their diet and the introduction of antibiotics and other chemicals, which have affected microbial diversity in indigenous populations, thereby threatening their existence. In this study, we preliminarily characterized the diversity of the gut microbiota of the Yanomami, a hunter-gatherer society from the Amazon, experiencing contact with urbanized populations. Similarly, we compared their diversity with the population in Manaus, Amazonas. A metabarcoding approach of the 16 S rRNA gene was carried out on fecal samples. Differences were found between the two populations, particularly regarding the abundance of genera (e.g., Prevotella and Bacteroides ) and the higher values of the phyla Bacteroidetes over Firmicutes, which were significant only in the Yanomami. Some bacteria were found exclusively in the Yanomami ( Treponema and Succinivibrio ). However, diversity was statistically equal between them. In conclusion, the composition of the Yanomami gut microbiota still maintains the profile characteristic of a community with a traditional lifestyle. However, our results suggest an underlying Westernization process of the Yanomami microbiota when compared with that of Manaus, which must be carefully monitored by authorities, as the loss of diversity can be a sign of growing danger to the health of the Yanomami.

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Remediation of soils contaminated with methomyl using electrochemically produced gaseous oxidants - Leticia Mirella da Silva; Ismael F. Mena; Cristina Sáez; Artur J. Motheo; Manuel A. Rodrigo (Chemosphere, 2024)

Toward new biomarkers of cold tolerance: microRNAs regulating cold adaptation in fish are differentially expressed in cold-tolerant and cold-sensitive Nile tilapia (Oreochromis niloticus) - Eduardo B. Blödorn; Amanda W.S. Martins; Eduardo N. Dellagostin; Leandro S. Nunes; Rita C.S. da Conceição; Antônio D. Pagano; Natiéli M. Gonçalves; Luana F.V. dos Reis; Mariana C. Nascimento; Dionet K.B. Quispe; Charles N. Fróes; Rafael A. Tavares; et al. (Aquaculture, 2024)

Catalytic ozonation using spent battery-based (SB) catalysts for dyes, micropollutant removal and disinfection - Jacqueline A. Malvestiti; Maina Ruth C. Silva; Iure B. de Sousa; Rodrigo P. Cavalcante; Amanda Gondim C. Quirino; Guenther C.C. Viana; Elisângela Maria R. Rocha; Renato F. Dantas (Journal of Water Process Engineering, 2024)

Enriched oil-in-water emulsions as bioactive agents for locust bean gum films: A comparative investigation - Rodrigo F. Gouvêa; Mariana G.C. Azevedo; Carlos A. Conte-Junior; Cristina T. Andrade (Food Bioscience, 2024)

Conservation opportunities for rare and endemic tropical mistletoes - Rodrigo F. Fadini; Claudenir S. Caires; Greta A. Dettke; Marcelo O.T. Menezes; Francisco E. Fontúrbel (Flora, 2024)

Aquatic bird predation by antarctic and subantarctic pinnipeds vagrants off argentina - Antonella D. Padula; M. Alejandra Romero; Rodrigo Machado; Alan F. Rosenthal; Mariela Dassis; Diego H. Rodríguez; Caio J. Carlos; Juan Pablo Seco Pon; Pablo Denuncio (Polar Biology, 2024)

Timed-artificial insemination protocols for Bos indicus beef heifers: Evaluation of protocol length and variations in prostaglandin F2α treatments - Rodrigo L.O.R. Alves; Lucas O.e Silva; Mateus A.da Silva; Carlos E.C. Consentini; José R.S. Gonçalves; Leonardo de F. e Melo; Marcelo B. Rodrigues; Roberto Sartori (Theriogenology, 2024)

Top-down characterization of resource use in LCA: from problem definition of resource use to operational characterization factors for resource inaccessibility of elements in a short-term time perspective - Lauran van Oers; Jeroen B. Guinée; Reinout Heijungs; Rita Schulze; Rodrigo A. F. Alvarenga; Jo Dewulf; Johannes Drielsma (The International Journal of Life Cycle Assessment, 2024)
Purpose When resources are extracted and used by society, they are not necessarily lost for future generations. Therefore, recent publications on impact assessment of abiotic resource use in life cycle assessment focus on a decreased accessibility of resources due to dissipation, rather than depletion. In a previous study, dissipation was defined as a function of the global change in accessible stock due to human actions, and the global amount of the accessible stock, assuming a very long-term time perspective (more than 500 years). In this paper, a short-term time perspective (25 years) is adopted. Methods The same generic characterization model is used, but different choices are outlined to derive characterization factors for a short-term perspective (25 years). To illustrate how the short term might be approached, a preliminary set of characterization factors is developed, based on assumptions and estimates. Results The problem of resource use is defined as follows: the decrease of accessibility on a global level of primary and/or secondary elements over the short term due to the net result of compromising actions (i.e., emissions, dissipation in the technosphere, occupation in use, and exploration for new stocks). Characterization factors are derived based on assumptions, like the following: the accessible stock is based on present estimates of accessible stocks in the environment and the technosphere; estimates of accessible stocks in the technosphere are based on past extractions and generic recycling rates; all flows that are presently not recycled are assumed to be inaccessible. Finally, weighting between elements and the functions they have for the present society is based on the added value of the economic sector that is affected due to the decreased accessibility. Discussion and conclusion A preliminary set of characterization factors is proposed for 55 elements. They assess the impact of the present use of resources on the decreased accessibility in the short term due to emissions and dissipation in the technosphere. However, calculation of impact category scores is still hampered by a lack of appropriate data for dissipative flows in life cycle inventory databases. The presented calculations are based on several simplifications and proxies. A more detailed distinction of dissipative flows and estimates of stocks in the technosphere may be possible based on (dynamic) SFA modelling of elements in different applications. To derive a more mature set of characterization factors, it is recommended to use the presented model as a basis and further elaborate or replace the proxies.

Influence of trophic overlaps and trophic niche amplitude on microplastic intake of fish species in shallow areas of a neotropical coastal lagoon - David V. Dantas; Cristian I.R. Ribeiro; Leticia S.C. Ito; Ana P.T. Pezzin; Victória F. Silveira; Ana L.P. Cardozo; Eduardo Gentil; Isabel B. Monteiro; Sofia A. Ribeiro; Luciano Lorenzi; Rodrigo Machado (Science of The Total Environment, 2024)

The role of compaction in the diagenetic evolution of Pre-Salt Aptian deposits of Santos Basin, Brazil - Rodrigo B. Rossoni; Carla C. Porcher; Edinei Koester; Júlia S. Sobiesiak; Luis A.C. da Silva; André S. Mexias; Márcia E.B. Gomes; Camila W. Ramnani; Luiz F. De Ros (Sedimentary Geology, 2024)

Seeing further into the early steps of the endangered atlantic goliath grouper (Epinephelus itajara): Eye lenses high resolution isotopic profiles reveal ontogenetic trophic and habitat shifts - Rodrigo F. Bastos; Mario V. Condini; Ester F. Barbosa; Rafael L. Oliveira; Lorena L. Almeida; Alexandre M. Garcia; Maurício Hostim-Silva (Marine Environmental Research, 2024)

Optimizing PtSn Composition in Direct Sugarcane Extract Fuel Cells: A Sustainable Bioenergy Solution - Bruno D. Q. Villardi; Victoria A. Maia; Julio Nandenha; Priscilla J. Zambiazi; Rodrigo F. B. de Souza; Almir O. Neto (Sugar Tech, 2024)

A taxonomic proposal for cedratviruses, orpheoviruses, and pithoviruses - Victória F. Queiroz; Rodrigo A. L. Rodrigues; Jônatas Santos Abrahão (Archives of Virology, 2024)

Systematic review and meta-analysis of randomized controlled trials on the effects of exercise interventions on amyloid beta levels in humans - Isabela Mayer Pucci; Andreo F. Aguiar; Rodrigo M. Pucci; Juliano Casonatto; Sergio Marques Borghi (Experimental Brain Research, 2024)

GIS-FA: an approach to integrating thematic maps, factor-analytic, and envirotyping for cultivar targeting - Maurício S. Araújo; Saulo F. S. Chaves; Luiz A. S. Dias; Filipe M. Ferreira; Guilherme R. Pereira; André R. G. Bezerra; Rodrigo S. Alves; Alexandre B. Heinemann; Flávio Breseghello; Pedro C. S. Carneiro; Matheus D. Krause; Germano Costa-Neto; et al. (Theoretical and Applied Genetics, 2024)

Correction: Effects of Intra-REV Pore Distribution Modeling in the Flow of Non-Newtonian Fluids in Porous Media - Allan B. G. Motta; Roney L. Thompson; Mateus P. Schwalbert; Luiz F. L. R. Silva; Jovani L. Favero; Rodrigo A. C. Dias; Raphael J. Leitão (Transport in Porous Media, 2024)

Prioritized imputed sequence variants from multi-population GWAS improve prediction accuracy for sea lice count in Atlantic salmon (Salmo salar) - Baltasar F. Garcia; Pablo A. Cáceres; Rodrigo Marín-Nahuelpi; Paulina Lopez; Daniela Cichero; Jørgen Ødegård; Thomas Moen; José M. Yáñez (Aquaculture, 2024)

Uncertainty Regarding Species Delimitation, Geographic Distribution, and the Evolutionary History of South-Central Amazonian Titi Monkey Species (Plecturocebus, Pitheciidae) - Hazel Byrne; Rodrigo Costa-Araújo; Izeni P. Farias; Maria N. F. da Silva; Mariluce Messias; Tomas Hrbek; Jean P. Boubli (International Journal of Primatology, 2024)

The richness of Fusarium species in maize tassels and their relationship with Fusarium stalk rot - Agustín F. Arata; Mauro Martínez; Eliana Castañares; Rodrigo I. Galizio; Miriam D. Fernández; María I. Dinolfo (European Journal of Plant Pathology, 2024)

Spatial and temporal variation of three Eddy-Covariance flux footprints in a Tropical Dry Forest - Mohammed Abdaki; Arturo Sanchez-Azofeifa; Rodrigo Vargas; Ralf Ludwig; Hendrik F. Hamann (Agricultural and Forest Meteorology, 2024)

Distribution, Invasion History, and Ecology of Non-native Pine Bark Beetles (Coleoptera: Curculionidae: Scolytinae) in Southern South America - Victoria Lantschner; Demian F. Gomez; Gimena Vilardo; Leonel Stazione; Sergio Ramos; Edgar Eskiviski; Romina Fachinetti; Marcela Schiappacassi; Natalia Vallejos; Monica Germano; José Villacide; Mariano P. Grilli; et al. (Neotropical Entomology, 2024)

A reliable validated high-performance liquid chromatography-photodiode array detection method for quantification of terpenes in Copaifera pubiflora , Copaifera trapezifolia , and Copaifera langsdorffii oleoresins - Luiza J. Carneiro; Jairo K. Bastos; Rodrigo C. S. Veneziani; Mario F. C. Santos; Sérgio R. Ambrósio (Natural Product Research, 2024)

Assessment of hydrological, geological, and biological parameters of a river basin impacted by old Hg mining in NW Spain - Lucía Escudero; Alfredo F. Ojanguren; Rodrigo Álvarez; Carmen García; Jose Pañeda; Fernando Alberquilla; Almudena Ordóñez (Environmental Science and Pollution Research, 2024)
Mercury (Hg) is a toxic metal that can cause adverse effects for the health of ecosystems. The Caudal River is one of the main rivers in the Asturias region (NW Spain), whose basin is highly anthropized, hosting several Hg mines, closed in the last century. Arsenic (As) is also found in the mineral paragenesis of the Hg deposits, posing a greater environmental risk. In the mining sites, remaining old facilities and tailings continue to release these elements into the environment. In this work, samples of fluvial sediments and water were taken, both in areas affected by anthropic activity and in pristine areas, in order to establish the background levels for the critical elements. The mineralogical study of the sediments, combined with EDS microanalysis, is useful to identify mineralogical traps such as Fe oxides or clays to retain the As. The As content in all sampled sediments is above the threshold effect levels (TEL), the possible effect range within which adverse effects occasionally occur, according to the Canadian Sediment Quality Guidelines for the Protection of Aquatic Life. This fact is related to a naturally high geochemical background in the basin, due to the existing mineral deposits. The PEL threshold (the probable effect range within which adverse effects frequently occur) is exceeded by more than an order of magnitude in the sediments downstream of the Hg mines. In these points, the As content in the water, exceeding 700 μg L −1 As, is also above the quality standard established in Spanish legislation. As a result, the Caudal River tributaries in the lower part of the basin do not reach a good ecological state, according to the Hydrological Planning Office, and in some cases their state is deficient, showing low richness and high dominance of macroinvertebrates. Although the concentrations decrease with distance from the source, these findings justify the low ecological quality of the affected watercourses.

GWAS meta-analysis of resistance against Piscirickettsia salmonis in Atlantic salmon - Rodrigo Marín-Nahuelpi; Baltasar F. Garcia; Agustin Piña-Elgueda; Jousepth Gallardo-Hidalgo; Paulina López; Daniela Cichero; Thomas Moen; Jørgen Ødegård; José M. Yáñez (Aquaculture, 2024)

Incomplete sanitation in the Metropolitan Region of São Paulo results in detection of SARS-CoV-2 in headwater streams - Ricardo H. Taniwaki; Rodrigo F. Bueno; Giulia B.S. Bispo; Matheus R. Augusto; Guilherme S. Souza; Bruna Chyoshi; Roseli F. Benassi; Nelson Gouveia; Lívia M.B. Camilo; Adriana F.A. Duran; Luís C. Schiesari (Science of The Total Environment, 2024)

Modelling ozone disinfection of secondary effluents in presence of scavengers and metal catalyst: Synergistic effect and regrowth - Jacqueline A. Malvestiti; Rodrigo P. Cavalcante; Pedro F.M. Bacellar; Valdemar L. Tornisielo; Renato F. Dantas (Journal of Water Process Engineering, 2024)

From bulk banana peels to active materials: Slipping into bioplastic films with high UV-blocking and antioxidant properties - Rodrigo D. Silva; Thályta F. Pacheco; Amanda D. de Santi; Fabiana Manarelli; Breno R. Bozzo; Michel Brienzo; Caio G. Otoni; Henriette M.C. Azeredo (Journal of Cleaner Production, 2024)

Skull and mandible alterations in Amazon river dolphins (de Blainville, 1817) (Cetacea, Iniidae, Inia spp.) - Lucas M. Lara; Vera M. F. da Silva; Rodrigo S. Amaral (Marine Mammal Science, 2024)

High methane concentrations in tidal salt marsh soils: Where does the methane go? - Margaret Capooci; Angelia L. Seyfferth; Craig Tobias; Andrew S. Wozniak; Alexandra Hedgpeth; Malique Bowen; Jennifer F. Biddle; Karis J. McFarlane; Rodrigo Vargas (Global Change Biology, 2024)
Tidal salt marshes produce and emit CH 4 . Therefore, it is critical to understand the biogeochemical controls that regulate CH 4 spatial and temporal dynamics in wetlands. The prevailing paradigm assumes that acetoclastic methanogenesis is the dominant pathway for CH 4 production, and higher salinity concentrations inhibit CH 4 production in salt marshes. Recent evidence shows that CH 4 is produced within salt marshes via methylotrophic methanogenesis, a process not inhibited by sulfate reduction. To further explore this conundrum, we performed measurements of soil–atmosphere CH 4 and CO 2 fluxes coupled with depth profiles of soil CH 4 and CO 2 pore water gas concentrations, stable and radioisotopes, pore water chemistry, and microbial community composition to assess CH 4 production and fate within a temperate tidal salt marsh. We found unexpectedly high CH 4 concentrations up to 145,000 μmol mol −1 positively correlated with S 2− (salinity range: 6.6–14.5 ppt). Despite large CH 4 production within the soil, soil–atmosphere CH 4 fluxes were low but with higher emissions and extreme variability during plant senescence (84.3 ± 684.4 nmol m −2 s −1 ). CH 4 and CO 2 within the soil pore water were produced from young carbon, with most Δ 14 C‐CH 4 and Δ 14 C‐CO 2 values at or above modern. We found evidence that CH 4 within soils was produced by methylotrophic and hydrogenotrophic methanogenesis. Several pathways exist after CH 4 is produced, including diffusion into the atmosphere, CH 4 oxidation, and lateral export to adjacent tidal creeks; the latter being the most likely dominant flux. Our findings demonstrate that CH 4 production and fluxes are biogeochemically heterogeneous, with multiple processes and pathways that can co‐occur and vary in importance over the year. This study highlights the potential for high CH 4 production, the need to understand the underlying biogeochemical controls, and the challenges of evaluating CH 4 budgets and blue carbon in salt marshes.

Groundwater is a hidden global keystone ecosystem - Mattia Saccò; Stefano Mammola; Florian Altermatt; Roman Alther; Rossano Bolpagni; Anton Brancelj; David Brankovits; Cene Fišer; Vasilis Gerovasileiou; Christian Griebler; Simone Guareschi; Grant C. Hose; et al. (Global Change Biology, 2024)
Groundwater is a vital ecosystem of the global water cycle, hosting unique biodiversity and providing essential services to societies. Despite being the largest unfrozen freshwater resource, in a period of depletion by extraction and pollution, groundwater environments have been repeatedly overlooked in global biodiversity conservation agendas. Disregarding the importance of groundwater as an ecosystem ignores its critical role in preserving surface biomes. To foster timely global conservation of groundwater, we propose elevating the concept of keystone species into the realm of ecosystems, claiming groundwater as a keystone ecosystem that influences the integrity of many dependent ecosystems. Our global analysis shows that over half of land surface areas (52.6%) has a medium‐to‐high interaction with groundwater, reaching up to 74.9% when deserts and high mountains are excluded. We postulate that the intrinsic transboundary features of groundwater are critical for shifting perspectives towards more holistic approaches in aquatic ecology and beyond. Furthermore, we propose eight key themes to develop a science‐policy integrated groundwater conservation agenda. Given ecosystems above and below the ground intersect at many levels, considering groundwater as an essential component of planetary health is pivotal to reduce biodiversity loss and buffer against climate change.

Observing Antarctic Bottom Water in the Southern Ocean - Alessandro Silvano; Sarah Purkey; Arnold L. Gordon; Pasquale Castagno; Andrew L. Stewart; Stephen R. Rintoul; Annie Foppert; Kathryn L. Gunn; Laura Herraiz-Borreguero; Shigeru Aoki; Yoshihiro Nakayama; Alberto C. Naveira Garabato; et al. (Frontiers in Marine Science, 2023)
Dense, cold waters formed on Antarctic continental shelves descend along the Antarctic continental margin, where they mix with other Southern Ocean waters to form Antarctic Bottom Water (AABW). AABW then spreads into the deepest parts of all major ocean basins, isolating heat and carbon from the atmosphere for centuries. Despite AABW’s key role in regulating Earth’s climate on long time scales and in recording Southern Ocean conditions, AABW remains poorly observed. This lack of observational data is mostly due to two factors. First, AABW originates on the Antarctic continental shelf and slope where in situ measurements are limited and ocean observations by satellites are hampered by persistent sea ice cover and long periods of darkness in winter. Second, north of the Antarctic continental slope, AABW is found below approximately 2 km depth, where in situ observations are also scarce and satellites cannot provide direct measurements. Here, we review progress made during the past decades in observing AABW. We describe 1) long-term monitoring obtained by moorings, by ship-based surveys, and beneath ice shelves through bore holes; 2) the recent development of autonomous observing tools in coastal Antarctic and deep ocean systems; and 3) alternative approaches including data assimilation models and satellite-derived proxies. The variety of approaches is beginning to transform our understanding of AABW, including its formation processes, temporal variability, and contribution to the lower limb of the global ocean meridional overturning circulation. In particular, these observations highlight the key role played by winds, sea ice, and the Antarctic Ice Sheet in AABW-related processes. We conclude by discussing future avenues for observing and understanding AABW, impressing the need for a sustained and coordinated observing system.

The marked dextro-dominance causes accentuated morphophysiological variations in the female reproductive organs of the bat Molossus molossus - Juliana F. Ferraz; Rodrigo S. de Oliveira; Cornélio S. Santiago; Emília M. Soares; Eliana Morielle-Versute; Sebastião R. Taboga; Mateus R. Beguelini (Tissue and Cell, 2023)

Assessment of lamb meat quality in two cooking methods: Water bath versus oven cooking - Mariana da S. Leal; Welder A. Baldassini; Rodrigo de N.S. Torres; Rogério A. Curi; Guilherme L. Pereira; Luis Artur L. Chardulo; Rafael F. Santos; Paulo R.L. Meirelles; Ciniro Costa (Small Ruminant Research, 2023)

Pulsed electric field-based technology for microbial inactivation in milk and dairy products - Rodrigo N Cavalcanti; Celso F Balthazar; Larissa P Margalho; Mônica Q Freitas; Anderson S Sant’Ana; Adriano G Cruz (Current Opinion in Food Science, 2023)

Continuous design and techno-economic assessment of a biorefinery process for heparan sulfate extraction from Nodipecten nodosus viscera waste - Caenam M.B. Bastos; Arthur V.L. Barbosa; Tainá C. Pereira; Pedro H.R. Alijó; Rodrigo F. Cano; Jeiveison G.S.S. Maia; João B.V. Bastos; Mauro S.G. Pavão (Chemical Engineering Journal, 2023)

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

Genome-wide association study for growth traits in Blanco Orejinegro and Romosinuano cattle - Diego H. Bejarano; Rodrigo A. Martínez; Juan F. Rocha (Tropical Animal Health and Production, 2023)
Growth traits are economically important characteristics for the genetic improvement of local cattle breeds. Genome-wide association studies (GWAS) provide valuable information to enhance the understanding on the genetics of complex traits. The aim of this study was to perform a GWAS to identify genomic regions and genes associated to birth weight, weaning weight adjusted for 240 days, 16 months, and 24 months weight in Romosinuano (ROMO) and Blanco Orejinegro (BON) cattle. A single-step genomic-BLUP was implemented using 596 BON and 569 ROMO individuals that were genotyped with an Illumina BovineSNP50 BeadChip. There were 25 regions of interest identified on different chromosomes, with few of them simultaneously associated with two or more growth traits and some were common to both breeds. The gene mapping allowed to find 173 annotations on these regions, from which 49 represent potential candidate genes with known growth-related functions in cattle and other species. Among the regions that were associated with several growth traits, that at 24 – 27 MB of BTA14, has important candidate genes such as LYPLA1, XKR4, TMEM68 and PLAG1. Another region of interest at 0.40–0.77 Mb of BTA23 was identified in both breeds, containing KHDRBS2 as a potential candidate gene influencing body weight. Future studies targeting these regions could provide more knowledge to uncover the genetic architecture underlying growth traits in BON and ROMO cattle. The genomic regions and genes identified in this study could be used to improve the prediction of genetic merit for growth traits in these creole cattle breeds.

Tree hydrological niche acclimation through ontogeny in a seasonal Amazon forest - Mauro Brum; Luciana F. Alves; Raimundo C. de Oliveira-Junior; Victor Hugo Pereira Moutinho; Natalia Restrepo-Coupe; Karoline Chaves; Deliane Penha; Neill Prohaska; Plínio Barbosa de Camargo; Grazielle Sales Teodoro; Sebastião Ribeiro Xavier Júnior; Scott C. Stark; et al. (Plant Ecology, 2023)

An extension of the characteristic curve model of plant species behavior in heavy metal soils - Elizabeth J. Lam; Brian F. Keith; Jaume Bech; María E. Gálvez; Rodrigo Rojas; Fernando A. Alvarez; Vicente Zetola; Ítalo L. Montofré (Environmental Geochemistry and Health, 2023)

Better Together: Volatile-Mediated Intraguild Effects on the Preference of Tuta absoluta and Trialeurodes vaporariorum for Tomato Plants - F. Rodrigo; A. P. Burgueño; A. González; C. Rossini (Journal of Chemical Ecology, 2023)

How natural and anthropogenic factors should drive microplastic behavior and fate: The scenario of Brazilian urban freshwater - Fernando F. Sodré; Imisi M. Arowojolu; Maria C. Canela; Rodrigo S. Ferreira; Andreia N. Fernandes; Cassiana C. Montagner; Cristiane Vidal; Mariana A. Dias; Gilberto Abate; Leticia C. da Silva; Marco T. Grassi; Crislaine Bertoldi; et al. (Chemosphere, 2023)

Asymmetric response of Amazon forest water and energy fluxes to wet and dry hydrological extremes reveals onset of a local drought‐induced tipping point - Natalia Restrepo‐Coupe; Bradley O’Donnell Christoffersen; Marcos Longo; Luciana F. Alves; Kleber Silva Campos; Alessandro C. da Araujo; Raimundo C. de Oliveira; Neill Prohaska; Rodrigo da Silva; Raphael Tapajos; Kenia T. Wiedemann; Steven C. Wofsy; et al. (Global Change Biology, 2023)
Understanding the effects of intensification of Amazon basin hydrological cycling—manifest as increasingly frequent floods and droughts—on water and energy cycles of tropical forests is essential to meeting the challenge of predicting ecosystem responses to climate change, including forest “tipping points”. Here, we investigated the impacts of hydrological extremes on forest function using 12+ years of observations (between 2001–2020) of water and energy fluxes from eddy covariance, along with associated ecological dynamics from biometry, at the Tapajós National Forest. Measurements encompass the strong 2015–2016 El Niño drought and La Niña 2008–2009 wet events. We found that the forest responded strongly to El Niño‐Southern Oscillation (ENSO): Drought reduced water availability for evapotranspiration ( ET ) leading to large increases in sensible heat fluxes ( H ). Partitioning ET by an approach that assumes transpiration ( T ) is proportional to photosynthesis, we found that water stress‐induced reductions in canopy conductance ( G s ) drove T declines partly compensated by higher evaporation ( E ). By contrast, the abnormally wet La Niña period gave higher T and lower E , with little change in seasonal ET . Both El Niño‐Southern Oscillation (ENSO) events resulted in changes in forest structure, manifested as lower wet‐season leaf area index. However, only during El Niño 2015–2016, we observed a breakdown in the strong meteorological control of transpiration fluxes (via energy availability and atmospheric demand) because of slowing vegetation functions (via shutdown of G s and significant leaf shedding). Drought‐reduced T and G s , higher H and E , amplified by feedbacks with higher temperatures and vapor pressure deficits, signaled that forest function had crossed a threshold, from which it recovered slowly, with delay, post‐drought. Identifying such tipping point onsets (beyond which future irreversible processes may occur) at local scale is crucial for predicting basin‐scale threshold‐crossing changes in forest energy and water cycling, leading to slow‐down in forest function, potentially resulting in Amazon forests shifting into alternate degraded states.

Amazonian earthworm biodiversity is heavily impacted by ancient and recent human disturbance - Ana C. Conrado; Wilian C. Demetrio; David W.G. Stanton; Marie L.C. Bartz; Samuel W. James; Alessandra Santos; Elodie da Silva; Talita Ferreira; Agno N.S. Acioli; Alexandre C. Ferreira; Lilianne S. Maia; Telma A.C. Silva; et al. (Science of The Total Environment, 2023)

Extremes in water quality parameters modulated by weather and climate conditions in Ceara State, Brazil - Auriane Laurent; Rodrigo Felipe Bedim Godoy; Mariane Cardoso Elias; Gabriel Franco; Andrea F. Carril; Elias Trevisan; Pedro Flombaum (Ecohydrology & Hydrobiology, 2023)

Feeding ecology of the olive ridley turtle (Lepidochelys olivacea) in southern Brazil - Ademir S. Maruyama; Silvina Botta; Rodrigo F. Bastos; Andrine Paiva da Silva; Danielle S. Monteiro (Marine Biology, 2023)

Spatiotemporal variability of dissolved inorganic macronutrients along the northern Antarctic Peninsula (1996–2019) - Thiago Monteiro; Sian F. Henley; Ricardo César Gonçalves Pollery; Carlos Rafael Borges Mendes; Mauricio Mata; Virginia Maria Tavano; Carlos Alberto Eiras Garcia; Rodrigo Kerr (Limnology and Oceanography, 2023)
The northern Antarctic Peninsula is a key region of the Southern Ocean due to its complex ocean dynamics, distinct water mass sources, and the climate‐driven changes taking place in the region. Despite the importance of macronutrients in supporting strong biological carbon uptake and storage, little is known about their spatiotemporal variability along the northern Antarctic Peninsula. Hence, we explored for the first time a 24‐year time series (1996–2019) in this region to understand the processes involved in the spatial and interannual variability of macronutrients. We found high macronutrient concentrations, even in surface waters and during strong phytoplankton blooms. Minimum concentrations of dissolved inorganic nitrogen (DIN; 16 μ mol kg −1 ), phosphate (0.7 μ mol kg −1 ), and silicic acid (40 μ mol kg −1 ) in surface waters are higher than those recorded in surrounding regions. The main source of macronutrients is the intrusions of Circumpolar Deep Water and its modified variety, while local sources (organic matter remineralization, water mass mixing, and mesoscale structures) can enhance their spatiotemporal variability. However, we identified a depletion in silicic acid due to the influence of Dense Shelf Water from the Weddell Sea. Macronutrient concentrations show substantial interannual variability driven by the balance between the intrusions of modified Circumpolar Deep Water and advection of Dense Shelf Water, which is largely modulated by the Southern Annular Mode (SAM) and to some extent by El Niño‐Southern Oscillation (ENSO). These findings are critical to improving our understanding of the natural variability of this Southern Ocean ecosystem and how it is responding to climate changes.

Electrochemical generation of chlorine dioxide for use in environmental remediation - Leticia Mirella da Silva; Ismael F. Mena; Miguel A. Montiel; Cristina Saez; Artur J. Motheo; Manuel A. Rodrigo (Process Safety and Environmental Protection, 2023)

Earliest Acheulian paleolandscape reveals a 1.7 million-year-old megasite at Olduvai Gorge (Tanzania) - M. Domínguez-Rodrigo; D. Uribelarrea; F. Diez-Martín; Mabulla A; A. Gidna; L. Cobo-Sánchez; D.M. Martín-Perea; E. Organista; R. Barba; E. Baquedano (Quaternary Science Reviews, 2023)

Hydroclimatic influence on the trophic ecology of Atlantic goliath grouper juveniles (Epinephelus itajara) in a tropical estuary using non-lethal methodologies - Mario V. Condini; Alexandre M. Garcia; Rodrigo F. Bastos; Sabrina R. Vollrath; Ester F. Barbosa; Rafael L. Oliveira; Lorena L. Almeida; Maurício Hostim-Silva (Marine Environmental Research, 2023)

Environmental characterization of an Amazonian lake for Isoëtes cangae translocation - Luis A. S. Prado; Anderson da R. Gripp; Antônio J. D. Cogo; Mirella P. Santos; Janiélio G. da Rocha; Jorge G. F. Genovez; Emiliano N. Calderon; Rodrigo L. Martins; Allysson B. Cavalcante; Francisco de A. Esteves; Daniel B. Zandonadi (Plant Ecology, 2023)

Interaction of Aspergillus niger in Double-Coated Urea Granules Reduces Greenhouse Gas Emissions from N Fertilization - Vinícius F. Majaron; Marisa G. da Silva; Marcela Pfeifer; Ricardo Bortoletto-Santos; Camila C. V. Velloso; Rodrigo Klaic; Wagner L. Polito; Sidney J. L. Ribeiro; Alberto C. C. Bernardi; Cristiane S. Farinas; Caue Ribeiro (Journal of Soil Science and Plant Nutrition, 2023)

Subacute high-refined carbohydrate diet leads to abnormal reproductive control of the hypothalamic-pituitary axis in female rats - Jeanini Zimerman; Oscar M.S. Niño; Charles S. da Costa; Jordana F. Zanol; Milena Comério; Letícia N. da Gama de Souza; Leandro Miranda-Alves; Rosiane A. Miranda; Patrícia C. Lisboa; Tays A. Camilo; Rodrigo Rorato; Guilherme Andrade Alves; et al. (Reproductive Toxicology, 2023)

Lessons from the invasion front: Integration of research and management of the lionfish invasion in Brazil - Marcelo O. Soares; Pedro H.C. Pereira; Caroline V. Feitosa; Rodrigo Maggioni; Rafael S. Rocha; Luis Ernesto Arruda Bezerra; Oscar S. Duarte; Sandra V. Paiva; Eurico Noleto-Filho; Maiara Queiroz M. Silva; Mayra Csapo-Thomaz; Tatiane M. Garcia; et al. (Journal of Environmental Management, 2023)

Spatiotemporal variability of the relationship between seasonal temperatures and precipitation in Spain, 1951–2019 - F. S. Rodrigo (Theoretical and Applied Climatology, 2023)

Deep Learning-Based Approaches for Oil Spill Detection: A Bibliometric Review of Research Trends and Challenges - Rodrigo N. Vasconcelos; André T. Cunha Lima; Carlos A. D. Lentini; José Garcia V. Miranda; Luís F. F. de Mendonça; José M. Lopes; Mariana M. M. Santana; Elaine C. B. Cambuí; Deorgia T. M. Souza; Diego P. Costa; Soltan G. Duverger; Washington S. Franca-Rocha (Journal of Marine Science and Engineering, 2023)
Oil spill detection and mapping using deep learning (OSDMDL) is crucial for assessing its impact on coastal and marine ecosystems. A novel approach was employed in this study to evaluate the scientific literature in this field through bibliometric analysis and literature review. The Scopus database was used to evaluate the relevant scientific literature in this field, followed by a bibliometric analysis to extract additional information, such as architecture type, country collaboration, and most cited papers. The findings highlight significant advancements in oil detection at sea, with a strong correlation between technological evolution in detection methods and improved remote sensing data acquisition. Multilayer perceptrons (MLP) emerged as the most prominent neural network architecture in 11 studies, followed by a convolutional neural network (CNN) in 5 studies. U-Net, DeepLabv3+, and fully convolutional network (FCN) were each used in three studies, demonstrating their relative significance too. The analysis provides insights into collaboration, interdisciplinarity, and research methodology and contributes to the development of more effective policies, strategies, and technologies for mitigating the environmental impact of oil spills in OSDMDL.

Outstanding productions of peroxymonosulfuric acid combining tailored electrode coating and 3D printing - M. Pilar Castro; Miguel A. Montiel; Ismael F. Mena; Jan Gäbler; Hunter King; Cristina Sáez; Manuel A. Rodrigo (Journal of Water Process Engineering, 2023)

Spatiotemporal variation of behavior and repeatability in a long-lived turtle - Benjamin M. Reed; Kaylyn Hobelman; Aubrey Gauntt; Madison Schwenka; Abigail Trautman; Patience Wagner; Samantha Kim; Chelsea Armstrong; Samuel Wagner; Amelia Weller; Katie Brighton; Shelby Bloom; et al. (Behavioral Ecology and Sociobiology, 2023)

Interdecadal Pacific Oscillation modulation of ENSO teleconnections in its decaying stages: Relations with Indian Ocean basin‐wide mode and South American precipitation - Itamara P. Souza; Rita V. Andreoli; Mary T. Kayano; Wilmar L. Cerón; Rodrigo A. F. Souza; Indrani Roy (International Journal of Climatology, 2023)
This study examines the Interdecadal Pacific Oscillation (IPO) modulation of the El Niño–Southern Oscillation (ENSO) teleconnections in its decaying stages with the tropical ocean by focusing on the Indian Ocean Basin‐Wide (IOBW) mode and the precipitation over South America (SA) in the 1901–2012 period. Composite analyses revealed that the ENSO teleconnections are IPO‐modulated due to the differential ENSO decaying speed, which is slower during the positive than negative IPO phase, for both El Niño (EN) and La Niña (LN) cases. Negative precipitation anomalies related to EN persist over northeastern SA until austral winter for the positive IPO phase (POS IPO), while significant opposite sign anomalies occur in this region for the negative IPO phase (NEG IPO). These results are associated with the Walker circulation's reversal during NEG IPO which is, in turn, accompanied by negative IOBW. During the POS IPO, the positive IOBW causes upward movements over there and, by continuity, downward movements over SA. In the NEG IPO, for LN events the wave train originating in the north of Australia propagates toward subtropical SA, which, coupled with the surface circulation, causes dryness in this region. In addition, the rapid decay of LN in the NEG IPO, followed by the emergence of EN, caused changes in the Walker circulation, such that enhanced upward movements occurred over the Pacific and SA region, and downward movements over the Indian Ocean until austral winter. In turn, the slower decay of the LN in the POS IPO maintains strong subsidence over the central Pacific and weak upward motions over western SA. So, the EN (LN) and positive (negative) IOBW during the POS (NEG) IPO prolong the scarcity of precipitation over equatorial (subtropical) SA. Persistent dry periods over these regions during the ENSO decaying stage might have important implications for the seasonal forecasts.

Rhomb-I, a P–I metalloproteinase from Lachesis muta rhombeata venom degrades vessel extra cellular matrix components and impairs platelet aggregation - Valéria Gonçalves de Alvarenga; Luciana S. Oliveira; Gustavo O. Santos; Dan E. Vivas-Ruiz; Márcia Helena Borges; Rodrigo C.G. de Souza; Johannes A. Eble; Ana Maria Moura-da-Silva; Eladio F. Sanchez (Toxicon, 2023)

Width/length–weight relationships and condition factor of seven decapod crustaceans in a Brazilian tropical estuary - Gustavo F. de Carvalho-Souza; Diego V. Medeiros; Rodrigo de A. Silva; Enrique González-Ortegón (Regional Studies in Marine Science, 2023)

Endometrial fibrosis in mares: Picrosirius Red and Collagen-2 and 3 - Luiz Augusto M Centeno; Henrique BA Bastos; Verônica LC Bueno; Janislene M Trentin; Gustavo R Larentis; Mariani F Fiorenza; Welden Panziera; Gustavo Henrique Z Winter; Sandra Fiala-Rechsteiner; Rodrigo C Mattos; Mara Iolanda B Rubin (Journal of Equine Veterinary Science, 2023)

Responses of ground-dwelling birds and mammals to local environmental variables and human pressure in an Amazonian protected area - Carlos R. Brocardo; Dian C. P. Rosa; Arlison B. Castro; Clarissa Rosa; Kelly Torralvo; Pedro Pequeno; William E. Magnusson; Rodrigo F. Fadini (European Journal of Wildlife Research, 2023)

Argentine Navy Icebreaker Ship “Almirante Irizar” Sludge Microbial Composition Analysis for Biohydrogen Production - Rodrigo E. García; Natalia Pin Viso; Fernando A. Gerosa; Verónica Nishinakamasu; Andrea F. Puebla; Marisa D. Farber; María J. Lavorante (BioEnergy Research, 2023)

Description of two cultivated and two uncultivated new Salinibacter species, one named following the rules of the bacteriological code: Salinibacter grassmerensis sp. nov.; and three named following the rules of the SeqCode: Salinibacter pepae sp. nov., Salinibacter abyssi sp. nov., and Salinibacter pampae sp. nov. - Tomeu Viver; Roth E. Conrad; Marianna Lucio; Mourad Harir; Mercedes Urdiain; Juan F. Gago; Ana Suárez-Suárez; Esteban Bustos-Caparros; Rodrigo Sanchez-Martinez; Eva Mayol; Federico Fassetta; Jinfeng Pang; et al. (Systematic and Applied Microbiology, 2023)

Multiproxy reconstruction of late quaternary upper ocean temperature in the subtropical southwestern Atlantic - Joana F. Cruz; Ioanna Bouloubassi; Arnaud Huguet; Alice M.S. Rodrigues; Thiago P. Santos; Igor M. Venancio; Douglas Lessa; Rodrigo L. Sobrinho; Rodrigo A. Nascimento; Marcelo C. Bernardes (Quaternary Science Reviews, 2023)

Improving performance of proton-exchange membrane (PEM) electro-ozonizers using 3D printing - Ismael F. Mena; Miguel A. Montiel; Cristina Sáez; Manuel A. Rodrigo (Chemical Engineering Journal, 2023)

Virulence factors of Gram-negative bacteria from free-ranging Amazon river dolphins (Inia geoffrensis) - Marcos Fábio Gadelha Rocha; Expedito Maia Diógenes; Vitor Luz Carvalho; Miriam Marmontel; Marcelo Oliveira da Costa; Vera M. F. da Silva; Rodrigo de Souza Amaral; Waleska Gravena; Nívia A. S. do Carmo; Juliana Marigo; Crister José Ocadaque; Alyne Soares Freitas; et al. (Antonie van Leeuwenhoek, 2023)

Estimation of body weight using body measurements in female water buffaloes reared in southeastern Mexico - Jorge Ruiz-Ramos; Oswaldo M. Torres-Chable; Jorge A. Peralta-Torres; Nadia F. Ojeda-Robertos; Carlos Luna-Palomera; Rodrigo Portillo-Salgado; Thobela Louis Tyasi; Antonio Leandro Chaves Gurgel; Luís Carlos Vinhas Ítavo; Alfonso J. Chay-Canul (Tropical Animal Health and Production, 2023)

Where are they from and where are they going? Detecting areas of endemism, distribution patterns and conservation status of the order Spirostreptida in Brazil (Diplopoda, Juliformia) - Luiz F. M. Iniesta; Rodrigo S. Bouzan; Jackson C. Means; Kaloyan Ivanov; Antonio D. Brescovit (Biodiversity and Conservation, 2023)

Scientometric analysis and literature synthesis of 60 years of science on the Atlantic goliath grouper ( Epinephelus itajara ) - Anna C. P. Locatelli; Rodrigo F. Bastos; Matheus A. Oliveira; Beatrice P. Ferreira (Journal of Fish Biology, 2023)
Here, the authors investigate the evolution of scientific literature on the Atlantic goliath grouper ( Epinephelus itajara ), the largest grouper species in the Atlantic. This species was considered threatened according to the IUCN for nearly three decades due to overfishing and has been protected from fishing in a large part of its range. For the purpose of evaluating the scientific production on an endangered species banned from fishing, the authors present a scientometry and synthesis review analysing the literature produced in the timeline and the content of their studies. To this end, they set up an almost 60‐year literary database through the Scopus, Web of Science and Google Scholar platforms. They analyse the publication and knowledge area patterns over the time in the world and in Brazil. They also feature the main areas, locations, ecosystems and types of those research studies and briefly describe the main records found in each decade. An increase in the number of publications was observed from the 1990s onwards worldwide, and particularly in Brazil from the 2000s, coinciding with the pioneering legislations for species protection. Most of the studies were classified within ecology and conservation and took place in countries that implemented moratoriums and had extensive areas of mangroves. Thus, fishing moratorium, classification as endangered, mangroves distribution and conservation all play a role in the studies distribution and contribute positively to the knowledge, as well as support conservation strategies for the species and its ecosystems of occurrence.

An Image-Based Explicit Matrix-Free FEM Implementation with Lumped Mass for NMR Simulations - Luiz F. Bez; Ricardo Leiderman; André Souza; Rodrigo B. de V. Azeredo; André M. B. Pereira (Transport in Porous Media, 2023)

Tolerance in rice genotypes to the sugarcane borer Diatraea saccharalis (Lepidoptera: Crambidae) - Ana Paula Pelosi; Franciele Cristina da Silva; Adriana G. Vaz; André Cirilo de S. Almeida; Anderson Rodrigo da Silva; Flávio G. de Jesus; José Alexandre de F. Barrigossi (Biologia, 2023)

Spatial modeling reveals a growing threat to the world's largest rhodolith beds - Viviane S. dos Santos; Rodrigo L. de Moura; Ulises R. Magdalena; Renae Hovey; Gary Kendrick; Ricardo G. Bahia; Gilberto M. Amado-Filho; Marinez F. de Siqueira (Ocean & Coastal Management, 2023)

Systemic oxalosis in a free-ranging green turtle (Chelonia mydas) - Daniela F Nóbrega; Victor H B Marutani; Marina M Alcala; Ivaí G de Lima Cesar de Albuquerque; Daphne W Goldberg; Cristiane M. del Rio do Valle; Rodrigo del Rio do Valle (Journal of Comparative Pathology, 2023)

What drives the abundance of marsupial carnivores in production forest landscapes? - Evie M. Jones; Amelia J. Koch; Dydee F. Mann; Rodrigo K. Hamede; Menna E. Jones (Forest Ecology and Management, 2023)

Tissue-resident glial cells associate with tumoral vasculature and promote cancer progression - Beatriz G. S. Rocha; Caroline C. Picoli; Bryan O. P. Gonçalves; Walison N. Silva; Alinne C. Costa; Michele M. Moraes; Pedro A. C. Costa; Gabryella S. P. Santos; Milla R. Almeida; Luciana M. Silva; Youvika Singh; Marcelo Falchetti; et al. (Angiogenesis, 2023)

Screening Hoffman-type metal organic frameworks for efficient C2H2/CO2 separation - Wushuang Lou; Jiahao Li; Wanqi Sun; Yongqi Hu; Lingyao Wang; Rodrigo F. Neumann; Mathias Steiner; Zonglin Gu; Binquan Luan; Yuanbin Zhang (Chemical Engineering Journal, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Ants of Brazil: an overview based on 50 years of diversity studies - Rodrigo M. Feitosa; Gabriela P. Camacho; Thiago S. R. Silva; Mônica A. Ulysséa; Natalia Ladino; Aline M. Oliveira; Emília Z. Albuquerque; Fernando A. Schmidt; Carla R. Ribas; Anselmo Nogueira; Fabrício B. Baccaro; Antônio C. M. Queiroz; et al. (Systematics and Biodiversity, 2022)

Multiyear La Niña effects on the precipitation in South America - Aixa Braga Lopes; Rita V. Andreoli; Rodrigo A. F. Souza; Wilmar L. Cerón; Mary T. Kayano; Teresita Canchala; Djanir Sales de Moraes (International Journal of Climatology, 2022)
The effect of multiyear La Niña (LN) events on precipitation in South America (SA) was assessed considering 10 persistent LN events over two successive years, referred to as Y1 and Y2 for the 1901–2012 period. Y1 spans from the austral winter of the first year to autumn of the second year, and Y2 spans from the austral winter of the second year to autumn of the third year. Comparisons were performed season by season of the Y1 and Y2. Composites revealed that the teleconnections related to a multiyear LN event during its Y1 and Y2 years, responsible for distinct seasonal precipitation anomaly patterns in SA, were associated with different tropical ocean conditions. In spring, the negative sea surface temperature (SST) dipole in the Indian Ocean during the Y2 was not observed during Y1. Different LN‐related SST anomaly patterns in the tropical Atlantic between Y1 and Y2 occurred in the other seasons. Over northern/northeastern SA, the positive precipitation anomalies became weaker (stronger) during austral summer and autumn (winter and spring) of the Y2 than Y1 and were associated with changes in the Walker cells. During austral spring and summer, southeastern presented drier conditions during the Y2 than Y1. In the spring of Y2, two Rossby wave trains, one associated with the LN‐related anomalous cooling in the equatorial Pacific and another triggered by the upper‐level anticyclone in the tropical Indian Ocean, characterized the circulation pattern over SA which explains the difference in precipitation anomalies between the Y2 and Y1. These drier (wetter) conditions during austral spring and summer (winter and spring), particularly over southern and southeastern Brazil (Colombia) in the Y2, might have more severe effects on the regional hydrological cycle than those in the Y1. The results here indicate that accurate prediction of LN duration is crucial in a climate‐monitoring context.

Application of linear mixed models for multiple harvest/site trial analyses in perennial plant breeding - Saulo F. S. Chaves; Jeniffer S. P. C. Evangelista; Rodrigo S. Alves; Filipe M. Ferreira; Luiz A. S. Dias; Rafael M. Alves; Kaio O. G. Dias; Leonardo L. Bhering (Tree Genetics & Genomes, 2022)

Density, habitat use and activity patterns of the last giant armadillo population in the Brazilian Atlantic Forest - Juliana B. Pasa; Rodrigo L. Massara; Cynthia E. Widmer; Arnaud L. J. Desbiez; Gabriel F. Massocato; Lucas M. Barreto; Fernando C. C. Azevedo (Mammalian Biology, 2022)

Leveraging multi-harvest data for increasing genetic gains per unit of time for fruit yield and resistance to witches’ broom in Theobroma grandiflorum - Saulo F. S. Chaves; Luiz A. S. Dias; Rodrigo S. Alves; Rafael M. Alves; Jeniffer S. P. C. Evangelista; Kaio O. G. Dias (Euphytica, 2022)

Silicon amendment induces resistance in rice to Diatraea saccharalis (Lepidoptera: Crambidae) - Ana Paula Pelosi; Franciele Cristina da Silva; Adriana G. Vaz; André Cirilo S. Almeida; Anderson Rodrigo da Silva; Michael J. Stout; Flávio G. de Jesus; José Alexandre F. Barrigossi (Arthropod-Plant Interactions, 2022)

Effects of Intra-REV Pore Distribution Modeling in the Flow of Non-Newtonian Fluids in Porous Media - Allan B. G. Motta; Roney L. Thompson; Mateus P. Schwalbert; Luiz F. L. R. Silva; Jovani L. Favero; Rodrigo A. C. Dias; Raphael J. Leitão (Transport in Porous Media, 2022)

Temporal filters in response to presynaptic spike trains: interplay of cellular, synaptic and short-term plasticity time scales - Yugarshi Mondal; Rodrigo F. O. Pena; Horacio G. Rotstein (Journal of Computational Neuroscience, 2022)

New records of pollen tube shower in species of Bertolonia (Melastomataceae) suggest that autogamy may be the rule in the genus - Luan Salles Passos; Renato Goldenberg; Lucas F. Bacci; Francismeire Jane Telles; Fabiano Rodrigo Maia (Plant Systematics and Evolution, 2022)

Hypoglycemic effect of rosmarinic acid-rich infusion (RosCE) from Origanum vulgare in alloxan-induced diabetic rats - Márcio L. A. e Silva; Rodrigo Lucarini; Fransergio F. dos Santos; Carlos H. G. Martins; Patricia M. Pauletti; Ana H. Januario; Mario Ferreira Conceição Santos; Wilson R. Cunha (Natural Product Research, 2022)

Identifying suitable areas for common bottlenose dolphin in anthropized waters - Guilherme Maricato; Rodrigo Tardin; Liliane Lodi; Leonardo L. Wedekin; Fábio G. Daura-Jorge; Israel Maciel; Tatiana F. Maria; Maria Alice S. Alves (Marine Biology, 2022)

Gene-associated markers as a genomic and transcriptomic resource for a highly migratory and apex predator shark (Isurus oxyrinchus) - Rodrigo R. Domingues; Vito Antonio Mastrochirico-Filho; Natalia J. Mendes; Diogo T. Hashimoto; Rui Coelho; Agostinho Antunes; Fausto Foresti; Fernando F. Mendonça (Marine Biology, 2022)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Oscillations and variability in neuronal systems: interplay of autonomous transient dynamics and fast deterministic fluctuations - Rodrigo F. O. Pena; Horacio G. Rotstein (Journal of Computational Neuroscience, 2022)

On the replacement of traditional stabilizers by guaiacol in environmentally safe nitrocellulose-based propellants - Rodrigo L. B. Rodrigues; Ana Paula da Silva; Rogério Rosato; Maurício F. Lemos; Fernando C. Peixoto; Tanos C. C. França; Letivan G. Mendonça Filho (Clean Technologies and Environmental Policy, 2022)

Sensitive fluorescent chemosensor for Hg(II) in aqueous solution using 4’-dimethylaminochalcone - Marco Mellado; Nicole Roldán; Rodrigo Miranda; Luis F. Aguilar; Manuel A. Bravo; Waldo Quiroz (Journal of Fluorescence, 2022)

Oil spill detection based on texture analysis: how does feature importance matter in classification? - Rodrigo N. Vasconcelos; Carlos A. D. Lentini; André T. Cunha Lima; Luís F. F. Mendonça; Garcia V. Miranda; Elaine C. B. Cambuí; Diego Pereira Costa; Soltan Galano Duverger; Mainara B. Gouveia; José M. Lopes; Milton J. Porsani (International Journal of Remote Sensing, 2022)

On the Utilization of Dietary Glycerol in Carnivorous Fish—Part II: Insights Into Lipid Metabolism of Rainbow Trout (Oncorhynchus mykiss) and European Seabass (Dicentrarchus labrax) - Ivan Viegas; Mariana Palma; Elisabeth Plagnes-Juan; Emanuel Silva; João Rito; Luís F. Henriques; Ludgero C. Tavares; Rodrigo O. A. Ozório; Stéphane Panserat; Leonardo J. Magnoni (Frontiers in Marine Science, 2022)
Glycerol is the by-product of biodiesel production and its utilisation in fish feed has recently gained relevance. As an important metabolic intermediate and structural component of triacylglycerol (TAG), it is still unclear whether its supplementation affects lipid utilisation and/or deposition in different tissues. Accordingly, a set of studies was aimed to evaluate how increasing levels of dietary glycerol (0, 2.5 and 5%) affect lipid synthesis in the liver, muscle and adipose tissue. After a growth trial with rainbow trout (8 weeks) and European seabass (6 weeks) fish were sampled at 6 and 24 h to assess mRNA levels of lipid metabolism-related enzymes. The remaining fish were subjected to a metabolic trial consisting of a 6-day residence in deuterated water ( 2 H 2 O) for metabolic flux calculations. This study stands as the second part of a broader experiment that also aimed at evaluating the carbohydrate metabolism ( Viegas et al., 2022 ). Dietary supplementation at 5% glycerol significantly increased plasma TAG levels in both species and liver TAG levels in seabass, with no repercussions on the perivisceral fat index. Despite responding as expected in a postprandial setting, only fas and Δ6-fad in trout and Δ6-fad in seabass responded significantly by increasing with the dietary supplementation of glycerol. In trout, the observed differences in the regulation of these enzymes were not reflected in the de novo lipogenic fluxes. The fractional synthetic rates (FSR) were overall low in all tissues with an average of 0.04, 0.02 and 0.01% d –1 , for liver, muscle and perivisceral fat, respectively. In seabass on the other hand, and despite increased mRNA levels in Δ6-fad, the overall lipid profile in the liver muscle and perivisceral fat was higher in MUFA at the expense of lower PUFA. Moreover, glycerol supplementation altered the lipogenic capacity of seabass with hepatic fractional synthetic rates for TAG-bound FA increasing with increasing glycerol levels (0.32 ± 0.18, 0.57 ± 0.18, and 0.82 ± 0.24 for 0%, 2.5% and 5% glycerol supplementation, respectively). The findings of the present study suggest that supplementation up to 2.5% of glycerol did not severely impact the lipid metabolism nor increased lipogenic potential in liver, muscle and perivisceral fat accumulation.

Environmental conditions differently affect the wing size and shape of two blow fly species (Calliphoridae) of forensic importance in the Brazilian tropical ecosystems - Rodrigo F. R. Carmo; Diego Astúa; Simão D. Vasconcelos (International Journal of Tropical Insect Science, 2022)

The voltage and spiking responses of subthreshold resonant neurons to structured and fluctuating inputs: persistence and loss of resonance and variability - Rodrigo F. O. Pena; Horacio G. Rotstein (Biological Cybernetics, 2022)

Indigenous and local communities can boost seed supply in the UN decade on ecosystem restoration - Danilo Urzedo; Simone Pedrini; Daniel L. M. Vieira; Alexandre B. Sampaio; Bruna D. F. Souza; Eduardo Malta Campos-Filho; Fatima C. M. Piña-Rodrigues; Isabel B. Schmidt; Rodrigo G. P. Junqueira; Kingsley Dixon (Ambio, 2022)
The UN Decade of Ecosystem Restoration is poised to trigger the recovery of ecosystem services and transform structural injustices across the world in a way unparalleled in human history. The inclusion of diverse Indigenous and local communities to co-create robust native seed supply systems is the backbone to achieve the goals for the Decade. Here we show how community-based organizations have co-developed native seed supply strategies for landscape restoration from the bottom-up. We draw on the interconnections over two decades of seed networks in Brazil and the emerging Indigenous participation in native seed production in Australia. From an environmental justice perspective, we provide a participatory seed supply approach for local engagement, noting local geographical, social and cultural contexts. Meeting large-scale restoration goals requires the connection between local seed production and collaborative platforms to negotiate roles, rights and responsibilities between stakeholders. An enduring native seed supply must include a diversity of voices and autonomy of community groups that builds equitable participation in social, economic, and environmental benefits.

Molecular Detection of Trypanosoma kaiowa in Tabanus triangulum (Diptera: Tabanidae) from the Coastal Plain of Rio Grande do Sul, Southern Brazil - Gratchela D. Rodrigues; Eduardo Blodorn; Ândrio Zafalon-Silva; William Domingues; Roberta Marques; Tiago K. Krolow; Gonzalo Greif; Vinicius F. Campos; Rodrigo F. Krüger (Acta Parasitologica, 2022)

Acetylcholinesterase inhibitory activity of Ocotea pomaderroides extracts: HPLC-MS/MS characterization and molecular modeling studies - Isabella M. A. Reis; Dayse S. A. Cassiano; Rodrigo S. Conceição; Humberto F. de Freitas; Samuel S. da R. Pita; Jorge M. David; Alexsandro Branco (Natural Product Research, 2022)

Life cycle assessment of the human energy expenditure in mobility activities - Roni M. Severis; Júlia F. Alvarenga; Flávio J. Simioni; Rodrigo A. F. Alvarenga; Sebastião R. Soares (The International Journal of Life Cycle Assessment, 2022)

A Novel Diselenide-Probucol-Analogue Protects Against Methylmercury-Induced Toxicity in HT22 Cells by Upregulating Peroxide Detoxification Systems: a Comparison with Diphenyl Diselenide - Ruth L. Quispe; Michael L. Jaramillo; Ingrid A. V. Wolin; Rômulo F. S. Canto; Flavio A. R. Barbosa; Antônio L. Braga; João B. T. Rocha; Michael Aschner; Rodrigo B. Leal; Andreza F. de Bem; Marcelo Farina (Neurotoxicity Research, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

From anecdotes to quantification: advances in characterizing volcanic eruption impacts on the built environment - Natalia Irma Deligne; Susanna F. Jenkins; Elinor S. Meredith; George T. Williams; Graham S. Leonard; Carol Stewart; Thomas M. Wilson; Sébastien Biass; Daniel M. Blake; Russell J. Blong; Costanza Bonadonna; Rodrigo Calderon B.; et al. (Bulletin of Volcanology, 2022)

The microbiome of a shell mound: ancient anthropogenic waste as a source of Streptomyces degrading recalcitrant polysaccharides - Luciano F. Huergo; Marcelo Conzentino; Maria V. Gonçalves; Marcos V. Gernet; Rodrigo A. Reis; Fábio O. Pedrosa; Valter A. Baura; Araceli Pires; Edileusa C. M. Gerhardt; Thalita R. Tuleski; Eduardo Balsanelli; Dieval Guizelini; et al. (World Journal of Microbiology and Biotechnology, 2021)

Pyramiding dsRNAs increases phytonematode tolerance in cotton plants - Maria E. Lisei-de-Sá; Paolo L. Rodrigues-Silva; Carolina V. Morgante; Bruno Paes de Melo; Isabela T. Lourenço-Tessutti; Fabricio B. M. Arraes; João P. A. Sousa; Rafael Galbieri; Regina M. S. Amorim; Camila B. J. de Lins; Leonardo L. P. Macedo; Valdeir J. Moreira; et al. (Planta, 2021)

The Prevalence and Characteristics of Alexithymia in Adults Following Brain Injury: A Meta-Analysis - Danielle M. Fynn; Gilles E. Gignac; Rodrigo Becerra; Carmela F. Pestell; Michael Weinborn (Neuropsychology Review, 2021)

Identification of a hybrid atypical enteropathogenic and enteroaggregative Escherichia coli (aEPEC/EAEC) clone of serotype O3:H2 associated with a diarrheal outbreak in Brazil - Daiany R. P. de Lira; Adriene M. F. Cavalcanti; Sandra R. S. Pinheiro; Henrique Orsi; Luís F. dos Santos; Rodrigo T. Hernandes (Brazilian Journal of Microbiology, 2021)

Antigen production and development of an indirect ELISA based on the nucleocapsid protein to detect human SARS-CoV-2 seroconversion - Marcelo S. Conzentino; Karl Forchhammer; Emanuel M. Souza; Fábio O. Pedrosa; Meri B. Nogueira; Sônia M. Raboni; Fabiane G. M. Rego; Dalila L. Zanette; Mateus N. Aoki; Jeanine M. Nardin; Bruna Fornazari; Hugo M. P. Morales; et al. (Brazilian Journal of Microbiology, 2021)

LT‐Brazil: A database of leaf traits across biomes and vegetation types in Brazil - Eduardo Mariano; Taciana F. Gomes; Silvia R. M. Lins; Adibe L. Abdalla‐Filho; Amin Soltangheisi; Maria G. S. Araújo; Rodrigo F. Almeida; Fernanda G. Augusto; Luiza P. Canisares; Siglea S. F. Chaves; Cristiane F. G. Costa; Thaís R. Diniz‐Reis; et al. (Global Ecology and Biogeography, 2021)
Motivation Leaf traits represent an important component of plant functional strategies, and those related to carbon fixation and nutrient acquisition form the leaf economics spectrum. However, observations of functional leaf traits are underrepresented in tropical regions in comparison with those in temperate areas. Brazil, a country with continental scale and vast biodiversity is a timely example, where many biomes are impacted by human activities and climate change. However, leaf traits relevant to understand vegetation responses to these impacts remain poorly quantified for many species found in the country. We compiled an extensive data set of four functional leaf traits for native woody species occurring in the Brazilian territory. In addition to trait observations, sampling dates and geo‐references were compiled and climatic parameters and soil properties of each sampling site were extracted from several databases. Main types of variables contained The LT‐Brazil data set contains 3,479, 1,216, 775 and 775 clean observations of leaf mass per area, leaf nitrogen (N) concentration per unit mass, leaf phosphorus (P) concentration per unit mass, and leaf N : P ratio, respectively, from native woody species, encompassing information of biome, vegetation, taxonomic data, geographical coordinates, climatic parameters, as well as soil properties. Spatial location and grain We compiled trait observations from 223 sites under native vegetation distributed in all main biomes (i.e., Amazônia, Caatinga, Cerrado, Mata Atlântica, Pampa and Pantanal) across the Brazilian territory. Time period and grain The data represent information published and/or sampled during the last 25 years. Major taxa and level of measurement Our compilation was focused on trait data observed for native woody species, excluding monocots, palm trees, herbs, and hemiparasitic plants. Thus, 108, 478 and 1,321 botanical families, genera and species were included, covering c . 9% of the woody angiosperm flora of Brazil. Software format Data are provided as comma‐separated value (.csv) files.

A User-Oriented Local Coastal Flooding Early Warning System Using Metamodelling Techniques - Déborah Idier; Axel Aurouet; François Bachoc; Audrey Baills; José Betancourt; Fabrice Gamboa; Thierry Klein; Andrés F. López-Lopera; Rodrigo Pedreros; Jérémy Rohmer; Alexandre Thibault (Journal of Marine Science and Engineering, 2021)
Given recent scientific advances, coastal flooding events can be properly modelled. Nevertheless, such models are computationally expensive (requiring many hours), which prevents their use for forecasting and warning. In addition, there is a gap between the model outputs and information actually needed by decision makers. The present work aims to develop and test a method capable of forecasting coastal flood information adapted to users’ needs. The method must be robust and fast and must integrate the complexity of coastal flood processes. The explored solution relies on metamodels, i.e., mathematical functions that precisely and efficiently (within minutes) estimate the results that would provide the numerical model. While the principle of relying on metamodel solutions is not new, the originality of the present work is to tackle and validate the entire process from the identification of user needs to the establishment and validation of the rapid forecast and early warning system (FEWS) while relying on numerical modelling, metamodelling, the development of indicators, and information technologies. The development and validation are performed at the study site of Gâvres (France). This site is subject to wave overtopping, so the numerical phase-resolving SWASH model is used to build the learning dataset required for the metamodel setup. Gaussian process- and random forest classifier-based metamodels are used and post-processed to estimate 14 indicators of interest for FEWS users. These metamodelling and post-processing schemes are implemented in an FEWS prototype, which is employed by local users and exhibits good warning skills during the validation period. Based on this experience, we provide recommendations for the improvement and/or application of this methodology and individual steps to other sites.

Benzophenone and Diethyl Phthalate Removal from Real Wastewater by a Multi-stage Hybrid Reactor - Amanda F. do Amaral; Alexandre S. A. da Silva; Rodrigo Coutinho; Deivisson L. Cunha; Marcia Marques (Water, Air, & Soil Pollution, 2021)

A “Dirty” Footprint: Macroinvertebrate diversity in Amazonian Anthropic Soils - Wilian C. Demetrio; Ana C. Conrado; Agno N. S. Acioli; Alexandre C. Ferreira; Marie L. C. Bartz; Samuel W. James; Elodie da Silva; Lilianne S. Maia; Gilvan C. Martins; Rodrigo S. Macedo; David W. G. Stanton; Patrick Lavelle; et al. (Global Change Biology, 2021)
Amazonian rainforests, once thought to be pristine wilderness, are increasingly known to have been widely inhabited, modified, and managed prior to European arrival, by human populations with diverse cultural backgrounds. Amazonian Dark Earths (ADEs) are fertile soils found throughout the Amazon Basin, created by pre‐Columbian societies with sedentary habits. Much is known about the chemistry of these soils, yet their zoology has been neglected. Hence, we characterized soil fertility, macroinvertebrate communities, and their activity at nine archeological sites in three Amazonian regions in ADEs and adjacent reference soils under native forest (young and old) and agricultural systems. We found 673 morphospecies and, despite similar richness in ADEs (385 spp.) and reference soils (399 spp.), we identified a tenacious pre‐Columbian footprint, with 49% of morphospecies found exclusively in ADEs. Termite and total macroinvertebrate abundance were higher in reference soils, while soil fertility and macroinvertebrate activity were higher in the ADEs, and associated with larger earthworm quantities and biomass. We show that ADE habitats have a unique pool of species, but that modern land use of ADEs decreases their populations, diversity, and contributions to soil functioning. These findings support the idea that humans created and sustained high‐fertility ecosystems that persist today, altering biodiversity patterns in Amazonia.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

A Continuum Model for the Unfolding of von Willebrand Factor - Mansur Zhussupbekov; Rodrigo Méndez Rojano; Wei-Tao Wu; Mehrdad Massoudi; James F. Antaki (Annals of Biomedical Engineering, 2021)

Correction to: Summer phyto‑ and bacterioplankton communities during low and high productivity scenarios in the Western Antarctic Peninsula - Sebastián Fuentes; José Ignacio Arroyo; Susana Rodriguez‑Marconi; Italo Masotti; Tomás Alarcon‑Schumacher; Martin F. Polz; Nicole Trefault; Rodrigo De la Iglesia; Beatriz Díez (Polar Biology, 2021)

C(3)1-TAg in C57BL/6 J background as a model to study mammary tumor development - Isadora F. G. Sena; Beatriz G. S. Rocha; Caroline C. Picoli; Gabryella S. P. Santos; Alinne C. Costa; Bryan O. P. Gonçalves; Ana Paula V. Garcia; Maryam Soltani-asl; Leda M. C. Coimbra-Campos; Walison N. Silva; Pedro A. C. Costa; Mauro C. X. Pinto; et al. (Histochemistry and Cell Biology, 2021)

Fifteen days of moderate normobaric hypoxia does not affect mitochondrial function, and related genes and proteins, in healthy men - Alessandra Ferri; Xu Yan; Jujiao Kuang; Cesare Granata; Rodrigo S. F. Oliveira; Christopher P. Hedges; Adriano E. Lima-Silva; Francois Billaut; David J. Bishop (European Journal of Applied Physiology, 2021)

Variable levels of antibiosis and/or antixenosis of Bt and non-Bt maize genotypes on Dalbulus maidis (Hemiptera: Cicadellidae) - Rodrigo D. Faria; Edson L. L. Baldin; Vinicius S. Takaku; Vinicius F. Canassa (Arthropod-Plant Interactions, 2021)

Mechanisms of dispersal and establishment drive a stepping stone community assembly on seamounts and oceanic islands - Eric F. Mazzei; Hudson T. Pinheiro; Thiony Simon; Rodrigo L. Moura; Raphael M. Macieira; Caio R. Pimentel; João Batista Teixeira; Sergio R. Floeter; Carlos Eduardo L. Ferreira; Renato D. Ghisolfi; Ronaldo B. Francini-Filho; Juan P. Quimbayo; et al. (Marine Biology, 2021)

Ancestry analysis indicates two different sets of essential genes in eukaryotic model species - Iara D. de Souza; Clovis F. Reis; Diego A. A. Morais; Vítor G. S. Fernandes; João Vitor F. Cavalcante; Rodrigo J. S. Dalmolin (Functional & Integrative Genomics, 2021)

Aerobic and anaerobic metabolic scaling in the burrowing freshwater crayfish Parastacus pugnax - Jorge Toro-Chacon; Flora Tickell; Rodrigo González; Pedro F. Victoriano; Igor Fernández-Urruzola; Mauricio A. Urbina (Journal of Comparative Physiology B, 2021)

Antidepressant-like effect of guanosine involves activation of AMPA receptor and BDNF/TrkB signaling - Priscila B. Rosa; Luis E. B. Bettio; Vivian B. Neis; Morgana Moretti; Fernanda N. Kaufmann; Mauren K. Tavares; Isabel Werle; Yasmim Dalsenter; Nicolle Platt; Axel F. Rosado; Daiane B. Fraga; Isabella A. Heinrich; et al. (Purinergic Signalling, 2021)

Correction to: Combining machine learning and texture analysis to differentiate mediastinal lymph nodes in lung cancer patients - Allan F. F. Alves; Sérgio A. Souza; Raul L. Ruiz; Tarcísio A. Reis; Agláia M. G. Ximenes; Erica N. Hasimoto; Rodrigo P. S. Lima; José Ricardo A. Miranda; Diana R. Pina (Physical and Engineering Sciences in Medicine, 2021)

Combining machine learning and texture analysis to differentiate mediastinal lymph nodes in lung cancer patients - Allan F. F. Alves; Sérgio A. Souza; Raul L. Ruiz; Tarcísio A. Reis; Agláia M. G. Ximenes; Erica N. Hasimoto; Rodrigo P. S. Lima; José Ricardo A. Miranda; Diana R. Pina (Physical and Engineering Sciences in Medicine, 2021)

Ruthenium (II)/allopurinol complex inhibits breast cancer progression via multiple targets - Ingrid O. Travassos; Francyelli Mello-Andrade; Raíssa P. Caldeira; Wanessa C. Pires; Paula F. F. da Silva; Rodrigo S. Correa; Tamara Teixeira; Alisson Martins-Oliveira; Alzir. A. Batista; Elisângela P. de Silveira-Lacerda (JBIC Journal of Biological Inorganic Chemistry, 2021)

Integrated Physiological Biomarkers Responses in Wild Fish Exposed to the Anthropogenic Gradient in the Biobío River, South-Central Chile - Mauricio Quiroz-Jara; Silvia Casini; Maria Cristina Fossi; Rodrigo Orrego; Juan F. Gavilán; Ricardo Barra (Environmental Management, 2021)

Neuroplastin expression is essential for hearing and hair cell PMCA expression - Xiao Lin; Michael G. K. Brunk; Pingan Yuanxiang; Andrew W. Curran; Enqi Zhang; Franziska Stöber; Jürgen Goldschmidt; Eckart D. Gundelfinger; Maike Vollmer; Max F. K. Happel; Rodrigo Herrera-Molina; Dirk Montag (Brain Structure and Function, 2021)
Hearing deficits impact on the communication with the external world and severely compromise perception of the surrounding. Deafness can be caused by particular mutations in the neuroplastin ( Nptn ) gene, which encodes a transmembrane recognition molecule of the immunoglobulin (Ig) superfamily and plasma membrane Calcium ATPase (PMCA) accessory subunit. This study investigates whether the complete absence of neuroplastin or the loss of neuroplastin in the adult after normal development lead to hearing impairment in mice analyzed by behavioral, electrophysiological, and in vivo imaging measurements. Auditory brainstem recordings from adult neuroplastin-deficient mice ( Nptn −/− ) show that these mice are deaf. With age, hair cells and spiral ganglion cells degenerate in Nptn −/− mice. Adult Nptn −/− mice fail to behaviorally respond to white noise and show reduced baseline blood flow in the auditory cortex (AC) as revealed by single-photon emission computed tomography (SPECT). In adult Nptn −/− mice, tone-evoked cortical activity was not detectable within the primary auditory field (A1) of the AC, although we observed non-persistent tone-like evoked activities in electrophysiological recordings of some young Nptn −/− mice. Conditional ablation of neuroplastin in Nptn lox/loxEmx1Cre mice reveals that behavioral responses to simple tones or white noise do not require neuroplastin expression by central glutamatergic neurons. Loss of neuroplastin from hair cells in adult Nptn Δlox/loxPrCreERT mice after normal development is correlated with increased hearing thresholds and only high prepulse intensities result in effective prepulse inhibition (PPI) of the startle response. Furthermore, we show that neuroplastin is required for the expression of PMCA 2 in outer hair cells. This suggests that altered Ca 2+ homeostasis underlies the observed hearing impairments and leads to hair cell degeneration. Our results underline the importance of neuroplastin for the development and the maintenance of the auditory system.

Influence of Silver Nanoparticle–Based Coating on Calcareous Rock Surfaces on Microbial Biofilm Colonization in Intertidal Environments in Campeche, Mexico - Juan Carlos Camacho-Chab; Benjamín O. Ortega-Morales; Christine Gaylarde; Juan E. Pereañez-Sacarías; Hilda P. León-Tejera; Rodrigo E. Tun-Che; Radames J. Álvarez-Zapata; Augusto I. Almeyda-Cen; William Talavera-Pech; Juan F. Illescas-Salinas (Water, Air, & Soil Pollution, 2021)

Invasive plants in Brazil: climate change effects and detection of suitable areas within conservation units - Luiza Gabriela Fulgêncio-Lima; André Felipe A. Andrade; Bruno Vilela; Dilermando P. Lima-Júnior; Rodrigo Antônio de Souza; Luciano F. Sgarbi; Juliana Simião-Ferreira; Paulo De Marco Jr; Daniel P. Silva (Biological Invasions, 2021)

Seasonal Changes in Dissolved Organic Matter Composition in a Patagonian Fjord Affected by Glacier Melt Inputs - Matthew G. Marshall; Anne M. Kellerman; Jemma L. Wadham; Jon R. Hawkings; Giovanni Daneri; Rodrigo Torres; Helena V. Pryer; Alexander Beaton; Hong Chin Ng; Alejandra Urra; Laura F. Robinson; Robert G. M. Spencer (Frontiers in Marine Science, 2021)
Biogeochemical processes in fjords are likely affected by changes in surrounding glacier cover but very little is known about how meltwater directly influences dissolved organic matter (DOM) in fjords. Moreover, the data available are restricted to a handful of northern hemisphere sites. Here we analyze seasonal and spatial variation in dissolved organic carbon (DOC) concentration and DOM composition (spectrofluorescence, ultrahigh resolution mass spectrometry) in Baker-Martinez Fjord, Chilean Patagonia (48°S), to infer the impacts of rapid regional deglaciation on fjord DOM. We show that surface layer DOC concentrations do not vary significantly between seasons, but DOM composition is sensitive to differences in riverine inputs. In summer, higher protein-like fluorescence reflects increased glacial meltwater inputs, whilst molecular level data show weaker influence from marine DOM due to more intense stratification. We postulate that the shifting seasonal balance of riverine and marine waters affects the supply of biolabile peptides and organic nitrogen cycling in the surface layer. Trends in DOM composition with increasing salinity are consistent with patterns in estuaries (i.e. preferential removal of aromatic compounds and increasing relative contribution of unsaturated and heteroatom-rich DOM from marine sources). Preliminary estimates also suggest that at least 10% of the annual organic carbon stock in this fjord is supplied by the four largest, glacially fed rivers and that these inputs are dominated by dissolved (84%) over particulate organic carbon. Riverine DOC may therefore be an important carbon subsidy to bacterial communities in the inner fjord. The overall findings highlight the biogeochemical sensitivity of a Patagonian fjord to changes in glacier melt input, which likely has relevance for other glaciated fjords in a warming climate.

Synergy of Aspergillus niger and Components in Biofertilizer Composites Increases the Availability of Nutrients to Plants - Rodrigo Klaic; Gelton G. F. Guimarães; Amanda S. Giroto; Alberto C. C. Bernardi; Teresa C. Zangirolami; Caue Ribeiro; Cristiane S. Farinas (Current Microbiology, 2021)

Age and growth of franciscana, Pontoporia blainvillei , and Guiana, Sotalia guianensis , dolphins from southeastern Brazil - Valéria R. M. Conversani; Débora F. Silva; Rodrigo A. Barbosa; Aleta A. Hohn; Marcos C. de O. Santos (Marine Mammal Science, 2021)

Population genetics reveals global and regional history of the apex predator Galeocerdo cuvier (carcharhiniformes) with comments on mitigating shark attacks in north‐eastern brazil - Flávia R.S. Andrade; André S. Afonso; Fábio H.V. Hazin; Fernando F. Mendonça; Rodrigo A. Torres (Marine Ecology, 2021)
The knowledge of the population structure of a given species is of great importance for its conservation and for the management of its fishing exploitation, especially for sharks. The tiger shark ( Galeocerdo cuvier Péron&Lesueur, 1822) is an apex predator species that is currently listed as “Near Threatened” on the International Union for the Conservation of Nature's (IUCN) Red List of Threatened Species. In this study, the tiger shark's genetic structure in the Metropolitan Region of Recife (MRR) and oceanic archipelago of Fernando de Noronha (FN) was investigated based on one mitochondrial and two nuclear DNA markers. In addition, sequenced data from other geographic sites were added into the mitochondrial analysis. The data showed moderate‐to‐high genetic diversity, and it is consistent with good resilience of G. cuvier in ecological terms. The structuring tests reinforced a global distinction of the species in two lineages, one being from the Indo‐Pacific and the other from the North Atlantic. Also, this analysis showed the close relationship between tiger sharks from Indo‐Pacific and South‐eastern coast of Brazil. The Bayesian and AMOVA tests indicated that tiger sharks from FN and MRR are genetically similar, forming a cohesive population. These analyses support live specimen translocations from beaches (where the attacks occur) to distant marine areas given we detected a historical cohesive population occurring between those beaches from MRR and FN Islands where the sharks migrate. This research is the first that has validated individual translocations as a green strategy in South‐western Atlantic.

Predator tactics and prey densities modulate the strength of trophic interactions in a temperate rocky reef - Rodrigo H Muñoz-Cordovez; Sergio A. Carrasco; F. Patricio Ojeda; Alejandro Pérez-Matus (Marine Biology, 2021)

Multi-mixture herbicides provide management strategies in the control of the aquatic weed Heteranthera reniformis - Úrsula R. Zaidan; Larissa M. Motta; Wendel M. de Souza; Rodrigo M. Faria; Maria C. G. Paiva; Kassio F. Mendes; Francisco Cláudio L. de Freitas (Journal of Crop Science and Biotechnology, 2021)

Accounting for relatedness and spatial structure to improve plant phenotypic selection in the wild - Francisco E. Fontúrbel; Pedro F. Ferrer; Caren Vega-Retter; Rodrigo Medel (Evolutionary Ecology, 2021)

Purification of arsenic-contaminated water using iron molybdate filters and monitoring of their genotoxic, mutagenic, and cytotoxic effects through bioassays - Rodrigo C. Hott; Thainá S. Magalhães; Luiz F. O. Maia; Kallel S. F. Santos; Guilherme L. Rodrigues; Luiz C. A. Oliveira; Márcio C. Pereira; Márcia C. S. Faria; Alessandra P. Carli; Caio C. Souza Alves; Jairo L. Rodrigues (Environmental Science and Pollution Research, 2021)

Vineyard environments influence Malbec grapevine phenotypic traits and DNA methylation patterns in a clone-dependent way - Anabella Varela; Verónica N. Ibañez; Rodrigo Alonso; Diego Zavallo; Sebastián Asurmendi; Sebastián Gomez Talquenca; Carlos F. Marfil; Federico J. Berli (Plant Cell Reports, 2021)

Nitrogen loading of Eucalyptus globulus seedlings: nutritional dynamics and influence on morphology and root growth potential - Manuel Acevedo; Rafael Rubilar; R. Kasten Dumroese; Juan F. Ovalle; Simón Sandoval; Rodrigo Chassin-Trubert (New Forests, 2021)

Impact of Inoculation with Pseudomonas aestus CMAA 1215T on the Non-target Resident Bacterial Community in a Saline Rhizosphere Soil - Rafael L. F. Vasconcellos; Emiliana Manesco Romagnoli; Rodrigo G. Taketani; Suikinai Nobre Santos; Tiago Domingues Zucchi; Itamar Soares Melo (Current Microbiology, 2021)

Environmental Drivers and Distribution Patterns of Carnivoran Assemblages (Mammalia: Carnivora) in the Americas: Past to Present - Andrés Arias-Alzate; José F. González-Maya; Joaquín Arroyo-Cabrales; Rodrigo A. Medellín; Enrique Martínez-Meyer (Journal of Mammalian Evolution, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

Top-down characterization of resource use in LCA: from problem definition of resource use to operational characterization factors for dissipation of elements to the environment - Lauran van Oers; Jeroen B. Guinée; Reinout Heijungs; Rita Schulze; Rodrigo A. F. Alvarenga; Jo Dewulf; Johannes Drielsma; David Sanjuan-Delmás; Tobias C. Kampmann; Glenn Bark; Ainara Garcia Uriarte; Pierre Menger; et al. (The International Journal of Life Cycle Assessment, 2020)
Purpose The methods for assessing the impact of using abiotic resources in life cycle assessment (LCA) have always been heavily debated. One of the main reasons for this is the lack of a common understanding of the problem related to resource use. This article reports the results of an effort to reach such common understanding between different stakeholder groups and the LCA community. For this, a top-down approach was applied. Methods To guide the process, a four-level top-down framework was used to (1) demarcate the problem that needs to be assessed, (2) translate this into a modeling concept, (3) derive mathematical equations and fill these with data necessary to calculate the characterization factors, and (4) align the system boundaries and assumptions that are made in the life cycle impact assessment (LCIA) model and the life cycle inventory (LCI) model. Results We started from the following definition of the problem of using resources: the decrease of accessibility on a global level of primary and/or secondary elements over the very long term or short term due to the net result of compromising actions. The system model distinguishes accessible and inaccessible stocks in both the environment and the technosphere. Human actions can compromise the accessible stock through environmental dissipation, technosphere hibernation, and occupation in use or through exploration. As a basis for impact assessment , we propose two parameters: the global change in accessible stock as a net result of the compromising actions and the global amount of the accessible stock. We propose three impact categories for the use of elements: environmental dissipation, technosphere hibernation, and occupation in use, with associated characterization equations for two different time horizons. Finally, preliminary characterization factors are derived and applied in a simple illustrative case study for environmental dissipation. Conclusions Due to data constraints, at this moment, only characterization factors for “dissipation to the environment” over a very-long-term time horizon could be elaborated. The case study shows that the calculation of impact scores might be hampered by insufficient LCI data. Most presently available LCI databases are far from complete in registering the flows necessary to assess the impacts on the accessibility of elements. While applying the framework, various choices are made that could plausibly be made differently. We invite our peers to also use this top-down framework when challenging our choices and elaborate that into a consistent set of choices and assumptions when developing LCIA methods.

Removal of sulfamethoxazole, sulfadiazine, and sulfamethazine by UV radiation and HO• and SO4•− radicals using a response surface model and DFT calculations - Luis A. J. Rodríguez-Blanco; Raúl Ocampo-Pérez; Cesar F. A. Gómez-Durán; Juan P. Mojica-Sánchez; Rodrigo S. Razo-Hernández (Environmental Science and Pollution Research, 2020)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Reproductive parameters of franciscana dolphins ( Pontoporia blainvillei ) of Southeastern Brazil - Débora F. Silva; Rodrigo A. Barbosa; Valéria R. M. Conversani; Silvina Botta; Aleta A. Hohn; Marcos C. de O. Santos (Marine Mammal Science, 2020)
Reproductive parameters of 168 franciscana dolphins, Pontoporia blainvillei (73 females and 95 males) incidentally caught ( n = 163) or stranded ( n = 5) between 2005 and 2016 in southeastern Brazil are presented. Ovarian macroscopic analysis revealed 55 immature (75.3%) and 18 mature (24.7%) females. Annual pregnancy rate was estimated to be 0.36, with a calving interval of 2.8 years. Testicular histology revealed 66 immature (69.5%) and 29 mature (30.5%) males. Males with combined testis weight above 4 g were mature, and 1‐year‐old mature males and a 2‐year‐old pregnant female are reported for the first time for the species. Reproductive seasonality does not seem to occur in the study area. Mean age and length at sexual maturation were estimated to be at 2.7 years and 128.5 cm for females, and 2.7 years and 114.0 cm for males. These estimates are lower than most of the estimates for this species. These results add novel and valuable information on the reproductive patterns of this endangered species, threatened by high levels of mortality in gill net fisheries. The information presented here represents an important effort to obtain more reliable parameter estimates for the studied area, needed for a better assessment of its current conservation status.

Restricted connectivity and population genetic fragility in a globally endangered Hammerhead Shark - Danillo Pinhal; Rodrigo R. Domingues; Christine C. Bruels; Bruno L. S. Ferrette; Otto B. F. Gadig; Mahmood S. Shivji; Cesar Martins (Reviews in Fish Biology and Fisheries, 2020)

Sugarcane Juice with Co-encapsulated Bifidobacterium animalis subsp. lactis BLC1 and Proanthocyanidin-Rich Cinnamon Extract - Augusto Tasch Holkem; Edmur José Santos Neto; Megumi Nakayama; Clitor J. F. Souza; Marcelo Thomazini; Fabio Augusto Gallo; Marluci Palazzolli da Silva; Laura de Queiroz Bomdespacho; Carla Giovana Luciano; Izabel Cristina Freitas Moraes; Rodrigo Rodrigues Petrus; Carmen S. Favaro-Trindade (Probiotics and Antimicrobial Proteins, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Chemical composition of essential oils from different parts of Protium heptaphyllum (Aubl.) Marchand and their in vitro antibacterial activity - Rodrigo S. C. Cabral; Cassia C. F. Alves; Hellen R. F. Batista; Wendel C. Sousa; Isabela S. Abrahão; Antônio E. M. Crotti; Mariana B. Santiago; Carlos H. G. Martins; Mayker L. D. Miranda (Natural Product Research, 2020)

Contrasting responses of cluster roots formation induced by phosphorus and nitrogen supply in Embothrium coccineum populations from different geographical origin - Ariana Bertin-Benavides; Luisa Bascuñán-Godoy; Carlos Henríquez-Castillo; Mabel Delgado; Carlos F. Burgos; Catalina Mardones; Andrea Ávila-Valdés; Francisco Valdebenito; Soraya Bravo; Rafael Rubilar; Rodrigo Hasbún; Alejandra Zúñiga-Feest (Plant and Soil, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Changing Biogeochemistry of the Southern Ocean and Its Ecosystem Implications - Sian F. Henley; Emma L. Cavan; Sarah E. Fawcett; Rodrigo Kerr; Thiago Monteiro; Robert M. Sherrell; Andrew R. Bowie; Philip W. Boyd; David K. A. Barnes; Irene R. Schloss; Tanya Marshall; Raquel Flynn; et al. (Frontiers in Marine Science, 2020)

Geographic variation in the whistles of bottlenose dolphins ( Tursiops spp.) in the southwestern Atlantic Ocean - Isabela M. S. Lima; Rihel Venuto; Carolina Menchaca; Lilian S. Hoffmann; Luciano Dalla Rosa; Rodrigo Genoves; Pedro F. Fruet; Andrea Milanelli; Paula Laporta; Bettina Tassino; Stephanie M. Bueno; Thales R. O. Freitas; et al. (Marine Mammal Science, 2020)

A Green Analytical Method for Pre-concentration of Uranium in Water Samples Using Minicolumn with Sugarcane Bagasse - Fábio de S. Dias; Marcos A. Carvalho; Candice N. Carneiro; Rodrigo F. da Silva (Water, Air, & Soil Pollution, 2020)

Detecting Infectious Bursal Disease Using a VP1 Gene-Based RT-qPCR Assay Compared to Standard Methods of Virus Isolation, ELISA, and Histopathology - Cintia H. Okino; Daiane Voss-Rech; Fátima R. F. Jaenisch; Iara M. Trevisol; Raquel Rebelatto; Arlei Coldebella; Marcos A. Z. Mores; Rodrigo Giglioti; Clarissa S. L. Vaz (Current Microbiology, 2020)

Foxn1 and Prkdc genes are important for testis function: evidence from nude and scid adult mice - Carolina FA Oliveira; Nathália LM Lara; Samyra MSN Lacerda; Rodrigo R Resende; Luiz R França; Gleide F Avelar (Cell and Tissue Research, 2020)

Successional trajectory of dung beetle communities in a tropical grassy ecosystem after livestock grazing removal - César M. A. Correa; Lívia D. Audino; Robert Holdbrook; Rodrigo F. Braga; Rosa Menéndez; Julio Louzada (Biodiversity and Conservation, 2020)

Aboveground biomass, transpiration and water use efficiency in eucalypt plantation fertilized with KCl, NaCl and phonolite rock powder - Fábio Henrique S. F. de Toledo; José Leonardo de Moraes Gonçalves; Yesid Alejandro Mariño; Alexandre de Vicente Ferraz; Eric Victor de Oliveira Ferreira; Gabriela Gonçalves Moreira; Rodrigo Hakamada; José Carlos de Arthur Júnior (New Forests, 2020)

Variogram-Based Descriptors for Comparison and Classification of Rock Texture Images - Gonzalo F. Díaz; Julián M. Ortiz; Jorge F. Silva; Rodrigo A. Lobos; Álvaro F. Egaña (Mathematical Geosciences, 2020)

Ecological response to altered rainfall differs across the Neotropics - Diane S. Srivastava; Régis Céréghino; M. Kurtis Trzcinski; A. Andrew M. MacDonald; Nicholas A. C. Marino; Dimaris Acosta Mercado; Céline Leroy; Bruno Corbara; Gustavo Q. Romero; Vinicius F. Farjalla; Ignacio M. Barberis; Olivier Dézerald; et al. (Ecology, 2020)
There is growing recognition that ecosystems may be more impacted by infrequent extreme climatic events than by changes in mean climatic conditions. This has led to calls for experiments that explore the sensitivity of ecosystems over broad ranges of climatic parameter space. However, because such response surface experiments have so far been limited in geographic and biological scope, it is not clear if differences between studies reflect geographic location or the ecosystem component considered. In this study, we manipulated rainfall entering tank bromeliads in seven sites across the Neotropics, and characterized the response of the aquatic ecosystem in terms of invertebrate functional composition, biological stocks (total invertebrate biomass, bacterial density) and ecosystem fluxes (decomposition, carbon, nitrogen). Of these response types, invertebrate functional composition was the most sensitive, even though, in some sites, the species pool had a high proportion of drought‐tolerant families. Total invertebrate biomass was universally insensitive to rainfall change because of statistical averaging of divergent responses between functional groups. The response of invertebrate functional composition to rain differed between geographical locations because (1) the effect of rainfall on bromeliad hydrology differed between sites, and invertebrates directly experience hydrology not rainfall and (2) the taxonomic composition of some functional groups differed between sites, and families differed in their response to bromeliad hydrology. These findings suggest that it will be difficult to establish thresholds of “safe ecosystem functioning” when ecosystem components differ in their sensitivity to climatic variables, and such thresholds may not be broadly applicable over geographic space. In particular, ecological forecast horizons for climate change may be spatially restricted in systems where habitat properties mediate climatic impacts, and those, like the tropics, with high spatial turnover in species composition.

Pacific and Atlantic multidecadal variability relations to the El Niño events and their effects on the South American rainfall - Mary T. Kayano; Rita V. Andreoli; Rodrigo A. F. de Souza (International Journal of Climatology, 2020)
This paper examines the oceanic mean states associated with the Pacific decadal oscillation (PDO) and the Atlantic multidecadal oscillation (AMO) and their relations to the El Niño (EN). The mean states refer to the simultaneous occurrences of warm (W) and cold (C) phases of these oscillations: WAMO/CPDO, CAMO/WPDO and CAMO/CPDO. In general, the sea surface temperature (SST) anomaly patterns of the mean states show a combination of the PDO and AMO related anomaly patterns in the Pacific Ocean, and the strongest AMO‐related anomaly signals in the Atlantic Ocean with almost antisymmetric SST anomaly patterns in the northern and southern extratropical sectors of this Ocean. One of the most important results of this paper concerns the contrasting features between the CAMO/WPDO and the WAMO/CPDO mean states, which are noticeable for the SST, zonal circulation cell and precipitation during the austral autumn. Besides the opposite inter‐basin equatorial Atlantic/eastern equatorial Pacific cells, the CAMO/WPDO and WAMO/CPDO mean states also feature, respectively, a weakened and strengthened Walker cell in the tropical Pacific during the austral autumn. The results here indicate that the inter‐basin east–west cell between the equatorial Atlantic and eastern Pacific contributes to strengthen (weaken) the Walker cell during the austral autumn of the WAMO/CPDO (CAMO/WPDO) mean state. We also found that the mean states alter the EN features. The EN‐related largest positive SST anomalies occur in the central tropical Pacific during the WAMO/CPDO, and in the eastern tropical Pacific during the CAMO/WPDO. The Atlantic and Pacific oceanic mean states play an important role in modulating the EN features and their effects on the South American rainfall. The results presented in this paper might be relevant for climate monitoring and modelling studies.

Fine-scale genetic structure in Lahille’s bottlenose dolphins (Tursiops truncatus gephyreus) is associated with social structure and feeding ecology - Rodrigo Cezar Genoves; Pedro F. Fruet; Silvina Botta; Luciano B. Beheregaray; Luciana M. Möller; Eduardo R. Secchi (Marine Biology, 2020)

Fractional-Flow Theory for Non-Newtonian Surfactant-Alternating-Gas Foam Processes - Rodrigo O. Salazar Castillo; Sterre F. Ter Haar; Christopher G. Ponners; Martijn Bos; William Rossen (Transport in Porous Media, 2020)
Foam can improve sweep efficiency in gas-injection-enhanced oil recovery. Surfactant-alternating-gas (SAG) is a favored method of foam injection. Laboratory data indicate that foam can be non-Newtonian at low water fractional flow f w , and therefore during gas injection in a SAG process. We investigate the implications of this finding for mobility control and injectivity, by extending fractional-flow theory to gas injection in a non-Newtonian SAG process in radial flow. We make most of the standard assumptions of fractional-flow theory (incompressible phases, one-dimensional displacement through a homogeneous reservoir, instantaneous attainment of local equilibrium), excluding Newtonian mobilities. For this initial study, we ignore the effect of changing or non-uniform oil saturation on foam. Non-Newtonian behavior at low f w implies that the limiting water saturation for foam stability varies as superficial velocity decreases with radial distance from the well. We discretize the domain radially and perform Buckley–Leverett analysis on each narrow increment in radius. Solution characteristics move outward with fixed f w . We base the foam model parameters and non-Newtonian behavior on laboratory data in the absence of oil. We compare results to mobility and injectivity determined by conventional simulation, where grid resolution is usually limited. For shear-thinning foam, mobility control improves as the foam front propagates from the well, but injectivity declines somewhat with time. This change in mobility ratio is not that at steady state at fixed water fractional flow in the laboratory, however, because the shock front in a non-Newtonian SAG process does not propagate at fixed fractional flow (though individual characteristics do). Moreover, the shock front is not governed by the conventional condition of tangency to the fractional-flow curve, though it continually approaches this condition. Injectivity benefits from the increased mobility of shear-thinning foam near the well. The foam front, which maintains a constant dimensionless velocity for Newtonian foam, decelerates somewhat with time for shear-thinning foam. For shear-thickening foam, mobility control deteriorates as the foam front advances, though injectivity improves somewhat with time. Overall, however, injectivity suffers from reduced foam mobility at high superficial velocity near the well. The foam front accelerates somewhat with time. Conventional simulators cannot adequately represent these effects, or estimate injectivity accurately, in the absence of extraordinarily fine grid resolution near the injection well.

Visible and near-infrared hyperspectral indices explain more variation in lower-crown leaf nitrogen concentrations in autumn than in summer - Kathryn I. Wheeler; Delphis F. Levia; Rodrigo Vargas (Oecologia, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Correction to: Transmission of the frequency components of the vibrational signal of the glassy-winged sharpshooter, Homalodisca vitripennis, within and between grapevines - Shira D. Gordon; Benjamin Tiller; James F. C. Windmill; Rodrigo Krugner; Peter M. Narins (Journal of Comparative Physiology A, 2019)
Unfortunately, Fig. 3 was incorrectly published in the original publication. The correct version of Fig. 3 is updated here.

Colletotrichum acutatum M11 can suppress the defence response in strawberry plants - Rodrigo H. Tomas-Grau; Pia Di Peto; Nadia R. Chalfoun; Carlos F. Grellet-Bournonville; Gustavo G. Martos; Mario Debes; Marta E. Arias; Juan C. Díaz-Ricci (Planta, 2019)

Terrestrial Behavior in Titi Monkeys (Callicebus, Cheracebus, and Plecturocebus): Potential Correlates, Patterns, and Differences between Genera - João Pedro Souza-Alves; Italo Mourthe; Renato R. Hilário; Júlio César Bicca-Marques; Jennifer Rehg; Carla C. Gestich; Adriana C. Acero-Murcia; Patrice Adret; Rolando Aquino; Mélissa Berthet; Mark Bowler; Armando M. Calouro; et al. (International Journal of Primatology, 2019)

Identification and characterization of atypical enteropathogenic and Shiga toxin-producing Escherichia coli isolated from ground beef and poultry breast purchased in Botucatu, Brazil - Rodrigo H. S. Tanabe; Melissa A. Vieira; Noelle A. B. Mariano; Regiane C. B. Dias; Rafael Ventin da Silva; Caroline M. Castro; Luis F. dos Santos; Carlos H. Camargo; Ricardo S. Yamatogi; Vera L. M. Rall; Rodrigo T. Hernandes (Brazilian Journal of Microbiology, 2019)

Transmission of the frequency components of the vibrational signal of the glassy-winged sharpshooter, Homalodisca vitripennis, within and between grapevines - Shira D. Gordon; Benjamin Tiller; James F. C. Windmill; Rodrigo Krugner; Peter M. Narins (Journal of Comparative Physiology A, 2019)

Scaling issues of neutral theory reveal violations of ecological equivalence for dominant Amazonian tree species - Edwin Pos; Juan Ernesto Guevara; Jean‐François Molino; Daniel Sabatier; Olaf S. Bánki; Nigel C.A. Pitman; Hugo F. Mogollón; Roosevelt García‐Villacorta; David Neill; Oliver L. Phillips; Carlos Cerón; Marcos Ríos Paredes; et al. (Ecology Letters, 2019)
Neutral models are often used as null models, testing the relative importance of niche versus neutral processes in shaping diversity. Most versions, however, focus only on regional scale predictions and neglect local level contributions. Recently, a new formulation of spatial neutral theory was published showing an incompatibility between regional and local scale fits where especially the number of rare species was dramatically under‐predicted. Using a forward in time semi‐spatially explicit neutral model and a unique large‐scale Amazonian tree inventory data set, we show that neutral theory not only underestimates the number of rare species but also fails in predicting the excessive dominance of species on both regional and local levels. We show that although there are clear relationships between species composition, spatial and environmental distances, there is also a clear differentiation between species able to attain dominance with and without restriction to specific habitats. We conclude therefore that the apparent dominance of these species is real, and that their excessive abundance can be attributed to fitness differences in different ways, a clear violation of the ecological equivalence assumption of neutral theory.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Drought-Induced Modifications on the Outer Part of the Root (OPR) and Root Endodermis of Selected Rice Genotypes - Cris Q. Cortaga; Rodrigo F. Sebidos (Journal of Crop Science and Biotechnology, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Guanosine Attenuates Behavioral Deficits After Traumatic Brain Injury by Modulation of Adenosinergic Receptors - Fernando Dobrachinski; Rogério R. Gerbatin; Gláubia Sartori; Ronaldo M. Golombieski; Alfredo Antoniazzi; Cristina W. Nogueira; Luiz F. Royes; Michele R. Fighera; Lisiane O. Porciúncula; Rodrigo A. Cunha; Félix A. A. Soares (Molecular Neurobiology, 2019)

Heterologous expression of nifA or nodD genes improves chickpea-Mesorhizobium symbiotic performance - José Rodrigo da-Silva; Esther Menéndez; Fernando Eliziário; Pedro F. Mateos; Ana Alexandre; Solange Oliveira (Plant and Soil, 2019)

Use of mucus as a non‐invasive sampling method for DNA barcoding of stingrays and skates (batoid elasmobranchs) - Rodrigo R. Domingues; Domingos Garrone‐Neto; Alexandre W. S. Hilsdorf; Otto B. F. Gadig (Journal of Fish Biology, 2019)
In this study we tested the use of mucus from five species of Neotropical marine batoid elasmobranchs to extract genomic DNA for barcoding and phylogenetic analysis. The DNA from all individuals sampled was successfully amplified and sequenced for molecular barcode, allowing 99–100% accuracy to the species level. This method proved to provide reliable and good‐quality DNA for barcoding and phylogenetic analysis of Neotropical elasmobranchs, through rapid handling and with low disturbance to animals.

Conserving adaptive potential: lessons from Tasmanian devils and their transmissible cancer - Paul A. Hohenlohe; Hamish I. McCallum; Menna E. Jones; Matthew F. Lawrance; Rodrigo K. Hamede; Andrew Storfer (Conservation Genetics, 2019)

Mild Exercise Differently Affects Proteostasis and Oxidative Stress on Motor Areas During Neurodegeneration: A Comparative Study of Three Treadmill Running Protocols - Karla P. Melo; Carolliny M. Silva; Michael F. Almeida; Rodrigo S. Chaves; Tania Marcourakis; Sandra M. Cardoso; Marilene Demasi; Luis E. S. Netto; Merari F. R. Ferrari (Neurotoxicity Research, 2019)

Patterns of taxonomic and functional diversity of dung beetles in a human-modified variegated landscape in Brazilian Cerrado - César M. A. Correa; Rodrigo F. Braga; Anderson Puker; Vanesca Korasaki (Journal of Insect Conservation, 2019)

Effects of dietary supplementation of Gracilaria sp. extracts on fillet quality, oxidative stress, and immune responses in European seabass (Dicentrarchus labrax) - Maria J. Peixoto; Leonardo Magnoni; José F. M. Gonçalves; Robert H. Twijnstra; Anake Kijjoa; Rui Pereira; Arjan P. Palstra; Rodrigo O. A. Ozório (Journal of Applied Phycology, 2019)

Summer phyto- and bacterioplankton communities during low and high productivity scenarios in the Western Antarctic Peninsula - Sebastián Fuentes; José Ignacio Arroyo; Susana Rodríguez-Marconi; Italo Masotti; Tomás Alarcón-Schumacher; Martin F. Polz; Nicole Trefault; Rodrigo De la Iglesia; Beatriz Díez (Polar Biology, 2019)

Coherent variability between seasonal temperatures and rainfalls in the Iberian Peninsula, 1951–2016 - F. S. Rodrigo (Theoretical and Applied Climatology, 2019)

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

The Brazilian food security scale for indigenous Guarani households: Development and validation - Ana Maria Segall-Corrêa; Leticia Marín-Leon; Marta Maria do Amaral Azevedo; Maria Beatriz R. Ferreira; Deoclécio Rocco Gruppi; Daniele F. M. Camargo; Rodrigo Pinheiro de Toledo Vianna; Rafael Pérez-Escamilla (Food Security, 2018)

Effects of hybridization on sea turtle fitness - Luciano S. Soares; Karen A. Bjorndal; Alan B. Bolten; Maria A. G. dei Marcovaldi; Pedro B. Luz; Rodrigo Machado; Rachel Lo; Stuart F. McDaniel; Adam C. Payton; Thomas B. Waltzek; Marta L. Wayne (Conservation Genetics, 2018)

Analysis of potential contamination factors in musculoskeletal tissues - Guilherme G. Naves; André F. Silva; Uri Antebi; Priscila C. Cristovam; Emerson K. Honda; Rodrigo P. Guimarães (Cell and Tissue Banking, 2018)

Condition analysis of the Brazilian sharpnose shark Rhizoprionodon lalandii : evidence of maternal investment for initial post‐natal life - Jessica T. Corsso; Otto B. F. Gadig; Rodrigo R. P. Barreto; Fabio S. Motta (Journal of Fish Biology, 2018)
The present study analysed the condition factor ( K ) and the hepato‐somatic index ( I H ) of the Brazilian sharpnose shark Rhizoprionodon lalandii during its entire life cycle. Discontinuity of liver growth was observed after sexual maturity. High condition values were recorded in the length classes of 300–350 mm (neonates), when the livers represented about 8% of total mass, decreasing until the length classes of 400–450 and 450–500 mm in females and males, respectively. Seasonal analysis exhibited low I H values in the summer, while for K , low values were in spring, indicating greater investment for body growth during spring and for gonad maturation in summer. Such findings indicate that this small coastal shark species accumulates reserve substances in the liver that will be used during reproduction. The decline in I H values in juveniles suggests that reserves provisioned by the mother to the neonate liver can be used in the first months of life.

Observed Changes in Daily Precipitation Extremes at Annual Timescale Over the Eastern Mediterranean During 1961–2012 - S. Mathbout; J. A. Lopez-Bustins; D. Royé; J. Martin-Vide; J. Bech; F. S. Rodrigo (Pure and Applied Geophysics, 2018)

Nesting patterns among Neotropical species assemblages: can reserves in urban areas be failing to protect anurans? - Ricardo Lourenço-de-Moraes; Leo R. Malagoli; Vinicius Guerra; Rodrigo B. Ferreira; Igor de Paiva Affonso; Célio F. B. Haddad; Ricardo J. Sawaya; Rogério P. Bastos (Urban Ecosystems, 2018)

Mineralization of humic acids (HAs) by a solar photo-Fenton reaction mediated by ferrioxalate complexes: commercial HAs vs extracted from leachates - Ana P. F. Santos; Bianca M. Souza; Tânia F. C. V. Silva; Rodrigo P. Cavalcante; Silvio C. Oliveira; Amílcar Machulek; Rui A. R. Boaventura; Vítor J. P. Vilar (Environmental Science and Pollution Research, 2018)

Increased active phase atrial contraction is related to marathon runner performance - Luigi Gabrielli; Sebastián Herrera; Felipe Contreras-Briceño; Julián Vega; María Paz Ocaranza; Fernando Yáñez; Rodrigo Fernández; Rodrigo Saavedra; Marta Sitges; Lorena García; Mario Chiong; Sergio Lavandero; et al. (European Journal of Applied Physiology, 2018)

Dynamics of spontaneous activity in random networks with multiple neuron subtypes and synaptic noise - Rodrigo F. O. Pena; Michael A. Zaks; Antonio C. Roque (Journal of Computational Neuroscience, 2018)

Jaguar movement database: a GPS‐based movement dataset of an apex predator in the Neotropics - Ronaldo G. Morato; Jeffrey J. Thompson; Agustin Paviolo; Jesus A. de La Torre; Fernando Lima; Roy T. McBride; Rogerio C. Paula; Laury Cullen; Leandro Silveira; Daniel L. Z. Kantek; Emiliano E. Ramalho; Louise Maranhão; et al. (Ecology, 2018)
The field of movement ecology has rapidly grown during the last decade, with important advancements in tracking devices and analytical tools that have provided unprecedented insights into where, when, and why species move across a landscape. Although there has been an increasing emphasis on making animal movement data publicly available, there has also been a conspicuous dearth in the availability of such data on large carnivores. Globally, large predators are of conservation concern. However, due to their secretive behavior and low densities, obtaining movement data on apex predators is expensive and logistically challenging. Consequently, the relatively small sample sizes typical of large carnivore movement studies may limit insights into the ecology and behavior of these elusive predators. The aim of this initiative is to make available to the conservation‐scientific community a dataset of 134,690 locations of jaguars ( Panthera onca ) collected from 117 individuals (54 males and 63 females) tracked by GPS technology. Individual jaguars were monitored in five different range countries representing a large portion of the species’ distribution. This dataset may be used to answer a variety of ecological questions including but not limited to: improved models of connectivity from local to continental scales; the use of natural or human‐modified landscapes by jaguars; movement behavior of jaguars in regions not represented in this dataset; intraspecific interactions; and predator‐prey interactions. In making our dataset publicly available, we hope to motivate other research groups to do the same in the near future. Specifically, we aim to help inform a better understanding of jaguar movement ecology with applications towards effective decision making and maximizing long‐term conservation efforts for this ecologically important species. There are no costs, copyright, or proprietary restrictions associated with this data set. When using this data set, please cite this article to recognize the effort involved in gathering and collating the data and the willingness of the authors to make it publicly available.

Critical review of elementary flows in LCA data - Ashley Edelen; Wesley W. Ingwersen; Cristina Rodríguez; Rodrigo A. F. Alvarenga; Artur Ribeiro de Almeida; Gregor Wernet (The International Journal of Life Cycle Assessment, 2018)

Faster photosynthetic induction in tobacco by expressing cyanobacterial flavodiiron proteins in chloroplasts - Rodrigo Gómez; Néstor Carrillo; María P. Morelli; Suresh Tula; Fahimeh Shahinnia; Mohammad-Reza Hajirezaei; Anabella F. Lodeyro (Photosynthesis Research, 2018)

Purification of arsenic-contaminated water with K-jarosite filters - Rodrigo C. Hott; Luiz F. O. Maia; Mayra S. Santos; Márcia C. Faria; Luiz C. A. Oliveira; Márcio C. Pereira; Cleide A. Bomfeti; Jairo L. Rodrigues (Environmental Science and Pollution Research, 2018)

Bat and bee pollination in Psittacanthus mistletoes, a genus regarded as exclusively hummingbird‐pollinated - Rodrigo F. Fadini; Erich Fischer; Sônia J. Castro; Andréa C. Araujo; Juan Francisco Ornelas; Paulo R. de Souza (Ecology, 2018)

Effects of the Pleistocene on the mitochondrial population genetic structure and demographic history of the silky shark (Carcharhinus falciformis) in the western Atlantic Ocean - Rodrigo R. Domingues; Alexandre W. S. Hilsdorf; Mahmood M. Shivji; Fabio V. H. Hazin; Otto B. F. Gadig (Reviews in Fish Biology and Fisheries, 2018)

Ecological role and historical trends of large pelagic predators in a subtropical marine ecosystem of the South Atlantic - Hugo Bornatowski; Ronaldo Angelini; Marta Coll; Rodrigo R. P. Barreto; Alberto F. Amorim (Reviews in Fish Biology and Fisheries, 2018)

In-column immobilization of Cs-saturated crystalline silicotitanates using phenolic resins - Rodrigo F. Curi; Vittorio Luca (Environmental Science and Pollution Research, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Assessment of sexual maturity in captive Amazonian manatees ( Trichechus inunguis ) - Rodrigo S. Amaral; Vera M. F. Da Silva; Stella Maris lazzarini; José Anselmo D'affonsêca Neto; Daniella Ribeiro; Fernando C. W. Rosas (Marine Mammal Science, 2018)

Fibroblast contributes for osteoblastic phenotype in a MAPK-ERK and sonic hedgehog signaling-independent manner - Celio J. da Costa Fernandes; Augusto Santana do Nascimento; Rodrigo A. da Silva; Willian F. Zambuzzi (Molecular and Cellular Biochemistry, 2017)

MicroRNAs in Sertoli cells: implications for spermatogenesis and fertility - Marcela S. Procópio; Gleide F. de Avelar; Guilherme M. J. Costa; Samyra M. S. N. Lacerda; Rodrigo R. Resende; Luiz R. de França (Cell and Tissue Research, 2017)

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

A new genus of schizomids (Arachnida: Schizomida: Hubbardiidae) from Mexico, with notes on its systematics - Rodrigo Monjaraz-Ruedas; Oscar F. Francke (Systematics and Biodiversity, 2017)

Automatic detection of P- and S-wave arrival times: new strategies based on the modified fractal method and basic matching pursuit - Rodrigo Chi-Durán; Diana Comte; Marcos Díaz; Jorge F. Silva (Journal of Seismology, 2017)

Removal of the emerging contaminant bisphenol A by an ureasil–PEO hybrid membrane: experimental study and molecular dynamic simulation - Lilian K. de Oliveira; André L. A. Moura; Valdir Barbosa; Renato L. T. Parreira; Rodrigo S. Banegas; Giovanni F. Caramori; Katia J. Ciuffi; Eduardo F. Molina (Environmental Science and Pollution Research, 2017)

Modeling abundance, growth, and health of the solitary coral Scolymia wellsi (Mussidae) in turbid SW Atlantic coral reefs - Ericka O. C. Coni; Camilo M. Ferreira; Pedro M. Meirelles; Rafael Menezes; Erika F. C. Santana; Ana Paula B. Moreira; Gilberto M. Amado-Filho; Beatrice P. Ferreira; Guilherme H. Pereira-Filho; Fabiano L. Thompson; Rodrigo L. Moura; Ronaldo B. Francini-Filho (Marine Biology, 2017)

Investigating essential and toxic elements in Antarctic macroalgae using a green analytical method - Rochele S. Picoloto; Rodrigo M. Pereira; Vanize C. Costa; Carla A. Hartwig; Claudio M. P. Pereira; Pio Colepicolo; Fabio A. Duarte; Marcia F. Mesko (Journal of Applied Phycology, 2017)

Labeling of adipose-derived stem cells with quantum dots provides stable and long-term fluorescent signal for ex vivo cell tracking - Clautina R. M. Costa; Matheus L. T. Feitosa; Dayseanny O. Bezerra; Yulla K. P. Carvalho; Rodrigo F. G. Olivindo; Pablo B. Fernando; Gustavo C. Silva; Mirna L. G. Silva; Carlos E. Ambrósio; Airton M. Conde Júnior; Napoleão M. Argolo Neto; Laís M. Costa Silva; et al. (In Vitro Cellular & Developmental Biology - Animal, 2017)

Complete genome sequence of a variant of maize-associated totivirus from Ecuador - Robert A. Alvarez-Quinto; Rodrigo F. Espinoza-Lozano; Carlos A. Mora-Pinargote; Diego F. Quito-Avila (Archives of Virology, 2017)

Topological redundancy and ‘small‐world’ patterns in a food web in a subtropical ecosystem of Brazil - Hugo Bornatowski; Rodrigo Barreto; Andrés F. Navia; Alberto Ferreira de Amorim (Marine Ecology, 2017)
According to graph theory, the frequency distribution of trophic interactions within a food web has deep structural implications, as it can highlight the presence of patterns associated with the web and indicate whether the properties of the web are independent of its size. A hypothesis is that ‘small‐world’ food webs are sensitive to the loss of species with the highest values. Therefore, the present work aimed to evaluate the degree to which a subtropical food web in Southern Brazil displays small‐world patterns and their resistance. As part of the assessment, we evaluated the topological redundancy values of species in the food web and then we simulated the exclusion of these species (such as sharks and sea birds), and also the exclusion of high centrality species (such as squids Loligo sp., portunid swimming crabs and the cutlassfish Trichiurus lepturus ). The food web showed a ‘broad‐scale’ distribution of connections by node, and a small‐world pattern. As expected, a simplification of the network was observed after elimination of some species with high centrality. However, the food web was resistant to the loss of species with low topological redundancy, probably because these species occupy a high trophic level and do not participate in lots of routes within the food web. We highlight however, the importance of the application of multiple analyses to evaluate the importance of components in food webs, and fisheries management plans should consider both species of high centrality values and species with low topological redundancy.

Arterial pulse wave propagation velocity in healthy dogs by pulse wave Doppler ultrasound - Rodrigo B. Nogueira; Lucas A. Pereira; Alice F. Basso; Ingrid S. da Fonseca; Lorena A. Alves (Veterinary Research Communications, 2017)

Reaching the canopy on the ground: incidence of infection and host-use by mistletoes (Loranthaceae and Viscaceae) on trees felled for timber in Amazonian rainforests - Jéssica Lira; Claudenir S. Caires; Rodrigo F. Fadini (Plant Ecology, 2017)

Estimation of genetic parameters for longevity considering the cow’s age at last calving - Sabrina L. Caetano; Guilherme J. M. Rosa; Rodrigo P. Savegnago; Salvador B. Ramos; Priscila A. Bernardes; Luiz A. F. Bezerra; Raysildo B. Lôbo; Claudia C. P. de Paz; Danísio Prado Munari (Journal of Applied Genetics, 2017)

Central Nervous System and Vertebrae Development in Horses: a Chronological Study with Differential Temporal Expression of Nestin and GFAP - Nathia N. Rigoglio; Rodrigo S. N. Barreto; Phelipe O. Favaron; Júlio C. F. Jacob; Lawrence C. Smith; Melba O. Gastal; Eduardo L. Gastal; Maria Angélica Miglino (Journal of Molecular Neuroscience, 2017)

Selenium Levels in the Whole Blood of Children and Teenagers from Two Riparian Communities at the Madeira River Basin in the Western Brazilian Amazon - Claudia M. Vega; José M. Godoy; Paulo R. G. Barrocas; Rodrigo A. Gonçalves; Beatriz F. A. De Oliveira; Ludmilla V. Jacobson; Dennys S. Mourão; Sandra S. Hacon (Biological Trace Element Research, 2017)

The carnivore guild circa 1.98 million years: biodiversity and implications for the palaeoenvironment at Malapa, South Africa - Brian F. Kuhn; Adam Hartstone-Rose; Rodrigo S. Lacruz; Andy I. R. Herries; Lars Werdelin; Marion K. Bamford; Lee R. Berger (Palaeobiodiversity and Palaeoenvironments, 2016)

Life history parameters and feeding preference of the green lacewing Ceraeochrysa cubana fed with virus-free and potato leafroll virus-infected Myzus persicae - Rodrigo L. de Oliveira; Valéria F. Moscardini; Pablo C. Gontijo; Rafaella R. Sâmia; Rosangela C. Marucci; Flor Budia; Geraldo A. Carvalho (BioControl, 2016)

Monitoring Methodology of Interventions for Riverbanks Stabilization: Assessment of Technical Solutions Performance - António Pinto; L. F. Sanches Fernandes; Rodrigo Maia (Water Resources Management, 2016)

Development of two artificial neural network models to support the diagnosis of pulmonary tuberculosis in hospitalized patients in Rio de Janeiro, Brazil - Fábio S. Aguiar; Rodrigo C. Torres; João V. F. Pinto; Afrânio L. Kritski; José M. Seixas; Fernanda C. Q. Mello (Medical & Biological Engineering & Computing, 2016)

Adsorption of arsenic from water and its recovery as a highly active photocatalyst - Rodrigo C. Hott; Thaina G. Andrade; Mayra S. Santos; Anne C. F. Lima; Márcia C. S. Faria; Cleide A. Bomfeti; Fernando Barbosa; Luiz F. O. Maia; Luiz C. A. Oliveira; Márcio C. Pereira; Jairo L. Rodrigues (Environmental Science and Pollution Research, 2016)

Analysis and Classification of Natural Rock Textures based on New Transform-based Features - Rodrigo Lobos; Jorge F. Silva; Julián M. Ortiz; Gonzalo Díaz; Alvaro Egaña (Mathematical Geosciences, 2016)

Scale-up of electrolytic and photoelectrolytic processes for water reclaiming: a preliminary study - María J. Martín de Vidales; Salvador Cotillas; José F. Perez-Serrano; Javier Llanos; Cristina Sáez; Pablo Cañizares; Manuel A. Rodrigo (Environmental Science and Pollution Research, 2016)

A further analysis of the tropical Atlantic SST modes and their relations to north‐eastern Brazil rainfall during different phases of Atlantic Multidecadal Oscillation - Mary T. Kayano; Vinicius B. Capistrano; Rita V. Andreoli; Rodrigo A. F. de Souza (International Journal of Climatology, 2016)
This paper examines the climate variability modes in the South American/Atlantic sector accompanying dry and wet years over north‐eastern Brazil ( NEB ) in which the tropical Pacific and Atlantic oceanic‐atmospheric conditions usually associated, respectively, with dryness and wetness are absent. The analyses are for several variables and take into account the warm and cold Atlantic Multidecadal Oscillation ( AMO ) phases ( WAMO and CAMO ). Four cases are analysed: DRY‐WAMO , DRY‐CAMO , WET‐WAMO and WET‐CAMO . The main difference in the sea surface temperature ( SST ) anomaly patterns in the tropics between the AMO phases responsible for the differences in the precipitation anomaly patterns is the differential longitude positioning of the warming or cooling of the surface waters in the equatorial Atlantic. In consequence, the anomalous Atlantic Hadley and Walker circulations also show differences between the AMO phases, which justify the observed precipitation anomalies over tropical South America for the analysed cases. The strong anomalous Atlantic Hadley cell determines the dipolar structure of the precipitation anomalies between NEB and northern South America for the DRY‐WAMO and WET‐WAMO cases. The strong anomalous Atlantic Walker cell defines the dryness over NEB for the DRY‐CAMO , and both the strong anomalous Atlantic Hadley and Walker cells act together to yield an anomalous dry condition over NEB and wet condition over northern South America. Therefore, the results here provided clear indications that for climate monitoring and forecasting tasks, the AMO phases should be considered. These are new aspects of the tropical Atlantic variability that might be useful for climate monitoring purposes.

Multitaxon activity profiling reveals differential microbial response to reduced seawater pH and oil pollution - Francisco J. R. C. Coelho; Daniel F. R. Cleary; Rodrigo Costa; Marina Ferreira; Ana R. M. Polónia; Artur M. S. Silva; Mário M. Q. Simões; Vanessa Oliveira; Newton C. M. Gomes (Molecular Ecology, 2016)
There is growing concern that predicted changes to global ocean chemistry will interact with anthropogenic pollution to significantly alter marine microbial composition and function. However, knowledge of the compounding effects of climate change stressors and anthropogenic pollution is limited. Here, we used 16S and 18S rRNA ( cDNA )‐based activity profiling to investigate the differential responses of selected microbial taxa to ocean acidification and oil hydrocarbon contamination under controlled laboratory conditions. Our results revealed that a lower relative abundance of sulphate‐reducing bacteria ( Desulfosarcina / Desulfococcus clade) due to an adverse effect of seawater acidification and oil hydrocarbon contamination (reduced pH –oil treatment) may be coupled to changes in sediment archaeal communities. In particular, we observed a pronounced compositional shift and marked reduction in the prevalence of otherwise abundant operational taxonomic units ( OTU s) belonging to the archaeal Marine Benthic Group B and Marine Hydrothermal Vent Group ( MHVG ) in the reduced pH –oil treatment. Conversely, the abundance of several putative hydrocarbonoclastic fungal OTU s was higher in the reduced pH –oil treatment. Sediment hydrocarbon profiling, furthermore, revealed higher concentrations of several alkanes in the reduced pH –oil treatment, corroborating the functional implications of the structural changes to microbial community composition. Collectively, our results advance the understanding of the response of a complex microbial community to the interaction between reduced pH and anthropogenic pollution. In future acidified marine environments, oil hydrocarbon contamination may alter the typical mixotrophic and k‐/r‐strategist composition of surface sediment microbiomes towards a more heterotrophic state with lower doubling rates, thereby impairing the ability of the ecosystem to recover from acute oil contamination events.

Spatio-temporal trends of precipitation, its aggressiveness and concentration, along the Pacific coast of South America (36–49°S) - Rodrigo Valdés-Pineda; Roberto Pizarro; Juan B. Valdés; Jorge F. Carrasco; Pablo García-Chevesich; Claudio Olivares (Hydrological Sciences Journal, 2016)

Cytokines profile and its correlation with endothelial damage and oxidative stress in patients with type 1 diabetes mellitus and nephropathy - Rodrigo M. C. Pestana; Caroline P. Domingueti; Rita C. F. Duarte; Rodrigo B. Fóscolo; Janice S. Reis; Ana Maria S. Rodrigues; Laís B. Martins; Lirlândia P. Sousa; Daniela P. Lage; Cláudia N. Ferreira; Adaliene V. M. Ferreira; Ana P. Fernandes; et al. (Immunologic Research, 2016)

“Cytochrome c oxidase I DNA sequence of Camponotus ants with different nesting strategies is a tool for distinguishing between morphologically similar species” - Manuela O. F. Ramalho; Rodrigo M. Santos; Tae T. Fernandes; Maria Santina C. Morini; Odair C. Bueno (Genetica, 2016)

New compositions of the materials from cellulose industry wastes - Vsévolod Mymrin; Daniel F. Cusma; André Nagalli; Andréia Pichorim; Rodrigo E. Catai; Urivald Pawlowsky (Clean Technologies and Environmental Policy, 2016)

Biological and molecular characterization of a highly divergent johnsongrass mosaic virus isolate from Pennisetum purpureum - Karina N. Silva; Fernando L. Melo; Anelise F. Orílio; Tatsuya Nagata; Marilia S. Silva; Celso D. Fernandes; Rodrigo R. Fragoso; Suelen N. Dessaune; Renato O. Resende (Archives of Virology, 2016)

Analysis of spatio‐temporal changes in annual and seasonal precipitation variability in South America‐Chile and related ocean–atmosphere circulation patterns - Rodrigo Valdés‐Pineda; Juan B. Valdés; Henry F. Diaz; Roberto Pizarro‐Tapia (International Journal of Climatology, 2016)
Establishing relationships between coupled ocean–atmospheric patterns and precipitation accumulation is important to describe and predict spatio‐temporal variability on annual or seasonal scales, and also to evaluate how this variability is influenced by global warming. The objective of this study was to examine the leading modes of interannual and seasonal (summer, autumn, winter, and spring) precipitation variability in South America‐Chile, and their significant relationship to seasonally aggregated gridded data and climatic indices. Applying exhaustive data quality control measures to data from 238 rain gauges with different lengths of records between 1893 and 2013, a new data set was created with the objective of obtaining reliable records for further analysis. A comprehensive analysis through empirical orthogonal functions ( EOF ) allowed for determination of the leading modes of annual and seasonal precipitation and their main spatial patterns for the whole country. The percentage of explained variance in the relationship between seasonally aggregated indices and the leading modes of precipitation confirmed that most of the interannual and winter precipitation variability in Chile is linked to the seasonal aggregation of El Nino Southern Oscillation ( ENSO ). The leading modes of summer, autumn, and spring precipitation were mostly linked to seasonal aggregations of the Madden and Julian Oscillation ( MJO ), and the Antarctic Oscillation ( AAO ).

Inhibition of cell proliferation, invasion and migration by the cardenolides digitoxigenin monodigitoxoside and convallatoxin in human lung cancer cell line - Naira F. Z. Schneider; Fabiana C. Geller; Lara Persich; Lucas L. Marostica; Rodrigo M. Pádua; Wolfgang Kreis; Fernão C. Braga; Cláudia M. O. Simões (Natural Product Research, 2016)

Diets supplemented with seaweed affect metabolic rate, innate immune, and antioxidant responses, but not individual growth rate in European seabass (Dicentrarchus labrax) - Maria J. Peixoto; Jon C. Svendsen; Hans Malte; Luis F. Pereira; Pedro Carvalho; Rui Pereira; José F. M. Gonçalves; Rodrigo O. A. Ozório (Journal of Applied Phycology, 2016)

Prey capture behavior in three Neotropical armored harvestmen (Arachnida, Opiliones) - Thaiany M. Costa; Norton F. S. Silva; Rodrigo H. Willemart (Journal of Ethology, 2016)

Effects of treatment with the anti-parasitic drug diminazene aceturate on antioxidant enzymes in rat liver and kidney - Matheus D. Baldissera; Ricardo A. Gonçalves; Michele R. Sagrillo; Thirssa H. Grando; Camila S. Ritter; Fabielly S. Grotto; Gerson F. Brum; Sônia C. A. da Luz; Sergio O. Silveira; Viviane P. Fausto; Aline A. Boligon; Rodrigo A. Vaucher; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

A randomized, placebo-controlled pilot trial of the delta opioid receptor agonist AZD2327 in anxious depression - Erica M. Richards; Daniel C. Mathews; David A. Luckenbaugh; Dawn F. Ionescu; Rodrigo Machado-Vieira; Mark J. Niciu; Wallace C. Duncan; Neal M. Nolan; Jose A. Franco-Chaves; Thomas Hudzik; Carla Maciag; Shuang Li; et al. (Psychopharmacology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Field Survey of the 2015 Chile Tsunami with Emphasis on Coastal Wetland and Conservation Areas - Manuel Contreras-López; Patricio Winckler; Ignacio Sepúlveda; Adolfo Andaur-Álvarez; Fernanda Cortés-Molina; Camila J. Guerrero; Cyntia E. Mizobe; Felipe Igualt; Wolfgang Breuer; José F. Beyá; Hernán Vergara; Rodrigo Figueroa-Sterquel (Pure and Applied Geophysics, 2016)

Silencing of Gonad-Inhibiting Hormone Transcripts in Litopenaeus vannamei Females by use of the RNA Interference Technology - Rubens G. Feijó; André L. Braga; Carlos F. C. Lanes; Márcio A. Figueiredo; Luis A. Romano; Marta C. Klosterhoff; Luis E. M. Nery; Rodrigo Maggioni; Wilson Wasielesky; Luis F. Marins (Marine Biotechnology, 2016)

Drivers of phytoplankton diversity in Patagonian and Antarctic lakes across a latitudinal gradient (2150 km): the importance of spatial and environmental factors - Irina Izaguirre; Juan F. Saad; M. Romina Schiaffino; Alicia Vinocur; Guillermo Tell; María Laura Sánchez; Luz Allende; Rodrigo Sinistro (Hydrobiologia, 2016)

Wood density, but not leaf hydraulic architecture, is associated with drought tolerance in clones of Coffea canephora - Paulo E. Menezes-Silva; Paulo C. Cavatte; Samuel C. V. Martins; Josimar V. Reis; Lucas F. Pereira; Rodrigo T. Ávila; Andréa L. Almeida; Marília C. Ventrella; Fábio M. DaMatta (Trees, 2015)

Bioenergy and Biodiversity: Key Lessons from the Pan American Region - Keith L. Kline; Fernanda Silva Martinelli; Audrey L. Mayer; Rodrigo Medeiros; Camila Ortolan F. Oliveira; Gerd Sparovek; Arnaldo Walter; Lisa A. Venier (Environmental Management, 2015)

A DNA tool for the identification of heavily exploited Atlantic billfishes - Rodrigo R. Domingues; Gabriel Okuda; Andrea M. Bernard; Alberto F. Amorim; Juliana De Biasi; Alexandre W. S. Hilsdorf (Conservation Genetics Resources, 2015)

Speciation with gene flow in whiptail lizards from a Neotropical xeric biome - Eliana F. Oliveira; Marcelo Gehara; Vinícius A. São‐Pedro; Xin Chen; Edward A. Myers; Frank T. Burbrink; Daniel O. Mesquita; Adrian A. Garda; Guarino R. Colli; Miguel T. Rodrigues; Federico J. Arias; Hussam Zaher; et al. (Molecular Ecology, 2015)
Two main hypotheses have been proposed to explain the diversification of the Caatinga biota. The riverine barrier hypothesis ( RBH ) claims that the São Francisco River ( SFR ) is a major biogeographic barrier to gene flow. The Pleistocene climatic fluctuation hypothesis ( PCH ) states that gene flow, geographic genetic structure and demographic signatures on endemic Caatinga taxa were influenced by Quaternary climate fluctuation cycles. Herein, we analyse genetic diversity and structure, phylogeographic history, and diversification of a widespread Caatinga lizard ( Cnemidophorus ocellifer ) based on large geographical sampling for multiple loci to test the predictions derived from the RBH and PCH . We inferred two well‐delimited lineages (Northeast and Southwest) that have diverged along the Cerrado–Caatinga border during the Mid‐Late Miocene (6–14 Ma) despite the presence of gene flow. We reject both major hypotheses proposed to explain diversification in the Caatinga. Surprisingly, our results revealed a striking complex diversification pattern where the Northeast lineage originated as a founder effect from a few individuals located along the edge of the Southwest lineage that eventually expanded throughout the Caatinga. The Southwest lineage is more diverse, older and associated with the Cerrado–Caatinga boundaries. Finally, we suggest that C. ocellifer from the Caatinga is composed of two distinct species. Our data support speciation in the presence of gene flow and highlight the role of environmental gradients in the diversification process.

Environmentally Realistic Doses of Cadmium as a Possible Etiologic Agent for Idiopathic Pathologies - Rodrigo Leite; Eduardo F. Peloso; Fernanda R. Gadelha; Mary A. D. Dolder (Biological Trace Element Research, 2015)

Environmental Degradation in a Eutrophic Shallow Lake is not Simply Due to Abundance of Non-native Cyprinus carpio - Juan P. Ramírez-Herrejón; Norman Mercado-Silva; Eduardo F. Balart; Rodrigo Moncayo-Estrada; Valentín Mar-Silva; Javier Caraveo-Patiño (Environmental Management, 2015)

On the covariability of seasonal temperature and precipitation in Spain, 1956–2005 - F. S. Rodrigo (International Journal of Climatology, 2015)
In this work, the covariability between the standardized anomalies of seasonal mean temperature and total rainfall in four Spanish sites during the periods 1956–1980 and 1981–2005 is analysed. Original data are standardized using the reference period 1971–2000. Using the hypothesis of bivariate normal distribution, the climate states corresponding to each period may be characterized by the confidence ellipses at the 95% confidence level. Movements of the ellipses indicate changes in the vector mean (translations), changes in the sign of the correlation coefficient (rotations) and in the variance–covariance matrix (deformations). Significance of these changes is assessed by Hotelling's, difference between correlation coefficients, and Barlett's tests, respectively. Results indicate a general translation towards higher (lower) mean temperature (precipitation) in the second period. Significant changes in the variance–covariance matrix did not show a clear pattern. Future developments of this methodology are outlined.

Disentangling the controversial identity of the halfbeak stock (Hemiramphus brasiliensis and H. balao) from northeastern Brazil using multilocus DNA markers - Rodrigo A. Torres; Filipe Alberto dos Santos; Flávia R. S. Andrade; Guilherme F. Gondolo; Rosangela P. R. Lessa (Reviews in Fish Biology and Fisheries, 2015)

Marker-trait association and epistasis for brown rust resistance in sugarcane - Fernanda R. C. Santos; Luciana R. Pinto; Luciana A. Carlini-Garcia; Rodrigo Gazaffi; Melina C. Mancini; Bruna S. Gonçalves; Cibele N. F. Medeiros; Dilermando Perecin; Antônio A. F. Garcia; Anete P. Souza; Maria I. Zucchi (Euphytica, 2015)

Unraveling the interactive effects of climate change and oil contamination on laboratory‐simulated estuarine benthic communities - Francisco J. R. C. Coelho; Daniel F. R. Cleary; Rui J. M. Rocha; Ricardo Calado; José M. Castanheira; Sílvia M. Rocha; Artur M. S. Silva; Mário M. Q. Simões; Vanessa Oliveira; Ana I. Lillebø; Adelaide Almeida; Ângela Cunha; et al. (Global Change Biology, 2015)
There is growing concern that modifications to the global environment such as ocean acidification and increased ultraviolet radiation may interact with anthropogenic pollutants to adversely affect the future marine environment. Despite this, little is known about the nature of the potential risks posed by such interactions. Here, we performed a multifactorial microcosm experiment to assess the impact of ocean acidification, ultraviolet B (UV‐B) radiation and oil hydrocarbon contamination on sediment chemistry, the microbial community (composition and function) and biochemical marker response of selected indicator species. We found that increased ocean acidification and oil contamination in the absence of UV‐B will significantly alter bacterial composition by, among other things, greatly reducing the relative abundance of Desulfobacterales , known to be important oil hydrocarbon degraders. Along with changes in bacterial composition, we identified concomitant shifts in the composition of oil hydrocarbons in the sediment and an increase in oxidative stress effects on our indicator species. Interestingly, our study identifies UV‐B as a critical component in the interaction between these factors, as its presence alleviates harmful effects caused by the combination of reduced pH and oil pollution. The model system used here shows that the interactive effect of reduced pH and oil contamination can adversely affect the structure and functioning of sediment benthic communities, with the potential to exacerbate the toxicity of oil hydrocarbons in marine ecosystems.

Global land use impacts on biomass production—a spatial-differentiated resource-related life cycle impact assessment method - Rodrigo A. F. Alvarenga; Karl-Heinz Erb; Helmut Haberl; Sebastião R. Soares; Rosalie van Zelm; Jo Dewulf (The International Journal of Life Cycle Assessment, 2015)

Using mark-recapture and stranding data to estimate reproductive traits in female bottlenose dolphins (Tursiops truncatus) of the Southwestern Atlantic Ocean - Pedro F. Fruet; Rodrigo Cezar Genoves; Luciana M. Möller; Silvina Botta; Eduardo R. Secchi (Marine Biology, 2015)

A new species of Troglocarcinus (Decapoda: Brachyura: Cryptochiridae) symbiotic with the Brazilian endemic coral Mussismilia (Anthozoa: Scleractinia: Mussidae) - Roberta Canário; Marcelle F. S. Badaró; Rodrigo Johnsson; Elizabeth G. Neves (Marine Biology Research, 2015)

Lithium increases leukocyte mitochondrial complex I activity in bipolar disorder during depressive episodes - Rafael T. de Sousa; Emilio L. Streck; Marcus V. Zanetti; Gabriela K. Ferreira; Breno S. Diniz; Andre R. Brunoni; Geraldo F. Busatto; Wagner F. Gattaz; Rodrigo Machado-Vieira (Psychopharmacology, 2015)

Molecular characterization of infectious laryngotracheitis virus in naturally infected egg layer chickens in a multi-age flock in Brazil - Rodrigo de Macedo Couto; Ingred Sales Preis; Juliana Fortes Vilarinho Braga; Bruno S. A. F. Brasil; Marcela Gonçalves Drummond; Nelson Rodrigo da Silva Martins; Roselene Ecco (Archives of Virology, 2015)

Assessment of tolerance to bud rot in oil palm under field conditions - Edwin A. Navia; Rodrigo A. Ávila; Edison E. Daza; Edwin F. Restrepo; Hernán Mauricio Romero (European Journal of Plant Pathology, 2014)

Bacterial community characterization in the soils of native and restored rainforest fragments - Rafael L. F. Vasconcellos; Tiago D. Zucchi; Rodrigo G. Taketani; Fernando D. Andreote; Elke J. B. N. Cardoso (Antonie van Leeuwenhoek, 2014)

Methods, fluxes and sources of gas phase alkyl nitrates in the coastal air - Alin C. Dirtu; Anna J. Buczyńska; Ana F. L. Godoi; Rodrigo Favoreto; László Bencs; Sanja S. Potgieter-Vermaak; Ricardo H. M. Godoi; René Van Grieken; Luc Van Vaeck (Environmental Monitoring and Assessment, 2014)

Reference genes for RT-qPCR studies in Corynebacterium pseudotuberculosis identified through analysis of RNA-seq data - Daiane M. Carvalho; Pablo H. de Sá; Thiago L. P. Castro; Rodrigo D. Carvalho; Anne Pinto; Danilo J. P. Gil; Priscilla Bagano; Bruno Bastos; Lilia F. M. Costa; Roberto Meyer; Artur Silva; Vasco Azevedo; et al. (Antonie van Leeuwenhoek, 2014)

A model for quantitative trait loci mapping, linkage phase, and segregation pattern estimation for a full-sib progeny - Rodrigo Gazaffi; Gabriel R. A. Margarido; Maria Marta Pastina; Marcelo Mollinari; Antonio Augusto F. Garcia (Tree Genetics & Genomes, 2014)

Insights into the mechanisms underlying the antiproliferative potential of a Co(II) coordination compound bearing 1,10-phenanthroline-5,6-dione: DNA and protein interaction studies - Daniel V. Luís; Joana Silva; Ana Isabel Tomaz; Rodrigo F. M. de Almeida; Miguel Larguinho; Pedro V. Baptista; Luísa M. D. R. S. Martins; Telma F. S. Silva; Pedro M. Borralho; Cecília M. P. Rodrigues; António S. Rodrigues; Armando J. L. Pombeiro; et al. (JBIC Journal of Biological Inorganic Chemistry, 2014)

Cytokines plasma levels during antidepressant treatment with sertraline and transcranial direct current stimulation (tDCS): results from a factorial, randomized, controlled trial - André R. Brunoni; Rodrigo Machado-Vieira; Carlos A. Zarate; Leandro Valiengo; Erica LM Vieira; Isabela M Benseñor; Paulo A. Lotufo; Wagner F. Gattaz; Antonio L Teixeira (Psychopharmacology, 2014)

A Single Neurotoxic Dose of Methamphetamine Induces a Long-Lasting Depressive-Like Behaviour in Mice - Carlos D. Silva; Ana F. Neves; Ana I. Dias; Hugo J. Freitas; Sheena M. Mendes; Inês Pita; Sofia D. Viana; Paulo A. de Oliveira; Rodrigo A. Cunha; Carlos A. Fontes Ribeiro; Rui D. Prediger; Frederico C. Pereira (Neurotoxicity Research, 2014)

Early Spanish meteorological records (1780–1850) - F. Domínguez‐Castro; J. M. Vaquero; F. S. Rodrigo; A. M. M. Farrona; M. C. Gallego; R. García‐Herrera; M. Barriendos; A. Sanchez‐Lorenzo (International Journal of Climatology, 2014)
This article summarizes recent efforts on early instrumental data recovery in Spain conducted under the Salvà‐Sinobas project. We have retrieved and digitized more than 100 000 meteorological observations prior to 1850 in Spain. This data set contains measurements of air temperature, atmospheric pressure, wind direction and state of the atmosphere in 16 places located in Iberia and the Balearic Islands. Most of the observations are made on a daily basis. However, monthly and annual information has also been retrieved. The time coverage of the series is not homogeneous, with the earliest records starting in Seville in 1780. Prior to this work only two series were available in Spain (i.e. Cadiz and Barcelona), so this data set represents a great advance in the early data availability for Spain. Due to the lack of metadata in most of the series, their interpretation must be made with caution. © 2013 Royal Meteorological Society

Remarkably low genetic diversity and strong population structure in common bottlenose dolphins (Tursiops truncatus) from coastal waters of the Southwestern Atlantic Ocean - Pedro F. Fruet; Eduardo R. Secchi; Fábio Daura-Jorge; Els Vermeulen; Paulo A. C. Flores; Paulo César Simões-Lopes; Rodrigo Cézar Genoves; Paula Laporta; Juliana C. Di Tullio; Thales Renato O. Freitas; Luciano Dalla Rosa; Victor Hugo Valiati; et al. (Conservation Genetics, 2014)

Neurophysiological Studies and Non-Motor Symptoms Prior to Ataxia in a Patient with Machado–Joseph Disease: Trying to Understand the Natural History of Brain Degeneration - José Luiz Pedroso; Edson Bor-Seng-Shu; Pedro Braga-Neto; Rodrigo Souza Ribeiro; Márcio Luiz Escorcio Bezerra; Lucila B. F. do Prado; Ilza Rosa Batista; Helena Alessi; Manoel Jacobsen Teixeira; Gilberto Mastrocola Manzano; Gilmar Fernandes do Prado; Orlando Graziani Povoas Barsottini (The Cerebellum, 2014)

Lectin of Abelmoschus esculentus (okra) promotes selective antitumor effects in human breast cancer cells - Leonardo G. Monte; Tatiane Santi-Gadelha; Larissa B. Reis; Elizandra Braganhol; Rafael F. Prietsch; Odir A. Dellagostin; Rodrigo Rodrigues e Lacerda; Carlos A. A. Gadelha; Fabricio R. Conceição; Luciano S. Pinto (Biotechnology Letters, 2014)

Optimism and Challenge for Science‐Based Conservation of Migratory Species in and out of U.S. National Parks - JOEL BERGER; STEVEN L. CAIN; ELLEN CHENG; PETER DRATCH; KEVIN ELLISON; JOHN FRANCIS; HERBERT C. FROST; SCOTT GENDE; CRAIG GROVES; WILLIAM A. KARESH; ELAINE LESLIE; GARY MACHLIS; et al. (Conservation Biology, 2014)
Public agencies sometimes seek outside guidance when capacity to achieve their mission is limited. Through a cooperative agreement and collaborations with the U.S. National Park Service (NPS), we developed recommendations for a conservation program for migratory species. Although NPS manages ∼36 million hectares of land and water in 401 units, there is no centralized program to conserve wild animals reliant on NPS units that also migrate hundreds to thousands of kilometers beyond parks. Migrations are imperiled by habitat destruction, unsustainable harvest, climate change, and other impediments. A successful program to counter these challenges requires public support, national and international outreach, and flourishing migrant populations. We recommended two initial steps. First, in the short term, launch or build on a suite of projects for high‐profile migratory species that can serve as proof to demonstrate the centrality of NPS units to conservation at different scales. Second, over the longer term, build new capacity to conserve migratory species. Capacity building will entail increasing the limited knowledge among park staff about how and where species or populations migrate, conditions that enable migration, and identifying species’ needs and resolving them both within and beyond parks. Building capacity will also require ensuring that park superintendents and staff at all levels support conservation beyond statutory borders. Until additional diverse stakeholders and a broader American public realize what can be lost and do more to protect it and engage more with land management agencies to implement actions that facilitate conservation, long distance migrations are increasingly likely to become phenomena of the past. Optimismo y Retos para la Conservación Científicamente Basada de Especies Migratorias Dentro y Fuera de Parques Nacionales de E.U.A.

The diversity of BVDV subgenotypes in a vaccinated dairy cattle herd in Brazil - Rodrigo A. A. Otonel; Alice F. Alfieri; Stelamaris Dezen; Michele Lunardi; Selwyn A. Headley; Amauri A. Alfieri (Tropical Animal Health and Production, 2014)

Molecular characterization of encephalitic bovine listeriosis from southern Brazil - Selwyn A. Headley; Juliana T. T. Fritzen; Gustavo R. Queiroz; Rodrigo A. M. Oliveira; Alice F. Alfieri; Giovana W. Di Santis; Júlio A. N. Lisbôa; Amauri A. Alfieri (Tropical Animal Health and Production, 2014)

Metabolic regulation in meagre, Argyrosomus regius (Asso, 1801): Study of gene-diet interactions on lipid metabolism - Silva-Brito Francisca; Fonseca Sthelio; Peixoto Maria João; Domingues Andreia; Damasceno-Oliveira Alfredo; Gonçalves José; Castro Filipe F.; Cunha Isabel; Ozorio Rodrigo O. (Frontiers in Marine Science, 2014)

Effect of dietary probiotic supplementation on growth and innate immune system in sole (Solea senegalensis Kaup, 1858) subjected to pathogenic bacteria infection and handling stress - Domingues Andreia; Peixoto Maria João; Batista Sónia M.; Gomes Ana; Manaia Célia; Gonçalves José F.; Cunha Sofia; Barros Rui; Valente Luísa M.; Costas Benjaním; Ozorio Rodrigo O. (Frontiers in Marine Science, 2014)

Antioxidant capacity of meagre (Argyrossomus regius) fed different lipid content and source, with and without selenium - Fonseca Sthelio; Magalhães Fernando; Gravato Carlos; Soares Amadeu M.V.; Gonçalves José F.; Peixoto Maria João; Domingues Andreia; Da Silva José Humberto; Gonçalves Giovani; Ozório Rodrigo O. (Frontiers in Marine Science, 2014)

Amoebas as mimivirus bunkers: increased resistance to UV light, heat and chemical biocides when viruses are carried by amoeba hosts - Paulo V. M. Boratto; Fábio P. Dornas; Kétyllen R. Andrade; Rodrigo Rodrigues; Felipe Peixoto; Lorena C. F. Silva; Bernard La Scola; Adriana Oliveira Costa; Gabriel Magno Freitas de Almeida; Erna G. Kroon; Jônatas S. Abrahão (Archives of Virology, 2013)

Drought Influences the Accuracy of Simulated Ecosystem Fluxes: A Model-Data Meta-analysis for Mediterranean Oak Woodlands - Rodrigo Vargas; Oliver Sonnentag; Gab Abramowitz; Arnaud Carrara; Jing Ming Chen; Philippe Ciais; Alexandra Correia; Trevor F. Keenan; Hideki Kobayashi; Jean-Marc Ourcival; Dario Papale; David Pearson; et al. (Ecosystems, 2013)

Development and validation of an experimental life support system for assessing the effects of global climate change and environmental contamination on estuarine and coastal marine benthic communities - Francisco J. R. C. Coelho; Rui J. M. Rocha; Ana C. C. Pires; Bruno Ladeiro; José M. Castanheira; Rodrigo Costa; Adelaide Almeida; Ângela Cunha; Ana Isabel Lillebø; Rui Ribeiro; Ruth Pereira; Isabel Lopes; et al. (Global Change Biology, 2013)
An experimental life support system ( ELSS ) was constructed to study the interactive effects of multiple stressors on coastal and estuarine benthic communities, specifically perturbations driven by global climate change and anthropogenic environmental contamination. The ELSS allows researchers to control salinity, pH , temperature, ultraviolet radiation ( UVR ), tidal rhythms and exposure to selected contaminants. Unlike most microcosms previously described, our system enables true independent replication (including randomization). In addition to this, it can be assembled using commercially available materials and equipment, thereby facilitating the replication of identical experimental setups in different geographical locations. Here, we validate the reproducibility and environmental quality of the system by comparing chemical and biological parameters recorded in our ELSS with those prevalent in the natural environment. Water, sediment microbial community and ragworm (the polychaete Hediste diversicolor ) samples were obtained from four microcosms after 57 days of operation. In general, average concentrations of dissolved inorganic nutrients ( NO 3 − ; NH 4 + and PO 4 −3 ) in the water column of the ELSS experimental control units were within the range of concentrations recorded in the natural environment. While some shifts in bacterial community composition were observed between in situ and ELSS sediment samples, the relative abundance of most metabolically active bacterial taxa appeared to be stable. In addition, ELSS operation did not significantly affect survival, oxidative stress and neurological biomarkers of the model organism Hediste diversicolor . The validation data indicate that this system can be used to assess independent or interactive effects of climate change and environmental contamination on benthic communities. Researchers will be able to simulate the effects of these stressors on processes driven by microbial communities, sediment and seawater chemistry and to evaluate potential consequences to sediment toxicity using model organisms such as Hediste diversicolor .

Exergy-based accounting for land as a natural resource in life cycle assessment - Rodrigo A. F. Alvarenga; Jo Dewulf; Herman Van Langenhove; Mark A. J. Huijbregts (The International Journal of Life Cycle Assessment, 2013)

Plant-derived essential oils affecting settlement and oviposition of Bemisia tabaci (Genn.) biotype B on tomato - Edson L. L. Baldin; Antônio E. M. Crotti; Kamila A. L. Wakabayashi; José P. G. F. Silva; Gabriela P. Aguiar; Efrain S. Souza; Rodrigo C. S. Veneziani; Milton Groppo (Journal of Pest Science, 2013)

Conservation value of alternative land-use systems for dung beetles in Amazon: valuing traditional farming practices - Vanesca Korasaki; Rodrigo F. Braga; Ronald Zanetti; Fatima M. S. Moreira; Fernando Z. Vaz-de-Mello; Julio Louzada (Biodiversity and Conservation, 2013)

Behavioural and genetic interactions between an endangered and a recently-arrived hummingbird - Wouter F. D. van Dongen; Ilenia Lazzoni; Hans Winkler; Rodrigo A. Vásquez; Cristián F. Estades (Biological Invasions, 2013)

Testing for Natural Selection in Human Exonic Splicing Regulators Associated with Evolutionary Rate Shifts - Rodrigo F. Ramalho; Sahar Gelfman; Jorge E. de Souza; Gil Ast; Sandro J. de Souza; Diogo Meyer (Journal of Molecular Evolution, 2013)

Effects of host plant and maternal feeding experience on population vital rates of a specialized leaf beetle - Rodrigo S. Rios; Maritza Cárdenas; Kely González; Mónica F. Cisternas; Patricia C. Guerra; Andrea P. Loayza; Ernesto Gianoli (Arthropod-Plant Interactions, 2013)

Cognitive Deficits in Machado–Joseph Disease Correlate with Hypoperfusion of Visual System Areas - Pedro Braga-Neto; Lívia Almeida Dutra; José Luiz Pedroso; André C. Felício; Helena Alessi; Ruth F. Santos-Galduroz; Paulo Henrique F. Bertolucci; Mário Luiz V. Castiglioni; Rodrigo Affonseca Bressan; Griselda Esther Jara de Garrido; Orlando Graziani Povoas Barsottini; Andrea Jackowski (The Cerebellum, 2012)

Trends in seasonal indices of daily temperature extremes in the Iberian Peninsula, 1929–2005 - S. Fernández‐Montes; F. S. Rodrigo (International Journal of Climatology, 2012)
Seasonal changes of extreme daily temperature indices (frequency of frost days, tropical nights, and ‘summer’ days) of 25 stations in the Iberian Peninsula (IP) from 1929 to 2005 are investigated. Cluster analysis is used to identify homogeneous groups of stations with similar thermal regimes. The Mann‐Kendall test is applied to look for statistically significant trends. The results show a significant decreasing trend (−0.6 days/decade), especially from 1965 onwards, in the frequency of frost days for coastal stations, and significant increasing trends, from 1980 onwards, especially important to the southeast of the IP (+3.8 days/decade) for summer tropical nights, and in the southern stations (+2.3 days/decade) for summer days. The behaviour of the winter frost days index is related to the evolution of winter NAO and EA patterns (with increasing trends in the last decades of the 20th century). Although multiple regression models establish a relationship between summer indices and the SCAN pattern, the behaviour of residuals indicates that summer indices must be explained by other causal mechanisms. Copyright © 2011 Royal Meteorological Society

Higher striatal dopamine transporter density in PTSD: an in vivo SPECT study with [99mTc]TRODAT-1 - Marcelo Q. Hoexter; Gustavo Fadel; André C. Felício; Mariana B. Calzavara; Ilza R. Batista; Marilia A. Reis; Ming C. Shih; Roger K. Pitman; Sérgio B. Andreoli; Marcelo F. Mello; Jair J. Mari; Rodrigo A. Bressan (Psychopharmacology, 2012)

Frequent aberrant expression of the human ether à go-go (hEAG1) potassium channel in head and neck cancer: pathobiological mechanisms and clinical implications - Sofía Tirados Menéndez; María Ángeles Villaronga; Juan P. Rodrigo; Saúl Álvarez-Teijeiro; Darío García-Carracedo; Rocío G. Urdinguio; Mario F. Fraga; Luis A. Pardo; Cristina Gutiérrez Viloria; Carlos Suárez; Juana María García-Pedrero (Journal of Molecular Medicine, 2012)

Bioconversion of Iodoacetophenones by Marine Fungi - Lenilson C. Rocha; Rodrigo F. Luiz; Isac G. Rosset; Cristiano Raminelli; Mirna H. R. Seleghim; Lara Durães Sette; André L. M. Porto (Marine Biotechnology, 2012)

Evaluation of the Influence of Natural and Antrhopogenic Processes on Water Quality in Karstic Region - Maria Lúcia Calijuri; Eduardo de Aguiar do Couto; Aníbal da Fonseca Santiago; Rodrigo de Arruda Camargo; Marcos D. F. M. e Silva (Water, Air, & Soil Pollution, 2012)

Changes in soil hyphal abundance and viability can alter the patterns of hydraulic redistribution by plant roots - José Ignacio Querejeta; Louise M. Egerton-Warburton; Iván Prieto; Rodrigo Vargas; Michael F. Allen (Plant and Soil, 2012)

Stereoselective Bioreduction of 1-(4-Methoxyphenyl)ethanone by Whole Cells of Marine-Derived Fungi - Lenilson C. Rocha; Hercules V. Ferreira; Rodrigo F. Luiz; Lara D. Sette; André L. M. Porto (Marine Biotechnology, 2012)

Connectivity and population subdivision at the fringe of a large brown bear (Ursus arctos) population in North Western Europe - Alexander Kopatz; Hans Geir Eiken; Snorre B. Hagen; Minna Ruokonen; Rodrigo Esparza-Salas; Julia Schregel; Ilpo Kojola; Martin E. Smith; Ingvild Wartiainen; Paul E. Aspholm; Steinar Wikan; Alexander M. Rykov; et al. (Conservation Genetics, 2012)

Completing the early instrumental weather record from Cádiz (Southern Spain): new data from 1799 to 1803 - F. S. Rodrigo (Climatic Change, 2012)

The use of microsatellite loci for accurate hybrid detection in a recent contact zone between an endangered and a recently-arrived hummingbird - Wouter F. D. van Dongen; Rodrigo A. Vásquez; Hans Winkler (Journal of Ornithology, 2012)

Precipitation variability and fire influence the temporal dynamics of soil CO 2 efflux in an arid grassland - Rodrigo Vargas; Scott L. Collins; Michell L. Thomey; Jennifer E. Johnson; Renee F. Brown; Donald O. Natvig; Michael T. Friggens (Global Change Biology, 2012)
Climate models suggest that extreme rainfall events will become more common with increased atmospheric warming. Consequently, changes in the size and frequency of rainfall will influence biophysical drivers that regulate the strength and timing of soil CO 2 efflux – a major source of terrestrial carbon flux. We used a rainfall manipulation experiment during the summer monsoon season ( J uly– S eptember) to vary both the size and frequency of precipitation in an arid grassland 2 years before and 2 years after a lightning‐caused wildfire. Soil CO 2 efflux rates were always higher under increased rainfall event size than under increased rainfall event frequency, or ambient precipitation. Although fire reduced soil CO 2 efflux rates by nearly 70%, the overall responses to rainfall variability were consistent before and after the fire. The overall sensitivity of soil CO 2 efflux to temperature ( Q 10 ) converged to 1.4, but this value differed somewhat among treatments especially before the fire. Changes in rainfall patterns resulted in differences in the periodicity of soil CO 2 efflux with strong signals at 1, 8, and 30 days. Increased rainfall event size enhanced the synchrony between photosynthetically active radiation and soil CO 2 efflux over the growing season before and after fire, suggesting a change in the temporal availability of substrate pools that regulate the temporal dynamics and magnitude of soil CO 2 efflux. We conclude that arid grasslands are capable of rapidly increasing and maintaining high soil CO 2 efflux rates in response to increased rainfall event size more than increased rainfall event frequency both before and after a fire. Therefore, the amount and pattern of multiple rain pulses over the growing season are crucial for understanding CO 2 dynamics in burned and unburned water‐limited ecosystems.

Heterogeneous seepage at the Nopal I natural analogue site, Chihuahua, Mexico - Patrick F. Dobson; Teamrat A. Ghezzehei; Paul J. Cook; J. Alfredo Rodríguez-Pineda; Lourdes Villalba; Rodrigo De la Garza (Hydrogeology Journal, 2012)

Remaining genetic diversity in Brazilian Merganser (Mergus octosetaceus) - Sibelle Torres Vilaça; Rodrigo A. F. Redondo; Livia Vanucci Lins; Fabricio R. Santos (Conservation Genetics, 2012)

Viability selection on body size in a non-marine ostracod - Rodrigo Scheihing; Pedro Labarca; Leyla Cardenas; Roberto F. Nespolo (Hydrobiologia, 2011)

Kanagawa-Negative, tdh- and trh-Positive Vibrio parahaemolyticus Isolated from Fresh Oysters Marketed in Fortaleza, Brazil - Regine H. S. F. Vieira; Renata A. Costa; Francisca G. R. Menezes; Giselle C. Silva; Grace N. D. Theophilo; Dália P. Rodrigues; Rodrigo Maggioni (Current Microbiology, 2011)

GH overexpression causes muscle hypertrophy independent from local IGF-I in a zebrafish transgenic model - Rafael Y. Kuradomi; Márcio A. Figueiredo; Carlos F. C. Lanes; Carlos E. da Rosa; Daniela V. Almeida; Rodrigo Maggioni; Maeli D. P. Silva; Luis F. Marins (Transgenic Research, 2011)

DTI-MR tractography of white matter damage in stroke patients with neglect - M. Urbanski; M. Thiebaut de Schotten; S. Rodrigo; C. Oppenheim; E. Touzé; J.-F. Méder; K. Moreau; C. Loeper-Jeny; B. Dubois; P. Bartolomeo (Experimental Brain Research, 2011)

Differential Resistance to Oxidants and Production of Hydrolytic Enzymes in Candida albicans - Maxwel A. Abegg; Rodrigo Lucietto; Paulo V. G. Alabarse; Marcus F. A. Mendes; Mara Silveira Benfato (Mycopathologia, 2011)

Analyzing GNSS data in precise point positioning software - Rodrigo F. Leandro; Marcelo C. Santos; Richard B. Langley (GPS Solutions, 2011)

Changes in the probability of extreme daily precipitation observed from 1951 to 2002 in the Iberian Peninsula - F. S. Rodrigo (International Journal of Climatology, 2010)
In this study trends in the probability of extreme rainfall in the Iberian Peninsula at a daily scale from 1951 to 2002 have been analysed. A simple statistical model of daily precipitation based on the gamma distribution is applied to data from 22 stations in the Iberian Peninsula from 1951 to 2002. The Mann–Kendall test was applied to look for trends of the distribution parameters. It is shown that the scale parameter remains stable, while the shape parameter is most variable, spatially and temporally, with significant negative trends in many stations. As a consequence, the trend of the probability of daily rainfall lesser than the 5th percentile is positive, mainly to the north and to the south of the Iberian Peninsula; meanwhile the probability of daily rainfall higher than the 95th percentile is negative. This behaviour, with slight spatial differences, is observed in the four seasons of the year. Results corresponding to the probability of heavy rainfalls are confirmed using the stretched exponential distribution. The possible influence of teleconnection patterns (North Atlantic Oscillation, East Atlantic, Mediterranean Oscillation pattern) is analysed calculating the correlation coefficients between teleconnection indices and the gamma distribution parameters. The winter NAO index shows significant relationships with the scale parameter, but not with the shape parameter. The East Atlantic pattern shows significant correlation coefficients with the shape parameter of 5 stations in winter, and 5 stations in autumn, but these results are not conclusive. These results suggest that the decrease of this parameter, and the behaviour of extreme rainfall probabilities, must be explained by other mechanisms. Copyright © 2009 Royal Meteorological Society

Higher dopamine transporter density in Parkinson’s disease patients with depression - Andre C. Felicio; Tais S. Moriyama; Clecio Godeiro-Junior; Ming C. Shih; Marcelo Q. Hoexter; Vanderci Borges; Sonia M. A. Silva; Edson Amaro-Junior; Luiz A. F. Andrade; Henrique B. Ferraz; Rodrigo A. Bressan (Psychopharmacology, 2010)

Using soil sensing technology to examine interactions and controls between ectomycorrhizal growth and environmental factors on soil CO2 dynamics - Niles J. Hasselquist; Rodrigo Vargas; Michael F. Allen (Plant and Soil, 2010)

Multiscale analysis of temporal variability of soil CO 2 production as influenced by weather and vegetation - RODRIGO VARGAS; MATTEO DETTO; DENNIS D. BALDOCCHI; MICHAEL F. ALLEN (Global Change Biology, 2010)
Ecosystem processes are influenced by weather and climatic perturbations at multiple temporal scales with a large range of amplitudes and phases. Technological advances of automated biometeorological measurements provide the opportunity to apply spectral methods on continuous time series to identify differences in amplitudes and phases and relationships with weather variation. Here we used wavelet coherence analysis to study the temporal covariance between soil CO 2 production and soil temperature, soil moisture, and photosynthetically active radiation (PAR). Continuous (hourly average) data were acquired over 2 years among three vegetation types in a semiarid mixed temperate forest. We showed that soil temperature and soil moisture influence soil CO 2 production differently at multiple periods (e.g. hours, days, weeks, months, years), especially after rain pulse events. Our results provide information about the periodicity of soil CO 2 production among vegetation types, and provide insights about processes controlling CO 2 production through the study of phase relationships between two time series (e.g. soil CO 2 production and PAR). We tested the performance of empirical models of soil CO 2 production using the continuous wavelet transform. These models, built around soil temperature and moisture, failed at multiple periods across the measured dates, suggesting that empirical models should include other factors that regulate soil CO 2 production at different temporal scales. Our results add a new dimension for the analysis of continuous time series of biometeorological measurements and model testing, which will prove useful for analysis of increasing sensor data obtained by environmental networks.

A composite transcriptional signature differentiates responses towards closely related herbicides in Arabidopsis thaliana and Brassica napus - Malay Das; Jay R. Reichman; Georg Haberer; Gerhard Welzl; Felipe F. Aceituno; Michael T. Mader; Lidia S. Watrud; Thomas G. Pfleeger; Rodrigo A. Gutiérrez; Anton R. Schäffner; David M. Olszyk (Plant Molecular Biology, 2010)

Morphological and molecular analysis of centropagids from the high Andean plateau (Copepoda: Calanoidea) - Rodrigo Scheihing; Leyla Cardenas; Roberto F. Nespolo; Paola Krall; Katherina Walz; Shiro Kohshima; Pedro Labarca (Hydrobiologia, 2010)

Relevance of unilateral and bilateral sexual polyploidization in relation to intergenomic recombination and introgression in Lilium species hybrids - Nadeem Khan; Rodrigo Barba-Gonzalez; M. S. Ramanna; Paul Arens; Richard G. F. Visser; Jaap M. Van Tuyl (Euphytica, 2010)

Effects of a Hurricane Disturbance on Aboveground Forest Structure, Arbuscular Mycorrhizae and Belowground Carbon in a Restored Tropical Forest - Rodrigo Vargas; Niles Hasselquist; Edith B. Allen; Michael F. Allen (Ecosystems, 2010)

Myrtaceae species resistance to rust caused by Puccinia psidii - Edival A. V. Zauza; Acelino C. Alfenas; Ken Old; Michelle M. F. Couto; Rodrigo N. Graça; Luiz Antônio Maffia (Australasian Plant Pathology, 2010)

Selection of a Clostridium perfringens type D epsilon toxin producer via dot-blot test - Luciana A. Gonçalves; Zélia I. P. Lobato; Rodrigo O. S. Silva; Felipe M. Salvarani; Prhiscylla S. Pires; Ronnie A. Assis; Francisco C. F. Lobato (Archives of Microbiology, 2009)

MMP-9 and CD68+ cells are required for tissue remodeling in response to natural hydroxyapatite - Willian F. Zambuzzi; Katiúcia B. S. Paiva; Renato Menezes; Rodrigo C. Oliveira; Rumio Taga; José M. Granjeiro (Journal of Molecular Histology, 2009)

Increased growth hormone (GH), growth hormone receptor (GHR), and insulin-like growth factor I (IGF-I) gene transcription after hyperosmotic stress in the Brazilian flounder Paralichthys orbignyanus - Karina M. Meier; Márcio A. Figueiredo; Michel T. Kamimura; Jomar Laurino; Rodrigo Maggioni; Luciano S. Pinto; Odir A. Dellagostin; Marcelo B. Tesser; Luís A. Sampaio; Luis F. Marins (Fish Physiology and Biochemistry, 2009)

Distribution of microphytobenthic biomass in Martel Inlet, King George Island (Antarctica) - Rodrigo S. P. de Skowronski; Paula F. Gheller; Sandra Bromberg; Carlos J. David; Mônica A. V. Petti; Thaïs N. Corbisier (Polar Biology, 2009)

Evidence of maternal QTL affecting growth and obesity in adult mice - Joaquim Casellas; Charles R. Farber; Rodrigo J. Gularte; Kari A. Haus; Craig H. Warden; Juan F. Medrano (Mammalian Genome, 2009)

Fire‐related traits for plant species of the Mediterranean Basin - S. Paula; M. Arianoutsou; D. Kazanis; Ç Tavsanoglu; F. Lloret; C. Buhk; F. Ojeda; B. Luna; J. M. Moreno; A. Rodrigo; J. M. Espelta; S. Palacio; et al. (Ecology, 2009)
Plant trait information is essential for understanding plant evolution, vegetation dynamics, and vegetation responses to disturbance and management. Furthermore, in Mediterranean ecosystems, changes in fire regime may be more relevant than direct changes in climatic conditions, making the knowledge of fire‐related traits especially important. Thus the purpose of this data set was to compile the most updated and comprehensive information on fire‐related traits for vascular plant species of the Mediterranean Basin, that is, traits related to plant persistence and regeneration after fire. Data were collected from an extensive literature review and from field and experimental observations. The data source is documented for each value. Since life history traits may vary spatially or with environmental conditions, we did not aggregate them by species; i.e., traits and species are repeated in different records if they were observed by different researchers and/or in different locations. Life history traits included in the data set are: life form, resprouting ability (after fire, after clipping, or after other disturbances that remove all the aboveground biomass), resprouting bud source, heat‐stimulated germination, other germination cues, seed bank location and longevity, post‐fire seedling emergence and survival, maturity age of resprouts and saplings, and seed mass. Several traits are unknown for many species; consequently, the data set reflects the state of the knowledge on the topic. However, since the ability to resprout is a trait of paramount relevance in fire‐prone environments, it was considered a core trait in the data set, and thus species whose resprouting capacity was unknown were not included. Life form is also provided for all taxa. The structure of the database allows different levels of information (and accuracy) for each entry, and thus some traits may include different types of data (quantitative, semi‐quantitative, or categorical) from different sources. The data set is structured in 8263 records and 11 columns, obtained from 301 published and unpublished sources of information. It includes 952 taxa determined at specific or infraspecific level, which comprise 859 species, 384 genera, and 79 families. Although this is the most comprehensive data set of fire‐relevant plant traits for Mediterranean species, there is still a considerable need for observations and experiments, especially in little‐studied Mediterranean areas, such as northern Africa. The complete data sets corresponding to abstracts published in the Data Papers section of the journal are published electronically in Ecological Archives at 〈 http://esapubs.org/archive 〉. (The accession number for each Data Paper is given directly beneath the title.)

Patterns of fish community composition along a river affected by agricultural and urban disturbance in south-central Chile - Rodrigo Orrego; S. Marshall Adams; Ricardo Barra; Gustavo Chiang; Juan F. Gavilan (Hydrobiologia, 2009)

On the Diversity of the Laccase Gene: A Phylogenetic Perspective from Botryosphaeria rhodina (Ascomycota: Fungi) and Other Related Taxa - Flávio J. D. Castilho; Rodrigo A. Torres; Aneli M. Barbosa; Robert F. H. Dekker; José E. Garcia (Biochemical Genetics, 2009)

Hunting Tactics in a Cobweb Spider (Araneae-Theridiidae) and the Evolution of Behavioral Plasticity - Hilton F. Japyassú; Rodrigo A. Caires (Journal of Insect Behavior, 2008)

A new method to reconstruct low-frequency climatic variability from documentary sources: application to winter rainfall series in Andalusia (Southern Spain) from 1501 to 2000 - F. S. Rodrigo (Climatic Change, 2008)

Guarana (Paullinia cupana var. sorbilis), an anciently consumed stimulant from the Amazon rain forest: the seeded-fruit transcriptome - Paula C. S. Ângelo; Carlos G. Nunes-Silva; Marcelo M. Brígido; Juliana S. N. Azevedo; Enedina N. Assunção; Alexandra R. B. Sousa; Fernando J. B. Patrício; Mailson M. Rego; Jean C. C. Peixoto; Waldesse P. Oliveira; Danival V. Freitas; Elionor R. P. Almeida; et al. (Plant Cell Reports, 2008)

UNB3m_pack: a neutral atmosphere delay package for radiometric space techniques - Rodrigo F. Leandro; Richard B. Langley; Marcelo C. Santos (GPS Solutions, 2008)

Biomass and carbon accumulation in a fire chronosequence of a seasonally dry tropical forest - RODRIGO VARGAS; MICHAEL F. ALLEN; EDITH B. ALLEN (Global Change Biology, 2008)
Seasonally dry tropical forests (SDTF) are a widely distributed vegetation type in the tropics, characterized by seasonal rainfall with several months of drought when they are subject to fire. This study is one of the first attempts to quantify above‐ and belowground biomass (AGB and BGB) and above‐ and belowground carbon (AGC and BGC) pools to calculate their recovery after fire, using a chronosequence approach (six forests that ranged form 1 to 29 years after fire and mature forest). We quantified AGB and AGC pools of trees, lianas, palms, and seedlings, and BGB and BGC pools (Oi, Oe, Oa soil horizons, and fine roots). Total AGC ranged from 0.05 to nearly 72 Mg C ha −1 , BGC from 21.6 to nearly 85 Mg C ha −1 , and total ecosystem carbon from 21.7 to 153.5 Mg C ha −1 ; all these pools increased with forest age. Nearly 50% of the total ecosystem carbon was stored in the Oa horizon of mature forests, and up to 90% was stored in the Oa‐horizon of early successional SDTF stands. The soils were shallow with a depth of −1 yr −1 , while AGB required 80 years with accumulation rates nearly 2.5 Mg C ha −1 yr −1 . Total ecosystem biomass and carbon required 70 and 50 years, respectively, to recover values similar to mature forests. When belowground pools are not included in the calculation of total ecosystem biomass or carbon recovery, we estimated an overestimation of 10 and 30 years, respectively.

Single Molecule Spectroscopy of Poly 3-octyl-thiophene (P3OT) - Rodrigo E. Palacios; Paul F. Barbara (Journal of Fluorescence, 2007)

Involvement of DNA methylation in tree development and micropropagation - Luis Valledor; Rodrigo Hasbún; Mónica Meijón; Jose Luis Rodríguez; Estrella Santamaría; Marcos Viejo; Maria Berdasco; Isabel Feito; Mario F. Fraga; Maria Jesús Cañal; Roberto Rodríguez (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Conservation Priorities and Population Structure of Woody Medicinal Plants in an Area of Caatinga Vegetation (Pernambuco State, NE Brazil) - Rodrigo L. C. de Oliveira; Ernani M. F. Lins Neto; Elcida L. Araújo; Ulysses P. Albuquerque (Environmental Monitoring and Assessment, 2007)

Modulation of synchrony without changes in firing rates - Jakob Heinzle; Peter König; Rodrigo F. Salazar (Cognitive Neurodynamics, 2007)

Trends in daily rainfall in the Iberian Peninsula from 1951 to 2002 - F. S. Rodrigo; Ricardo M. Trigo (International Journal of Climatology, 2007)
An analysis of 22 sites of daily precipitation records over the period 1951–2002 for the Iberian Peninsula is presented. Annual and seasonal total precipitation ( P ), number of wet days ( N ), precipitation intensity ( I ), the 95th percentile ( P 95), and percentage of rain falling on days with rainfall above the 95th percentile (%) are investigated. The annual and seasonal trends for these variables and for all 22 rain gauges are analysed, using the Mann–Kendall statistic, and a linear regression model. Moreover, a t ‐test is applied to the difference between the means of two subperiods, respectively 1951–1976 and 1977–2002. Principal results indicate a decreasing trend in P , I , and P 95 for several northern and southern stations in winter; P , I , and P 95 in some southern stations in spring, I and P 95 in some southern stations in summer, and I in some northern and southern stations in autumn. The general behaviour is a decrease in the daily intensity of rainfall, while the number of wet days does not reveal pronounced changes. This pattern is valid for both annual and seasonal values of the indices. The decreasing trend found for I in winter and annual series for some localities may be related to the predominance of the positive phase of the North Atlantic Oscillation (NAO), but it is necessary to find other mechanisms for those stations and seasons not linked directly to NAO. Copyright © 2006 Royal Meteorological Society.

Antipredator Behavior of Brown Howlers Attacked by Black Hawk-eagle in Southern Brazil - João M. D. Miranda; Itiberê P. Bernardi; Rodrigo F. Moro-Rios; Fernando C. Passos (International Journal of Primatology, 2006)

Progenies of allotriploids of Oriental × Asiatic lilies (Lilium) examined by GISH analysis - Rodrigo Barba-Gonzalez; Alex A. Van Silfhout; Richard G. F. Visser; Munikote S. Ramanna; Jaap M. Van Tuyl (Euphytica, 2006)

Unusual Orofacial Manifestations of Histoplasmosis in Renal Transplanted Patient - Ana Carolina F. Motta; Rodrigo Galo; Alan Grupioni Lourenço; Marilena C. Komesu; Darlene Arruda; Fabiana Guerra Velasco; Beatriz C. Garcia; Norma T. Foss (Mycopathologia, 2006)

Evolutionary Studies on an α-amylase Gene Segment in Bats and other Mammals - Rodrigo A. F. Redondo; Fabrício R. Santos (Genetica, 2006)

Special Section: Implementation and Management of Marine Protected Areas - Carolyn J. Lundquist; Elise F. Granek; Rodrigo H. Bustamante (Conservation Biology, 2005)

Production and partial characterization of extracellular proteinases from Streptomyces malaysiensis, isolated from a Brazilian cerrado soil - Rodrigo P. Nascimento; Claudia M. d’Avila-Levy; Rodrigo F. Souza; Marta H. Branquinha; Elba P. S. Bon; Nei Pereira-Jr; Rosalie R. R. Coelho (Archives of Microbiology, 2005)

Macroecological correlates and spatial patterns of anuran description dates in the Brazilian Cerrado - José Alexandre F. Diniz‐Filho; Rogério Pereira Bastos; Thiago F. L. V. B. Rangel; Luis M. Bini; Priscilla Carvalho; Rodrigo J. Silva (Global Ecology and Biogeography, 2005)
Aim To quantify the relationship between the description dates of anuran species in the Brazilian Cerrado and some macroecological traits, and to verify the spatial patterns of average description dates and their correlation with human occupation and biodiversity knowledge. Location Brazilian Cerrado (South America). Methods The average date of description of 131 species of anurans found in 181 cells overlaying the Brazilian Cerrado was recorded. Description date was regressed across species on body size and geographical range size. Phylogenetic effects that could bias the significance tests of the multiple regression model of description dates on macroecological traits were taken into account using a phylogenetic subtraction method in which families and genera were classificatory factors in a nested two‐way analysis of variance ( anova ) model. We also conducted a spatial analysis of the average description date that was estimated for each cell. This cell‐based metric was regressed on human population size, the year of foundation of the municipalities and the number of inventories undertaken in each cell. The influence of spatial autocorrelation patterns was taken into account by using the geographically effective number of degrees of freedom. Results The number of new species being discovered in the Brazilian Cerrado has been increasing, especially over the last 50 years. Cross‐species analyses indicated that description dates were negatively correlated with body size and geographical range size, taking phylogenetic effects into account. Even after controlling for the spatial structures in all variables, average description date was positively correlated with human population in geographical space, but because of multicolinearity structure in the data, it was not possible to quantify the independent influence of human population and number of inventories on description date. Conclusions As found in previous papers, large‐bodied and widely distributed species are likely to be described first. Species yet to be discovered are probably small‐bodied and with narrow distributions, more restricted to the Cerrado biome. Also, the explicit spatial approach showed that the average description date is spatially correlated with total human population and biodiversity knowledge in the Cerrado region. Our findings suggest that incorporating human population density into the reserve design algorithms, which has usually been done to avoid or minimize conservation conflicts, may also produce good results because this will preserve many places where most of the non‐described species will probably be found in the future.

Ticks (Acari: Ixodida) on wild carnivores in Brazil - Marcelo B. Labruna; Rodrigo S. P. Jorge; Dênis A. Sana; Anah Tereza A. Jácomo; Cyntia K. Kashivakura; Mariana M. Furtado; Claudia Ferro; Samuel A. Perez; Leandro Silveira; Tarcísio S. Santos JR; Samuel R. Marques; Ronaldo G. Morato; et al. (Experimental and Applied Acarology, 2005)

Development of a citrus genome-wide EST collection and cDNA microarray as resources for genomic studies - J. Forment; J. Gadea; L. Huerta; L. Abizanda; J. Agusti; S. Alamar; E. Alos; F. Andres; R. Arribas; J. P. Beltran; A. Berbel; M. A. Blazquez; et al. (Plant Molecular Biology, 2005)

Pneumococcal bacteremia in children: an 8-year review in two hospitals in Barcelona - A. Prez; P. Sala; M. Gimnez; M. Sierra; A. Esteve; A. Alonso; M. Quesada; F. Raspall; V. Ausina; C. Rodrigo (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Effects of the North Atlantic oscillation on the probability for climatic categories of local monthly rainfall in southern Spain - D. Muñoz‐Díaz; F. S. Rodrigo (International Journal of Climatology, 2003)
In many regions of the world, planning agricultural and water management activities is usually done based on probabilities for seasonal or monthly rainfall, for specified intervals of values. These intervals of rainfall amounts are commonly grouped into three categories: drought, normal rainfall, and abundant rainfall. Changes in the probabilities of occurrence of rainfall amounts within these climatic rainfall categories will influence the decisions that farmers and water managers will take. This research explores the changes produced by the North Atlantic oscillation (NAO) on the probability that local monthly rainfall takes in the southern Iberian Peninsula. The evolution of the NAO was divided into three phases: negative NAO, ‘normal’ NAO, and positive NAO, and local rainfall series were divided into three groups, corresponding to each NAO phase. The resulting empirical distribution functions were analysed and modelled by Gamma distributions. The results allow one to estimate the change in the probabilities of wet and dry months when a change in NAO phase is produced. The main result of this work is that changes in the probability of occurrence of climate categories of rainfall are more complex than only an increase of rainfall amount during the negative NAO phase and a decrease during the positive NAO phase. In fact, a certain asymmetry is detected in January, with more extremes linked to the negative NAO phase. Copyright © 2003 Royal Meteorological Society

Changes in climate variability and seasonal rainfall extremes: a case study from San Fernando (Spain), 1821-2000 - F. S. Rodrigo (Theoretical and Applied Climatology, 2002)

Reverse genetic approaches in plants and yeast suggest a role for novel, evolutionarily conserved, selenoprotein-related genes in oxidative stress defense - M.-J. Rodrigo; J. Moskovitz; F. Salamini; D. Bartels (Molecular Genetics and Genomics, 2002)

Detection and Characterization of Membrane Microheterogeneity by Resonance Energy Transfer - Luís M. S. Loura; Rodrigo F. M. de Almeida; Manuel Prieto (Journal of Fluorescence, 2001)

A study of NAO variability and its possible non-linear influences on European surface temperature - D. Pozo-Vázquez; M. J. Esteban-Parra; F. S. Rodrigo; Y. Castro-Díez (Climate Dynamics, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

On the Use of the Jesuit Order Private Correspondence Records in Climate Reconstructions: A Case Study from Castille (Spain) for 1634–1648 A.D. - F. S. Rodrigo; M. J. Esteban-Parra; Y. Castro-Diez (Climatic Change, 1998)

Spatial and temporal patterns of precipitation in Spain for the period 1880–1992 - M. J. Esteban-Parra; F. S. Rodrigo; Y. Castro-Diez (International Journal of Climatology, 1998)

Investigating the molecular basis of desiccation tolerance using the resurrection plant Craterostigma plantagineum as an experimental system - D. Bartels; J. Chandler; C. Bockel; W. Frank; M. Kleines; M. J. Rodrigo; J. Phillips; J. -B. Mariaux; A. Furini; F. Salamini (Acta Physiologiae Plantarum, 1997)

Parasitoeds (Hym.: Aphelinidae) of three scale insects (Hom.: Diaspididae) in a citrus grove in valencia, spain - E. Rodrigo; P. Troncho; F. García-Marí (BioControl, 1996)